Phosphocreatine mitigates pulmonary fibrosis in STZ-induced diabetic rats with bleomycin injury through TGF-β/Smad and Wnt/β-catenin pathways - Fu Han Wang; Abdulrahman Khaled Alwesabi; Eskandar Qaed; Waleed Aldahmash; Mueataz A. Mahyoub; Marwan almoiliqy (Tissue and Cell, 2027)

Urbanization drives rapid convergence of riverine greenhouse gas levels in the urban agglomeration, North China - Ling Wen; Zhengkui Ge; Yulin Qi; Dietrich A. Volmer; Chao Ma; Chunmei Chen; Zhifeng Yan; Pingqing Fu; Si-Liang Li (Agriculture, Ecosystems & Environment, 2026)

Selection and validation of stable reference genes for Actinobacillus succinogenes to support brewery wastewater valorization - Haidong Zhu; Aozhan Liu; Rajendra Prasad Singh; Ioannis A. Fotidis; Bin Hu; Dafang Fu; Yixin Yan (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Enhanced household food waste composting through biochar-immobilised composite bioaugmentation inoculum - Yixin Yan; Xiaoyu Chen; Zequn Sun; Dafang Fu; Rajendra Prasad Singh; Ioannis A. Fotidis (Journal of Environmental Chemical Engineering, 2026)

Radiocarbon Reveals Modern Carbon Exchange With Topsoil Inorganic Carbon in Drylands - Hui Wang; Jianbei Huang; Fernando T. Maestre; Guang Zhao; Nan Lu; Cong Wang; Weiliang Chen; De Shorn E. Bramble; Marion Schrumpf; Michaela A. Dippold; Yangjian Zhang; Sönke Zaehle; et al. (Global Change Biology, 2026)
Drylands store most of the global soil inorganic carbon (SIC), yet the extent to which this pool interacts with contemporary carbon (C) cycling remains poorly understood. To test whether SIC behaves primarily as an inert geological reservoir or instead bears a modern carbon imprint, we quantified SIC content and radiocarbon (∆ 14 C) at 42 dryland sites spanning broad aridity gradients across Eurasia. We also evaluated the climatic, edaphic, and biotic factors associated with variation in ∆ 14 C‐SIC. Across all sites, topsoil SIC (~0–10 cm) was strongly depleted in 14 C but consistently enriched relative to 14 C‐dead carbonates, indicating that it contains a measurable component derived from modern carbon inputs. In the Chinese drylands, ∆ 14 C‐SIC declined with increasing aridity, consistent with weaker modern carbon exchange under drier conditions and a greater contribution of inherited or 14 C‐depleted carbonate carbon. Soil pH and ∆ 14 C of soil organic carbon were the strongest predictors of ∆ 14 C‐SIC, suggesting that carbonate dissolution‐reprecipitation and the age of carbon entering soil CO 2 play key roles in determining SIC origins. At a subset of nine Chinese sites, ∆ 14 C‐SIC declined sharply with depth and approached 14 C‐dead values in subsoils, indicating little influence of modern carbon in deeper carbonate pools. The presence of mixed 14 C‐depleted and modern 14 C signatures in SIC potentially complicates the use of SIC isotopic signatures as proxies of environmental conditions. Together, our results indicate that dryland topsoil SIC commonly carries a measurable modern carbon signature that is tightly linked to contemporary carbon cycling. This coupling weakens with increasing aridity and soil depth, suggesting that environmental change in drylands may reshape one of the planet's largest carbon pools not only through changes in SIC stocks, but also through shifts in carbonate radiocarbon signatures and sources.

Up-to-date, and taxonomy-curated mcrA reference databases for methanogen community profiling - Sotirios Vasileiadis; Marios I. Valmas; Dimitra S. Pitsikoglou; Johana Rodosthenous; Michalis Omirou; Thomas A. Kotsopoulos; Yixin Yan; Dafang Fu; Ioannis A. Fotidis (Systematic and Applied Microbiology, 2026)

Evaluation of linear and circumferential slit virtual impactors for high flow rate, submicrometer particle concentration enrichment - Qingqing Fu; Susmita Islam; Li Li; Christopher J. Hogan; Bernard A. Olson (Journal of Aerosol Science, 2026)

40Ar/39Ar geochronology, SrNd isotopes and melting conditions of the Dahongshan alkaline basalts: Constraints on mantle modification beneath the northern Yangtze Craton - Yue Song; Xuan-Ce Wang; Simon A. Wilde; Xiang-Zhong Li; Chong-Jin Pang; Si-Yu Hu; Yang Luo; Jia-Xu Tang; Si-Zhe Fu (Chemical Geology, 2026)

Drought sensitivity and tree growth attributes regulate growth resilience of Southeast Asian pines under extreme drought - Rao-Qiong Yang; Pei-Li Fu; Zaw Zaw; Pieter A. Zuidema; Xiu-Chen Wu; Guang-You Hao; Shankar Panthi; Xin-Hua Peng; Tong-Liang Xu; Hui Zhang; Jia-Yan Shen; Achim Bräuning; et al. (Agricultural and Forest Meteorology, 2026)

Phosphocreatine attenuates diabetes-exacerbated kidney fibrosis via TGF-β/Smad and PI3K/Akt pathways in a dual rat model - Fu Han Wang; Abdulrahman Khaled Alwesabi; Wu Liu; Mueataz A. Mahyoub; Marwan almoiliqy; Eskandar Qaed; Waleed Aldahmash (Tissue and Cell, 2026)

Discovery of isotope 153Hf near the proton drip line via isochronous mass spectrometry: extending the nuclear landscape with HIAF - Hongfu Li; Min Zhang; Hongyang Jiao; Xing Xu; Chaoyi Fu; Jinyang Shi; Jiahao Lv; Xu Zhou; Yuanming Xing; Mingze Sun; Yuhu Zhang; Xiaohong Zhou; et al. (Science Bulletin, 2026)

Climate velocity outpaces static building-code assumptions in China - Nuodi Fu; Aijia Wang; Ruijun Zhang; Junqi Wang; Asim A. Ditta; Raúl Castaño-Rosa; Prashant Kumar; Fariborz Haghighat; Shi-Jie Cao (Journal of Cleaner Production, 2026)

Effects of urban greenbelt on ambient particulate matter under multiple urban stressors and their interactions during heavily polluted winter conditions - D.Y. Hao; H. Liu; J.Z. Song; A. Przybysz; R. Popek; H.J. Yi; J.C. He; Z.C. Fu; C.Y. Zhu (Atmospheric Pollution Research, 2026)

Microbial adaptation and environmental co-selection drive antimicrobial resistance risk in agricultural ditches, evidence from the multilevel ditch-river continuum - Xiangyao Wu; Yulin Qi; Lingchen Meng; Keyan Li; Chao Ma; Dietrich A. Volmer; Chunmei Chen; Peizhe Sun; Pingqing Fu; Zhifeng Yan (Journal of Hazardous Materials, 2026)

A review of early Paleozoic subduction-accretion tectonics in the North Qilian Orogenic Belt, Northeastern Tibet: Implications for the evolution of the Proto-Tethys Ocean - Dong Fu; Bo Huang; Timothy Kusky; Simon A. Wilde; Fengyu Qi; Xiaoxue Shan; Yilin Qu; Hong Wang (Earth-Science Reviews, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Optimizing Pistacia lentiscus (mastic tree) food and healthcare applications: phytochemical composition, extraction methods, quality control, and novel delivery systems - Mohamed A. Anwar; Yuting Fu; Haroun Khan; Mohamed A. Farag (Phytochemistry Reviews, 2026)
Pistacia lentiscus , from the Anacardiaceae family, is native to the Mediterranean region and best known for its aromatic resin, Chios mastic gum (CMG), which is exclusively produced on Chios Island, Greece. While the gum is the tree’s primary commercial product, various extracts from different P. lentiscus organs also hold potential applications due to their rich chemical profiles. This review assesses strategies to optimize the utilization of P. lentiscus products, not only the oleogum, in food and healthcare products. First, we review the phytochemical composition and environmental factors affecting this composition, highlighting conditions that maximize yield for different uses and applications. Additionally, various extraction techniques are reviewed, including solvent, ultrasonic-assisted, microwave-assisted, and supercritical fluid extraction methods, to identify the most effective methods. Authentication and quality control aspects, particularly for CMG, are compared, besides highlighting recent advances in novel delivery systems, i.e., liposomes, that are used to enhance the bioavailability of CMG key phytoconstituents. Graphical abstract

Contrasting behaviour in geogenic degassing along an active segment of the East Anatolian fault zone (Türkiye) - G. Yüce; W. D'Alessandro; C.C. Fu; F. Italiano; M. İçhedef; H. Elmacı; B. Kürkcüoğlu; B. Kahraman; A. Demirtaş; L.H. Lin; D. Yasin; Ş. Gürboğa; et al. (Applied Geochemistry, 2026)

Priming Effects on Soil Organic Matter Mineralization by Carbon Substrates: A Global Meta‐Analysis - Hongxin Dong; Yingyi Fu; Shanshan Dai; Peng He; Yu Luo; Margaret A. Oliver; William R. Horwath; Lu‐Jun Li (Global Change Biology, 2026)
Priming effects (PE) on soil organic matter (SOM) mineralization depend strongly on the type of carbon substrates added. It is crucial to understand the PE induced by various carbon substrates for predicting SOM dynamics and soil‐atmosphere carbon feedback. We conducted a meta‐analysis of 8015 observations from 283 articles to evaluate how carbon substrates (plant residues, root exudates, biochar, and degradable microplastics) regulate the mineralization of SOM through PE. Results demonstrated that all these types of carbon substrates increased SOM mineralization, which induced a positive PE. Plant residues induced the highest average PE, followed by root exudates, biochar, and degradable microplastics. Compared to soils without carbon substrate inputs, the rate of SOM mineralization increased by 113% in soil with cellulose‐rich non‐woody residues, whereas it increased by only 25% in soil with lignin‐rich woody residues. The mineralization of SOM increased by organic acids (151%) was greatest in root exudates, followed by monosaccharides (60%) and polysaccharides (12%). The strong mineralization induced by organic acids was probably related to the release of more mineral nutrients by reducing soil pH. The PE on SOM mineralization by woody biochar with high aromatic carbon content (48%) was greater than that of non‐woody biochar with high alkyl carbon content (43%). Microplastics with rapidly degradable polyhydroxyalkanoates induced more SOM mineralization (258%) than polybutylene succinate (61%) and polybutylene adipate‐co‐terephthalate (21%). The SOM priming was positively correlated with soil clay and incubation moisture, and negatively correlated with soil organic carbon, total nitrogen, soil C:N ratio, dissolved organic carbon, microbial biomass carbon, carbon input rate, incubation temperature, and soil depth. These results show that the positive PE is ubiquitous in soil ecosystems; its magnitude is linked intrinsically to the physicochemical characteristics and source of exogenous carbon substrate.

Carbon emission prediction based on spatial–temporal pattern recognition and novel integrated vine copula - A. Xu; S. Fang; J. Chen; Z. Fu; Z. Chen (International Journal of Environmental Science and Technology, 2026)

‘Building the (Im)perfect Beast’: Strategies for Identifying Appropriate Spatial Stock Assessment Model Complexity From an International, Blinded High‐Resolution Simulation Experiment - Aaron M. Berger; Daniel R. Goethel; Simon D. Hoyle; Patrick Lynch; Caren Barceló; Alistar Dunn; Brian J. Langseth; Carolina Minte‐Vera; Jemery Day; Haikun Xu; Francisco Izquierdo; Dan Fu; et al. (Fish and Fisheries, 2026)
Despite their potential to inform sustainable regional harvest and climate‐resilient fisheries management, spatial stock assessment models remain underused for management advice. To identify barriers that inhibit broader use of these methods, we conducted a blinded international simulation experiment mimicking real‐world stock assessment development when confronting spatial complexity. Seven analyst teams built spatially aggregated and spatially explicit assessment models using data simulated from high‐resolution operating models based on Indian Ocean yellowfin tuna and Ross Sea Antarctic toothfish dynamics. Each team documented how assessment software platform, data analyses, model building approach, and diagnostics influenced model complexity and realism. A consensus emerged on key assessment building approaches: (1) conduct high‐resolution data analyses to identify appropriate spatial structure; (2) start with simplified models and incrementally add complexity; (3) iteratively evaluate diagnostics to determine necessary spatial complexity; and (4) maintain models with different spatial structures to aid interpretation. The experiment also revealed several valuable insights for parameterising assessments, including consideration of data pre‐processing with spatiotemporal models to better inform data‐sparse regions; regression trees to identify fleet and spatial structure; trade‐offs in complexity between productivity and movement dynamics to achieve tractable and stable model structures; and ensemble modelling approaches to address structural uncertainty. Our findings demonstrate that international collaborations and simulation experiments are crucial for addressing challenges in implementing spatial stock assessments and for evaluating whether their added complexity is justified given management objectives. Broader collaborations are encouraged to foster innovation in fisheries management and to help recognise the practical trade‐offs between model parsimony and complexity.

GLS-YOLOv8n: a lightweight ‘Guiqi’ mango detection model via RGB-depth-thermal image fusion - Weihua Cao; Zhao Zhang; Zeping Wang; Ailin Wei; Qianfu Chen; C. Igathinathane; Fu Zhang; Mahmoud A. Abdelhamid; Dapeng Ye; Yiannis Ampatzidis (Computers and Electronics in Agriculture, 2026)

Phosphocreatine attenuates doxorubicin-induced hepatotoxicity via activation of Nrf2/HO-1 and PGC-1α pathways in mice - Eskandar Qaed; Mueataz A. Mahyoub; Waleed Q.A. Naji; Fu Han Wang; Wu Liu; Waleed Aldahmash; Zeyao Tang; Marwan almoiliqy (Tissue and Cell, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Temporal variation of water content in the lithospheric mantle beneath the central North China Craton: New evidence from mantle xenocrystic pyroxenes - Yao Xu; Hong-Fu Zhang; A-Bing Lin; Chao Zhang (Lithos, 2026)

Late Neoproterozoic arc-fore-arc magmatism from the South Eastern Desert of Egypt: Geochronology, whole-rock geochemistry, Hf-Nd isotopic compositions, and implications for Gondwana assembly - Amro M. Diab; Abdel-Kader M. Moghazi; Fawzy F. Abu El-Ela; Mahmoud K. Alawy; Fu-Yuan Wu; Hisham A. Gahlan; Mohamed A. Abd El Wahed; Kamal A. Ali (Gondwana Research, 2026)

Discovery, herbicidal activity evaluation, and mechanism of action of Heteroaryl chalcones as novel HPPD inhibitors - Li-xia Zhao; Dmitry B. Rubinov; Pan-xiu Zhang; Veronica G. Zinovich; Wen-qing Yu; Tatyana S. Khlebnicova; Fei Ye; Ying Fu; Fedor A. Lakhvich (Pesticide Biochemistry and Physiology, 2026)

Response of dry-wet abrupt alternation to precipitation variation in the Hailar River Basin, northern China - Yanchao Fu; Baolin Xue; Yuntao Wang; Yinglan A; Jin Wu (Journal of Contaminant Hydrology, 2026)

Fine-scale patterns and drivers of ploidy state in lentic and lotic macrophyte assemblages across the world - Tatiana Lobato-de Magalhães; Kevin Murphy; Thomas A. Davidson; Jorge García-Girón; Andrey Efremov; Victor Chepinoga; Eugenio Molina-Navarro; Celeste Franceschini; Roger P. Mormul; Hui Fu; Rossano Bolpagni; Juri Nascimbene; et al. (Aquatic Botany, 2026)

Event‐Specific Meteorological Drivers Shape Diverse Water‐Use Efficiency Trajectories Under Drought Propagation - Feng Li; Qinchuan Xin; Julia K. Green; Chuixiang Yi; Armen R. Kemanian; Steven A. Kannenberg; Paul C. Stoy; Yuting Yang; Huimin Lei; Yujiu Xiong; Zheng Fu (Global Change Biology, 2026)
Drought propagation from meteorological to soil drought marks a critical phase in regulating vegetation water–carbon dynamics, yet the response trajectories of water‐use efficiency (WUE) during these events remain poorly understood. Here, combining global flux tower observations with simulations from Earth System Models (ESMs), we quantified the spatiotemporal patterns of drought propagation characteristics, identified WUE response trajectories for characteristic‐specific droughts, and investigated their dominant drivers. We found that 58% of soil droughts follow meteorological droughts. Most sites experience drought propagation events with increasing intensity, faster propagation, and shorter intervals. Among all identifiable trajectories, nonmonotonic patterns account for approximately 60%. WUE response trajectories generally follow continuous and nonmonotonic patterns, dominated by a rise‐then‐fall pattern. This pattern reflects a process in which vegetation functions regulated by stomatal behavior are initially stressed and then partially recover. Intra‐site variability is extremely pronounced, mainly driven by event‐specific thermal factors such as air temperature and net radiation. ESMs reproduce broad site‐level prevalence of nonmonotonic patterns, but show discrepancies in the relative importance of drivers due to the coupling of different land surface models. These findings challenge the notion of fixed vegetation functional responses and highlight the dynamic variability of response trajectories in relation to event‐specific characteristics, and provide concrete diagnostics to guide model improvements.

Congo Basin Carbon Cycle Responses to Global Change - Sarah Worden; Rong Fu; A. Anthony Bloom; Marijn Bauters; Hans Verbeeck; Temilola Fatoyinbo; Wannes Hubau; Lydie‐Stella Koutika; Steve Kwatcho Kengdo; Sybryn L. Maes; Vincent Medjibe; Nicholas J. Russo; et al. (Global Change Biology, 2026)
The Congo Basin and its contiguous forests harbor globally significant carbon stocks, estimated at 65 gigatons of C (GtC) above and belowground. Despite rising temperatures and intensifying droughts, they have remained a carbon sink, albeit weak: 0.26–0.50 GtC yr. −1 carbon uptake since 1980. However, these forests' carbon stocks and fluxes, including gross primary productivity, respiration, net primary productivity, and riverine carbon transport, remain poorly quantified. This limits understanding of the region's role in the global carbon cycle, its vulnerability to environmental change, and its potential as a long‐term carbon sink. We review and quantify Congo Basin and contiguous forest carbon stocks and fluxes and synthesize the current knowledge on how key global change drivers shape the region's carbon cycle. We find limited responses to long‐term precipitation variability, but declining stocks and fluxes in response to long‐term and increasing temperature and drought frequency. Land cover and land use changes, largely driven by small‐scale agriculture, logging, and agro‐industrial expansion, reduce carbon stocks, ecosystem structure and functioning, and animal‐mediated ecosystem services. In contrast, large‐scale savanna biomass burning delivers phosphorus and nitrogen to Congo Basin forests via cross‐equatorial winds, providing additional nutrients and supporting carbon sequestration. In situ studies suggest that CO 2 fertilization has increased intrinsic water‐use efficiency, although its effects may be modulated by climate change, and its impacts on biomass accumulation remain uncertain. Legacy effects from historical land use and climate change likely shaped present‐day vegetation structure, yet their relative influence is unclear. High‐resolution carbon monitoring, improved remote sensing, and strengthened in situ measurement networks are needed to quantify the impacts of these key drivers and their interactions on the Central African carbon cycle. This is needed to inform conservation strategies and advance understanding of the region's future as a carbon sink under global change pressures.

Prof Stephen P. Long, FRS (1950–2025) - Lorenzo Álvarez‐Filip; Edith Bai; Carl J. Bernacchi; Rhea Bruno; Klaus Butterbach‐Bahl; Maria Byrne; I‐Ching Chen; Shaolin Chen; William W. L. Cheung; M. Francesca Cotrufo; Tatenda Dalu; Xiaojuan Feng; et al. (Global Change Biology, 2025)

Recent advances in the discovery of novel bleaching herbicides inspired by natural products - Tengfei Ma; Tiansong Li; Yi Zhang; Fedor A. Lakhvich; Tatyana S. Khlebnicova; Ying Fu; Fei Ye (Pesticide Biochemistry and Physiology, 2025)

Stage–discharge relationships in vegetated channels with overbank floods - Hongsheng Fu; Yuqi Shan; Marwan A. Hassan; Kejun Yang; Chao Liu (Journal of Hydrology, 2025)

Interpretable-generative machine learning approaches for predicting simultaneous removal of organic pollutants and heavy metals from water by adsorbent materials - Mudi Zhai; Zhaozhong Wu; Bomin Fu; Jingzhang Sun; Mohamad Sleiman; Frederic C. Meunier; Junsen Wang; Weijie Wang; Tianrun Wang; Haoran Duan; Zisheng Ai; Jose Luis Valverde; et al. (Journal of Cleaner Production, 2025)

Phosphocreatine alleviates liver fibrosis in diabetic mice by targeting TGF-β/Smad and α-SMA pathways - Fu Han Wang; Eskandar Qaed; Waleed Aldahmash; Mueataz A. Mahyoub; Dalal Sanad Al-Mutairi; Zeyao Tang; Marwan almoiliqy (Tissue and Cell, 2025)

Recycling of continental crust into the deep mantle in orogens: Constraints from zircon U-Pb-Hf-O and whole-rock Mg-Fe isotopes of Baihua complex, North Qinling Orogen - Gang Yang; Juan Zhang; Hong-Fu Zhang; An-Ping Chen; A-Bing Lin (Chemical Geology, 2025)

Sources and potential health indicators in urban aerosols revealed by gas chromatography-mass spectrometry combined with nitrogen chemiluminescence detector: evidence from a megacity (Tianjin) of China - Jingying Ma; Yulin Qi; Yufu Han; Jinfeng Ge; Ling Wen; Xiaoli Fu; Wei Hu; Zongbo Shi; Dietrich A. Volmer; Pingqing Fu (Atmospheric Environment, 2025)

P30-60 Grouping and assessment of chemicals for hazard and risk assessment by high content analysis using the zebrafish embryos as an alternative non-sentient animal model - S. Scholz; C. Zanini; A.-K. Koblitz; T. Möller; M.A. Aslam; G.C. Ajugwo; E. Chukwu; J. Colbourne; S. Kader; Q. Fu; N. Grasse; T. Reemtsma; et al. (Toxicology Letters, 2025)

P30-57 Towards a Defined Approach to Assess Pesticides for their Potential to Cause Parkinsonian Neurodegeneration - J. Nyffeler; T. Tal; S. Schildknecht; B. Viviani; B. Tanja; Q. Fu; R. Owen; A.E.V. Krishnakumar; I. Mangas; A. Terron (Toxicology Letters, 2025)

P16-05 The zebrafish microbiome has the capacity to bioactivate PFOS precursor compounds - S. Gutsfeld; C. Wray; N. Schweiger; A. Röhrig; H. Paschke; Q. Fu; J. Kasmanas; S. Kader; U. da Rocha; T. Tal (Toxicology Letters, 2025)

Histological differences between brachycephalic and normocephalic dog palatine tonsils - Isabella A. Smith; Philip A. Moses; William B. Moses; Jamie Fu; Xena Yap; Daniel McGilp; Michelle M. Story; Rachel Allavena (Research in Veterinary Science, 2025)

Physiological and molecular responses to different sizes of polystyrene micro/nanoplastics in the model unicellular eukaryote Paramecium tetraurelia - Ping Ni; Congjun Li; Yu Fu; Naomi A. Stover; Lifang Li (Journal of Hazardous Materials, 2025)

A low oxygen threshold for physiological responses and trace metal quotas of Prochlorococcus and Synechococcus - Joan De Vera; Yuanyuan Feng; Feixue Fu; Shun‐Chung Yang; Amjad Mansour; Nicholas J. Hawco; David A. Hutchins; Seth G. John (Limnology and Oceanography, 2025)
Continued human activity is expected to accelerate ocean deoxygenation, leading to the expansion and shallowing of oxygen‐deficient zones (ODZs). This decline in oxygen may impact both phytoplankton growth and trace metal uptake. We conducted culture experiments with Prochlorococcus MIT9313 and Synechococcus XM‐24, two numerically dominant genera of marine picocyanobacteria, under varying O 2 levels (36–242 μ M). These experiments provide some of the first data on trace metal quotas in phytoplankton under varying O 2 conditions in culture. Moderate deoxygenation, above hypoxic levels, did not negatively impact the growth and trace metal quotas of either Prochlorococcus MIT9313 or Synechococcus XM‐24 (80 and 85 μ M O 2 , respectively). Indeed, some parameters (e.g., growth rate, carbon fixation and chlorophyll fluorescence) suggest slight growth enhancement at these moderate levels of deoxygenation. However, hypoxic conditions (36 μ M O 2 ) significantly inhibited the growth of Prochlorococcus MIT9313, suggesting a minimum O 2 threshold needed to prevent disruptions in O 2 ‐dependent processes. Synechococcus XM‐24 exhibited no significant response to elevated p CO₂ (1054 μ atm), indicating possible adaptation to variable coastal CO₂ environments. Changes in trace‐metal quotas (metal‐to‐phosphorous ratios; metal/P) were also observed when Prochlorococcus MIT9313 was cultured under hypoxia, including up to 48% increases in Fe/P, 48% decreases in Ni/P, and 27% decreases in Co/P, compared to oxic conditions. These results contrast with elevated metal/P ratios in autotrophic‐associated particles from ODZs, suggesting either distinct metal uptake strategies by phytoplankton in low‐O 2 regions or that elevated particulate metals are influenced by other plankton types such as heterotrophs.

Integrated hydrothermal pretreatment and enzymatic hydrolysis for optimal succinic acid production from the liquid fraction of municipal food waste - Yixin Yan; Aozhan Liu; Qingyu Shang; Rajendra Prasad Singh; Dafang Fu; Thomas A. Kotsopoulos; Ioannis A. Fotidis (Journal of Cleaner Production, 2025)

Exploring Lumbar Ligamentum Flavum, Disc Height and Foraminal Height Variations Across Different Postures: A Cadaveric Computed Tomography Investigation - Yuan-Fu Liu; Nozomu Inoue; Yu-Hua Dean Fang; Jing-Yao Wang; Alejandro A. Espinoza Orías; Chao-Jui Chang; Cheng-Li Lin (Journal of Medical and Biological Engineering, 2025)

Making waves: Pioneering a nanoconfinement platform with mesoporous silica for sustainable water management and environmental applications - Haklae Lee; Han Fu; Kimberly A. Gray (Water Research, 2025)

Cyclosiloxane artifacts explain reported Henry’s law constants for nonvolatile fluorotelomer sulfonates - Sophia K. Nelson; Mitchell L. Kim-Fu; Mohammad Azizian; Jennifer A. Field (Journal of Hazardous Materials, 2025)

Phosphorus recovery through struvite crystallization from real wastewater: Bridging gaps from lab to market - Yixin Yan; Nomiki I. Kallikazarou; Olympia Nisiforou; Qingyu Shang; Dafang Fu; Maria G. Antoniou; Ioannis A. Fotidis (Bioresource Technology, 2025)

Limited Regulation of Canopy Water Use Efficiency by Stomatal Behavior Under Drought Propagation - Feng Li; Qinchuan Xin; Chuixiang Yi; Steven A. Kannenberg; Julia K. Green; Mirco Migliavacca; David J. P. Moore; Armen R. Kemanian; Pierre Gentine; Paul C. Stoy; Fangyue Zhang; Yujiu Xiong; et al. (Global Change Biology, 2025)
Water use efficiency (WUE) is a critical ecosystem function and a key indicator of vegetation responses to drought, yet its temporal trajectories and underlying drivers during drought propagation remain insufficiently understood. Here, we examined the trajectories, interdependencies and drivers of multidimensional WUE metrics and their components (gross primary production (GPP), evapotranspiration, transpiration (T), and canopy conductance (Gc)) using a conceptual drought propagation framework. We found that even though the carbon assimilation efficiency per stomata increases during drought, the canopy‐level WUE (represented by transpiration WUE (TWUE)) declines, indicating that stomatal regulation operates primarily at the leaf level and cannot offset the drought‐induced reduction in WUE at the canopy scale. A stronger dependence on T and TWUE indicates that the water–carbon trade‐off relationship of vegetation more inclines toward water transport than carbon assimilation. Gc fails to prevent the sharp decline in GPP during drought and has limited capacity to suppress T, as reflected by the reduction magnitude and the threshold (the turning point at which a component shifts from a normal to drought‐responsive state). The primary drivers of the water–carbon relationship under drought propagation include vapor pressure deficit and hydraulic traits. Among plant functional types, grasslands show the strongest water–carbon fluxes in response to drought, whereas evergreen broadleaf forests exhibit the weakest response. These findings refine our comprehensive understanding of multidimensional ecosystem functional dynamics under drought propagation and enlighten how the physiological response of vegetation to drought affects the carbon and water cycles.

Meta‐Omics Analysis Reveals Global Distribution of Toxic Pseudo‐nitzschia and Enhanced Neurotoxin Production Under Climate Warming - Dong Xu; Zhuonan Wang; Georgina L. Brennan; Yuqiu Wei; Guanchao Zheng; Qingshan Luan; Xintong Huang; Yanmin Sun; Jia Yang; Xiaowen Zhang; Ke Sun; Xiao Fan; et al. (Global Change Biology, 2025)
The harmful diatom Pseudo‐nitzschia produces the neurotoxin domoic acid (DA), threatening human health and seafood safety in a changing climate. However, global patterns of Pseudo‐nitzschia abundance and the responses of DA production to underlying environmental drivers remain poorly understood, hindering accurate projections of their responses to environmental change. Using global meta‐omics data from Tara Oceans, alongside field survey data from the Chinese coasts and the Southern Ocean, we present the first evidence that four of the most toxic species— Pseudo‐nitzschia multiseries , Pseudo‐nitzschia multistriata , Pseudo‐nitzschia delicatissima , and Pseudo‐nitzschia pungens —are prevalent not only in coastal ecosystems but also in open ocean environments, spanning from pole to pole. We identify rising temperatures are recognized as a key driver of Pseudo‐nitzschia 's spatial distribution, DA production, and biosynthetic metabolism. Global models suggest that by 2100, under the SSP2‐4.5 climate scenario, the abundance of P. multiseries will increase by approximately 75.4%, while toxin production will be even more significantly enhanced, rising by up to 200.4%. This study significantly expands the known global distribution of these neurotoxin‐producing diatoms and predicts their increasing prevalence and toxicity under future global changes.

Long-term stored lyophilized methanogenic inocula to bioaugment biomethanation of problematic biomasses - Ioannis A. Fotidis; Dimitra Pitsikoglou; Sotirios Douklias; Thomas A. Kotsopoulos; Jaime Moreno Garcia; Dafang Fu; Yixin Yan (Journal of Environmental Chemical Engineering, 2025)

Correction to: Appraising flood risk and inundation extent using GIS-aided 2D hydraulic modeling in Nepal Himalaya: a case of West Rapti river Basin - Amrit Prasad Sharma; Xudong Fu; Giri R. Kattel; Tirtha Raj Adhikari; Marwan A. Hassan (Modeling Earth Systems and Environment, 2025)

Appraising flood risk and inundation extent using GIS-aided 2D hydraulic modeling in Nepal Himalaya: a case of West Rapti River Basin - Amrit Prasad Sharma; Xudong Fu; Giri R. Kattel; Tirtha Raj Adhikari; Marwan A. Hassan (Modeling Earth Systems and Environment, 2025)

Mapping the landscape of bird strike research: insights from a quantitative analysis - H. X. Wang; W. Fu; N. A. Razak; Y. Y. Shi (International Journal of Environmental Science and Technology, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

The importance of tropical tree-ring chronologies for global change research - Peter Groenendijk; Flurin Babst; Valerie Trouet; Ze-Xin Fan; Daniela Granato-Souza; Giuliano Maselli Locosselli; Mulugeta Mokria; Shankar Panthi; Nathsuda Pumijumnong; Abrham Abiyu; Rodolfo Acuña-Soto; Eduardo Adenesky-Filho; et al. (Quaternary Science Reviews, 2025)

Comprehensive modification of cratonic lithospheric mantle beneath the central North China Craton: Insights from Li isotope systematics of olivine xenocrysts in Cenozoic basalts - Yao Xu; Hong-Fu Zhang; Yan-Jie Tang; A-Bing Lin; Juan Zhang; Ming-Jie Zhang (Chemical Geology, 2025)

Relative phase between tidal and solar cycles influences the heating of a coral atoll lagoon - Sarah Ruth Merrigan; Geno Pawlak; Gregory Sinnett; Ke‐Hsien Fu; Kristen A. Davis (Limnology and Oceanography, 2025)
We seek to understand the physical processes driving a recent warming event in Dongsha Atoll lagoon, a coral atoll in the South China Sea. The system has experienced hypoxia‐related fish kills and seagrass die‐offs, further motivating our understanding of circulation and exchange within the lagoon. Hydrographic observations were collected in summer 2019 to examine circulation and ocean–lagoon exchange. A heat budget was constructed to investigate the relative influence of tides, wind, waves, surface heating, and advective ocean–lagoon exchange on the lagoon heat content. Volume fluxes also allow for the estimate of bulk lagoon flushing time, which is critical in driving water temperatures, biogeochemical cycles, and reef ecosystem functions. Over the 22‐d study period, the lagoon warmed by 1.5°C, driven primarily by solar radiative heating. Surface heat fluxes were balanced by cooling from advective exchange through deeper channels and over the shallow reef flat surrounding the lagoon. Without these cooling flows, the lagoon would have heated by 4.5°C over the study period. Estimated flushing times for the Dongsha Atoll lagoon range from 4.6 to 6.1 d for spring and neap tide. A phase‐locked interaction between the diurnal solar cycle and the diurnal tide drives advective cooling over the reef flat into the lagoon at night during the summer, especially during spring tide. These results highlight a unique mechanism shaping seasonal patterns in circulation and heat fluxes in a diurnal‐tide‐dominated reef system, which is likely important for other biogeochemical parameters and in shallow coastal ecosystems with similar tidal forcing.

ApoM-bound S1P acts via endothelial S1PR1 to suppress choroidal neovascularization and vascular leakage - Bongnam Jung; Hitomi Yagi; Andrew Kuo; Tim F. Dorweiler; Masanori Aikawa; Taku Kasai; Sasha A. Singh; Andrew J. Dannenberg; Zhongjie Fu; Colin Niaudet; Lois E. H. Smith; Timothy Hla (Angiogenesis, 2025)

Constraints of the paleowind directions on the paleogeography of the North China, South China and Tarim cratons during the Ediacaran Period - C. L. Hu; Z. Q. Lin; J. A. Quaye; X. B. Fu (Australian Journal of Earth Sciences, 2025)

Global Soil Methane Uptake Estimated by Scaling Up Local Measurements - Jiawei Jiang; Zhifeng Yan; Jinshi Jian; Shushi Peng; Hanqin Tian; Kendalynn A. Morris; Robert M. Ellam; Jesper Riis Christiansen; Huai Chen; Jianzhi Dong; Si‐Liang Li; Pingqing Fu; et al. (Global Change Biology, 2025)
Aerobic soils remove methane from the atmosphere, but global soil methane uptake (SMU) estimates remain highly uncertain due to challenges in scaling local data. We develop a data‐driven approach to refine this global estimate by incorporating local data of 79,800 flux measurements from 198 sites. This novel approach links the global SMU budget to local SMU fluxes by varying its parameters with soil properties. Our 2003–2018 global SMU estimate is ~39.0 Tg CH 4 year −1 —about 30% higher than existing bottom‐up estimates and consistent with top‐down assessments. Cold grasslands and deserts were found to contribute nearly 30% of the total SMU, while disturbed agricultural biomes have the lowest SMU. The projected future global SMU is shaped by temperature and atmospheric methane, though local SMU is primarily influenced by changes in soil moisture. This study emphasizes the potential of soils in climate regulation and highlights the need to focus on key biomes for a better understanding of the soil‐atmosphere methane feedback and optimizing methane management strategies.

Comprehensive extractables and leachables sensitization analysis and practical application of a risk-based approach to sensitization assessment for parenteral drug products - Patricia Parris; Geraldine Whelan; Martyn L. Chilton; Claire Beaumont; Anders Burild; Uma Bruen; Courtney Callis; Jessica Graham; Natalia Kovalova; Elizabeth A. Martin; Melisa Masuda-Herrera; Carsten Worsøe; et al. (Regulatory Toxicology and Pharmacology, 2025)

Cytochrome P450 CYP6EM1 confers resistance to thiamethoxam in the whitefly Bemisia tabaci (Hemiptera: Aleyrodidae) via detoxification metabolism - Mingjiao Huang; Peipan Gong; Cheng Yin; Jing Yang; Shaonan Liu; Buli Fu; Xuegao Wei; Jinjin Liang; Hu Xue; Chao He; Tianhua Du; Chao Wang; et al. (Pesticide Biochemistry and Physiology, 2025)

Role of an allowable chloride range in drinking water in corrosion and bacteria colonization of ferrous distribution systems: Patterns at varying temperatures and sulfate levels - Muhammad A. Imran; Lei Fu; Xiaozhou Yang; Manjie Li (Journal of Water Process Engineering, 2025)

Back-analysis of the 2000 Yigong dam breach flood morphodynamics: Challenges and promises - Yunlong Lei; Marwan A. Hassan; Giorgio Rosatti; Luigi Fraccarollo; Daniel Zugliani; Xudong Fu; Chunhong Hu (Geomorphology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

The induction of polyamines metabolism pathway and membrane stability with silicon alleviate the vanadium toxicity in pepper plants - Naveed Mushtaq; Muhammad Ahsan Altaf; Huangying Shu; Xu Lu; Shanhan Cheng; Mohamed A. El-Sheikh; Parvaiz Ahmad; Huizhen Fu; Zhiwei Wang (Journal of Hazardous Materials, 2025)

Drivers of forest productivity in two regions of the United States: Relative impacts of management and environmental variables - Hazhir Karimi; Michael Binford; William Kleindl; Gregory Starr; Bailey A. Murphy; Ankur R. Desai; Chiung-Shiuan Fu; Michael C. Dietze; Christina Staudhammer (Journal of Environmental Management, 2025)

Hypotensive effect of potent angiotensin-I-converting enzyme inhibitory peptides from corn gluten meal hydrolysate: Gastrointestinal digestion and transepithelial transportation modifications - Phiromya Chanajon; Ali Hamzeh; Fu Tian; Sittiruk Roytrakul; Olayinka A. Oluwagunwa; Deepak Kadam; Rotimi E. Aluko; Sasitorn Aueviriyavit; Ratjika Wongwanakul; Jirawat Yongsawatdigul (Food Chemistry, 2025)

Fully Coupled Thermo-hydro-mechanical Model for Wellbore Stability Analysis in Deep Gas-Bearing Unsaturated Formations Based on Thermodynamics - Tianshou Ma; Jinhua Liu; Jianhong Fu; Yi Qiu; Xiangyu Fan; Dmitriy A. Martyushev (Rock Mechanics and Rock Engineering, 2025)

Attributions of Rainfall Anomalies to Weather Systems and Their Spatial and Temporal Variabilities: A Case Study of Victoria in Southeast Australia - Guobin Fu; Francis H. S. Chiew; David A. Post; Acacia Pepler; Irina Rudeva (International Journal of Climatology, 2024)
Attributions of rainfall anomalies to weather systems and their spatio‐temporal variability in Victoria, southeast Australia are investigated with a multimethod weather type dataset and two popularly used gridded daily rainfall datasets for the period 1979–2015. The rainfall anomalies before, during and after the Millennium Drought (1997–2009) are compared to quantify the temporal variability of rainfall responses to weather type changes. The results show: (1) Three weather systems (Front, Cyclone and Thunderstorm) and their combinations contribute 89% of total rainfall; (2) Contributions of weather types to rainfall vary from month to month with winter season rainfall coming from more diverse weather types than summer rainfall; (3) The contributions of weather types to rainfall in three periods show temporal variabilities and there is a clear shift of contribution pattern after the Millennium Drought, such as front‐thunderstorm (FT) is now the largest contributor to rainfall compared with cyclone‐frontal‐thunderstorm (CFT) before and during the Millennium Drought; (4) A seasonal shift in the post‐drought period is found with higher rainfall in February and March and lower rainfall in September and October. The increased rainfall in February mainly results from Front–Thunderstorm (FT) and Thunderstorm‐only (TO), while rainfall declines in September from all weather types; (5) Several rainfall characteristics that are important for streamflow generation, such as rainfall intensity, probability of rainfall occurrence, number of rainfall days and the maximum daily rainfall, do depend on the weather types; (6) The results are similar with different rainfall datasets, but differences do exist, especially at the local scale. The conclusions of this study are drawn from an Australian case study but have implications for other regions to investigate the attributions of rainfall characteristic changes to weather systems.

Yield prediction of root crops in field using remote sensing: A comprehensive review - Hanhui Jiang; Liguo Jiang; Leilei He; Bryan Gilbert Murengami; Xudong Jing; Paula A. Misiewicz; Fernando Auat Cheein; Longsheng Fu (Computers and Electronics in Agriculture, 2024)

Phosphocreatine ameliorates hepatocellular apoptosis mediated by protecting mitochondrial damage in liver ischemia/reperfusion injury through inhibiting TLR4 and Agonizing Akt Pathway - Fu Han Wang; Eskandar Qaed; Waleed Aldahmash; Mueataz A. Mahyoub; Zhongyuan Tang; Peng Chu; Ze Yao Tang (Tissue and Cell, 2024)

Graphene-encapsulated nanocomposites: Synthesis, environmental applications, and future prospects - Han Fu; Kimberly A. Gray (Science of The Total Environment, 2024)

Individual and combinatorial application of nanosilica and carbon nanoparticles alleviate nickel stress in barley (Hordeum vulgare L.): Impacts on gene expression, AsA − GSH cycle, cellular fractionation, and proline metabolism - Zhanbin Luo; Manar Fawzi Bani Mfarrej; Muhammad Hamzah Saleem; Jing Ma; Ibrahim A. Saleh; Mostafa A. Abdel-Maksoud; Adel M. Zakri; Fu Chen; Leobardo Manuel Gómez Oliván (Science of The Total Environment, 2024)

Mitigating risks from atrazine drift to soybeans through foliar pre-spraying with a degrading bacterium - Xin Wen; Leilei Xiang; Jean Damascene Harindintwali; Yu Wang; Chao He; Yuhao Fu; Siqi Wei; Syed A. Hashsham; Jiandong Jiang; Xin Jiang; Fang Wang (Journal of Hazardous Materials, 2024)

An improved convolutional architecture for quantitative characterization of pore networks in fine-grained rocks using FIB-SEM - Bo Liu; Qamar Yasin; Mengdi Sun; Atif Ismail; David A. Wood; Xin Tian; Baiquan Yan; Li Fu (International Journal of Coal Geology, 2024)

Control of stepwise subduction and slab breakoff on volcanism and uplift in the Tibetan Plateau - Jian Wang; Zhi Wang; Xiugen Fu; Xuan-Ce Wang; Simon A. Wilde; Yi Fu; Jian Lin; Hengye Wei; Lijun Shen; Gang Rao; Ahmed Mansour (Earth and Planetary Science Letters, 2024)

Chemical classification of spherules recovered from the Pacific Ocean site of the CNEOS 2014-01-08 (IM1) bolide - A. Loeb; S.B. Jacobsen; R. Tagle; T. Adamson; S. Bergstrom; J. Cherston; R. Cloete; S. Cohen; L. Domine; H. Fu; C. Hoskinson; E. Hyung; et al. (Chemical Geology, 2024)

Evolution and legacy of East Asian aurochs - Jiawen Hou; Xiwen Guan; Xiaoting Xia; Yang Lyu; Xin Liu; Yuri Mazei; Ping Xie; Fengqin Chang; Xiaonan Zhang; Jialei Chen; Xinyi Li; Fengwei Zhang; et al. (Science Bulletin, 2024)

Biofilm enhanced the mitigations of antibiotics and resistome in sulfadiazine and trimethoprim co-contaminated soils - Zhi Mei; Fang Wang; Yuhao Fu; Yu Liu; Syed A. Hashsham; Yu Wang; Jean Damascene Harindintwali; Qingyuan Dou; Marko Virta; Xin Jiang; Yu Deng; Tong Zhang; et al. (Journal of Hazardous Materials, 2024)

Paleoredox and lithofacies assessments in Deepwater intervals of the Monterey Formation, Santa Maria Basin, California: Insights from organic sulfur geochemistry - Ana Vielma; Joseph A. Curiale; Humberto Carvajal-Ortiz; Jagoš R. Radović; Qi Fu; Thomas B. Malloy; K.K. (Adry) Bissada (International Journal of Coal Geology, 2024)

Synergetic Interplay of MnNi-MOF Composite with 2D MXene for Improved Supercapacitor Application - S. Siva Shalini; Yen-Pei Fu; A. Chandra Bose (Chemical Engineering Journal, 2024)

MSH6-proficient crypt foci in MSH6 constitutional mismatch repair deficiency: reversion of a frameshifted coding microsatellite to its wild-type sequence - Jinru Shia; Francisco Sanchez-Vega; Stanley Cho; Jie-Fu Chen; Chin-Tung Chen; Umesh Bhanot; Nil Urganci; Canan Firat; Peter Ntiamoah; Raymond A. Isidro; Amitabh Srivastava; Martin R. Weiser; et al. (Familial Cancer, 2024)

Correction: Mitochondrial control of hypoxia-induced pathological retinal angiogenesis - Hitomi Yagi; Myriam Boeck; Shen Nian; Katherine Neilsen; Chaomei Wang; Jeff Lee; Yan Zeng; Matthew Grumbine; Ian R. Sweet; Taku Kasai; Kazuno Negishi; Sasha A. Singh; et al. (Angiogenesis, 2024)

Timed topical dexamethasone eye drops improve mitochondrial function to prevent severe retinopathy of prematurity - Hitomi Yagi; Myriam Boeck; Mariya Petrishka-Lozenska; Pia Lundgren; Taku Kasai; Gael Cagnone; Katherine Neilsen; Chaomei Wang; Jeff Lee; Yohei Tomita; Sasha A. Singh; Jean-Sébastien Joyal; et al. (Angiogenesis, 2024)
Pathological neovascularization in retinopathy of prematurity (ROP) can cause visual impairment in preterm infants. Current ROP treatments which are not preventative and only address late neovascular ROP, are costly and can lead to severe complications. We showed that topical 0.1% dexamethasone eye drops administered prior to peak neovessel formation prevented neovascularization in five extremely preterm infants at high risk for ROP and suppressed neovascularization by 30% in mouse oxygen-induced retinopathy (OIR) modeling ROP. In contrast, in OIR, topical dexamethasone treatment before any neovessel formation had limited efficacy in preventing later neovascularization, while treatment after peak neovessel formation had a non-statistically significant trend to exacerbating disease. Optimally timed topical dexamethasone suppression of neovascularization in OIR was associated with increased retinal mitochondrial gene expression and decreased inflammatory marker expression, predominantly found in immune cells. Blocking mitochondrial ATP synthetase reversed the inhibitory effect of dexamethasone on neovascularization in OIR. This study provides new insights into topical steroid effects in retinal neovascularization and into mitochondrial function in phase II ROP, and suggests a simple clinical approach to prevent severe ROP.

Mitochondrial control of hypoxia-induced pathological retinal angiogenesis - Hitomi Yagi; Myriam Boeck; Shen Nian; Katherine Neilsen; Chaomei Wang; Jeff Lee; Yan Zeng; Matthew Grumbine; Ian R. Sweet; Taku Kasai; Kazuno Negishi; Sasha A. Singh; et al. (Angiogenesis, 2024)
Objective Pathological retinal neovascularization is vision-threatening. In mouse oxygen-induced retinopathy (OIR) we sought to define mitochondrial respiration changes longitudinally during hyperoxia-induced vessel loss and hypoxia-induced neovascularization, and to test interventions addressing those changes to prevent neovascularization. Methods OIR was induced in C57BL/6J mice and retinal vasculature was examined at maximum neovessel formation. We assessed total proteome changes and the ratio of mitochondrial to nuclear DNA copy numbers (mtDNA/nDNA) of OIR vs. control retinas, and mitochondrial oxygen consumption rates (OCR) in ex vivo OIR vs. control retinas (BaroFuse). Pyruvate vs. vehicle control was supplemented to OIR mice either prior to or during neovessel formation. Results In OIR vs. control retinas, global proteomics showed decreased retinal mitochondrial respiration at peak neovascularization. OCR and mtDNA/nDNA were also decreased at peak neovascularization suggesting impaired mitochondrial respiration. In vivo pyruvate administration during but not prior to neovessel formation (in line with mitochondrial activity time course) suppressed NV. Conclusions Mitochondrial energetics were suppressed during retinal NV in OIR. Appropriately timed supplementation of pyruvate may be a novel approach in neovascular retinal diseases.

Marine heatwaves alter competition between the cultured macroalga Gracilariopsis lemaneiformis and the harmful bloom alga Skeletonema costatum - Lin Gao; Yonglong Xiong; Fei-Xue Fu; David A. Hutchins; Kunshan Gao; Guang Gao (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Manure sterilization reduced antibiotic resistance genes in lettuce endophytes - Qingyuan Dou; Ying Liang; Yuhao Fu; Zhi Mei; Leilei Xiang; Rehan Ahmad; Wei Zhao; Xin Jiang; Syed A. Hashsham; James M. Tiedje; Fang Wang (Journal of Cleaner Production, 2024)

Can ozone mass transfer in water treatment be enhanced through independent pressurized ozonation? - Yixin Yan; Ioannis A. Fotidis; Dafang Fu; Rajendra Prasad Singh (Journal of Environmental Chemical Engineering, 2024)

Novel findings on the mitochondria in ciliates, with description of mitochondrial genomes of six representatives - Tengteng Zhang; Jinyu Fu; Chao Li; Ruitao Gong; Khaled A. S. Al-Rasheid; Naomi A. Stover; Chen Shao; Ting Cheng (Marine Life Science & Technology, 2024)
Determining and comparing mitochondrial genomes (mitogenomes) are essential for assessing the diversity and evolution of mitochondria. Ciliates are ancient and diverse unicellular eukaryotes, and thus are ideal models for elucidating the early evolution of mitochondria. Here, we report on six new mitogenomes of spirotrichs, a dominant ciliate group, and perform comparative analyses on 12 representative species. We show that: (1) the mitogenomes of spirotrichs are linear structures with high A+T contents (61.12–81.16%), bidirectional transcription, and extensive synteny (except for the nad5 , ccmf and cob genes in Euplotia); (2) the non-split of NADH dehydrogenase subunit 2 gene ( nad2 ) is a plesiomorphy of ciliates, whereas it has evolved into a split gene in Spirotrichea (apart from Euplotes taxa), Oligohymenophorea, and Armophorea; (3) the number of small subunit ribosomal proteins (rps) encoded in mitogenomes increases in the later branching classes of ciliates, whereas rps8 shows a loss trend during the evolution of Euplotes taxa; (4) the mitogenomes of spirotrichs exhibit A/T codon bias at the third position, and the codon bias is mainly due to DNA mutation in oligotrichs, hypotrichs and Diophrys appendiculata ; (5) the phylogenetic position of D. appendiculata is unstable and controversial based on both phylogenetic analyses and mitogenome evidence. In summary, we investigated the mitogenome diversity of spirotrichs and broadened our understanding of the evolution of mitochondria in ciliates.

A robust self-regenerating graphene-based adsorbent for pharmaceutical removal in various water environments - Han Fu; Laura Gutierrez; Sofia Shewfelt; Yingqian Xiong; Kimberly A. Gray (Water Research, 2024)

Unveiling the distinctive traits of functional rye centromeres: minisatellites, retrotransposons, and R-loop formation - Chang Liu; Shulan Fu; Congyang Yi; Yang Liu; Yuhong Huang; Xianrui Guo; Kaibiao Zhang; Qian Liu; James A. Birchler; Fangpu Han (Science China Life Sciences, 2024)

Warming alters the network of physiological traits and their contribution to plant abundance - Guixiang Yuan; Eti E. Levi; Thomas A. Davidson; Torben L. Lauridsen; Martin Søndergaard; Zhenzhi Yang; Aiping Wu; Te Cao; Youzhi Li; Hui Fu; Erik Jeppesen (Science of The Total Environment, 2024)

Bourgeoning Impacts of the Coastal Megacities and Potential Ecological Risks of Leachable Heavy Metals in Fine-sediments Fractions along the Egyptian Red Sea Shores - Ahmed Salah-Tantawy; Aldoushy Mahdy; Mahmoud A. Dar; Ching-Fu Lee; Abdelbaset M. A. Abdelreheem (Water, Air, & Soil Pollution, 2024)

PROSAC as a selection tool for SO-PLS regression: A strategy for multi-block data fusion - Jose A. Diaz-Olivares; Ryad Bendoula; Wouter Saeys; Maxime Ryckewaert; Ines Adriaens; Xinyue Fu; Matti Pastell; Jean-Michel Roger; Ben Aernouts (Analytica Chimica Acta, 2024)

Differential accumulation patterns of flavor compounds in Longjing 43 and Qunti fresh leaves and during processing responding to altitude changes - A. Bassiony; Qunhua Peng; Susanne Baldermann; Shan Feng; Kangni Yang; Yongcheng Zhang; Jianyu Fu; Haipeng Lv; Zhi Lin; Jiang Shi (Food Research International, 2024)

Soil autotrophic-to-heterotrophic-respiration ratio and its controlling factors across several terrestrial biomes: A global synthesis - Chuan Jin; Jinshi Jian; Charles P.-A. Bourque; Tianshan Zha; Licong Dai; Yue Yang; Ruiyu Fu; Qiaoyan Chen; Peng Liu; Xinhao Li; Zifan Guo; Zhongmin Hu (CATENA, 2024)

Machine learning approaches delimit cryptic taxa in a previously intractable species complex - Haley L.A. Heine; Shahan Derkarabetian; Rina Morisawa; Phoebe A. Fu; Nathaniel H.W. Moyes; Sarah L. Boyer (Molecular Phylogenetics and Evolution, 2024)

Silkworm pupae globulin promotes Cordyceps militaris fermentation: Regulation of metabolic pathways enhances cordycepin synthesis and extends the synthesis phase - Yi-Tong Li; Hao-Tian Yao; Ze-Lai Huang; Lu-Chan Gong; Richard A. Herman; Fu-An Wu; Jun Wang (Food Bioscience, 2024)

Reproducible responses of geochemical and microbial successional patterns in the subsurface to carbon source amendment - Jonathan P. Michael; Andrew D. Putt; Yunfeng Yang; Benjamin G. Adams; Kathryn R. McBride; Yupeng Fan; Kenneth A. Lowe; Daliang Ning; Sindhu Jagadamma; Ji Won Moon; Dawn M. Klingeman; Ping Zhang; et al. (Water Research, 2024)

Pilot-scale membrane-covered composting of food waste: Initial moisture, mature compost addition, aeration time and rate - Fei Wang; Ting Pan; Dafang Fu; Ioannis A. Fotidis; Christina Moulogianni; Yixin Yan; Rajendra Prasad Singh (Science of The Total Environment, 2024)

‘Drivin' with your eyes closed’: Results from an international, blinded simulation experiment to evaluate spatial stock assessments - Daniel R. Goethel; Aaron M. Berger; Simon D. Hoyle; Patrick D. Lynch; Caren Barceló; Jonathan Deroba; Nicholas D. Ducharme‐Barth; Alistair Dunn; Dan Fu; Francisco Izquierdo; Craig Marsh; Haikun Xu; et al. (Fish and Fisheries, 2024)
Spatial models enable understanding potential redistribution of marine resources associated with ecosystem drivers and climate change. Stock assessment platforms can incorporate spatial processes, but have not been widely implemented or simulation tested. To address this research gap, an international simulation experiment was organized. The study design was blinded to replicate uncertainty similar to a real‐world stock assessment process, and a data‐conditioned, high‐resolution operating model (OM) was used to emulate the spatial dynamics and data for Indian Ocean yellowfin tuna ( Thunnus albacares ). Six analyst groups developed both single‐region and spatial stock assessment models using an assessment platform of their choice, and then applied each model to the simulated data. Results indicated that across all spatial structures and platforms, assessments were able to adequately recreate the population trends from the OM. Additionally, spatial models were able to estimate regional population trends that generally reflected the true dynamics from the OM, particularly for the regions with higher biomass and fishing pressure. However, a consistent population biomass scaling pattern emerged, where spatial models estimated higher population scale than single‐region models within a given assessment platform. Balancing parsimony and complexity trade‐offs were difficult, but adequate complexity in spatial parametrizations (e.g., allowing time‐ and age‐variation in movement and appropriate tag mixing periods) was critical to model performance. We recommend expanded use of high‐resolution OMs and blinded studies, given their ability to portray realistic performance of assessment models. Moreover, increased support for international simulation experiments is warranted to facilitate dissemination of methodology across organizations.

Exploring the impact of ESG ratings on enterprises' green technology innovation - Mingtao Zhao; Xuebao Fu; Guobing Fang; Lianbiao Cui; Abdelmohsen A. Nassani (Environment, Development and Sustainability, 2024)

Proprioceptive and olfactory deficits in individuals with Parkinson disease and mild cognitive impairment - Kuan-yi Li; Kristen A. Pickett; Hsuan-wei Fu; Rou-shayn Chen (Acta Neurologica Belgica, 2024)
Background Individuals with neurodegenerative diseases such as Parkinson disease (PD) and Alzheimer’s (AD) disease often present with perceptual impairments at an early clinical stage. Therefore, early identification and quantification of these impairments could facilitate diagnosis and early intervention. Objectives This study aimed to compare proprioceptive and olfactory sensitivities in individuals diagnosed with PD and mild cognitive impairment (MCI). Methods Proprioception in the forearm and olfactory function were measured in neurotypical older adults, individuals with PD, and individuals with MCI. Position and passive motion senses were assessed using a passive motion apparatus. The traditional Chinese version of the University of Pennsylvania smell identification test (UPSIT-TC) and the smell threshold test (STT) were used to identify and discriminate smell, respectively. Results Position sense threshold between the groups differed significantly ( p p p = 0.004) groups showing significantly higher than the control group. The control group had significantly higher mean UPSIT-TC scores than the PD ( p p = 0.006) groups. The control group had a significantly lower mean STT threshold than the PD and MCI groups ( p p = 0.008, respectively). UPSIT-TC scores significantly correlated with disease progression in PD (r = − 0.50, p = 0.008) and MCI (r = 0.44, p = 0.04). Conclusions Proprioceptive and olfactory sensitivities were reduced in individuals with PD and MCI, and these deficits were related to disease severity. These findings support previous findings indicating that perceptual loss may be a potential biomarker for diagnosing and monitoring disease progression in individuals with neurodegenerative diseases.

Nanoparticles synergy: Enhancing wheat (Triticum aestivum L.) cadmium tolerance with iron oxide and selenium - Fu Chen; Feifei Jiang; Mohammad K. Okla; Zahid Khorshid Abbas; Salem Mesfir Al-Qahtani; Nadi Awad Al-Harbi; Mostafa A. Abdel-Maksoud; Leobardo Manuel Gómez-Oliván (Science of The Total Environment, 2024)

From germline genome to highly fragmented somatic genome: genome-wide DNA rearrangement during the sexual process in ciliated protists - Liping Lyu; Xue Zhang; Yunyi Gao; Tengteng Zhang; Jinyu Fu; Naomi A. Stover; Feng Gao (Marine Life Science & Technology, 2024)
Genomes are incredibly dynamic within diverse eukaryotes and programmed genome rearrangements (PGR) play important roles in generating genomic diversity. However, genomes and chromosomes in metazoans are usually large in size which prevents our understanding of the origin and evolution of PGR. To expand our knowledge of genomic diversity and the evolutionary origin of complex genome rearrangements, we focus on ciliated protists (ciliates). Ciliates are single-celled eukaryotes with highly fragmented somatic chromosomes and massively scrambled germline genomes. PGR in ciliates occurs extensively by removing massive amounts of repetitive and selfish DNA elements found in the silent germline genome during development of the somatic genome. We report the partial germline genomes of two spirotrich ciliate species, namely Strombidium cf. sulcatum and Halteria grandinella , along with the most compact and highly fragmented somatic genome for S. cf. sulcatum . We provide the first insights into the genome rearrangements of these two species and compare these features with those of other ciliates. Our analyses reveal: (1) DNA sequence loss through evolution and during PGR in S . cf. sulcatum has combined to produce the most compact and efficient nanochromosomes observed to date; (2) the compact, transcriptome-like somatic genome in both species results from extensive removal of a relatively large number of shorter germline-specific DNA sequences; (3) long chromosome breakage site motifs are duplicated and retained in the somatic genome, revealing a complex model of chromosome fragmentation in spirotrichs; (4) gene scrambling and alternative processing are found throughout the core spirotrichs, offering unique opportunities to increase genetic diversity and regulation in this group.

Seasonal variation and dissolved organic matter influence on the distribution, transformation, and environmental risk of pharmaceuticals and personal care products in coastal zone: A case study of Tianjin, China - Wenrui Yao; Yulin Qi; Yufu Han; Jinfeng Ge; Yuanyuan Dong; Jianwen Wang; Yuanbi Yi; Dietrich A. Volmer; Si-Liang Li; Pingqing Fu (Water Research, 2024)

Deciphering the ore-forming process of Sb-W deposits through scheelite and stibnite trace element geochemistry - Tianxing Wang; Shanling Fu; Neal A. Sullivan; Jiangbo Lan; Luming Wei (Journal of Geochemical Exploration, 2024)

Iron oxyhydroxide catalyzes production of artificial humic substances from waste biomass - Xinyu Chen; Bo Yang; Hao Zhou; Patrycja Boguta; Xinying Fu; Andrei Ivanets; Alexander A. Ratko; Tatyana Kouznetsova; Yongqi Liu; Xiaoyan He; Dongmei Zhao; Xintai Su (Journal of Environmental Management, 2024)

Characteristics of bacterial community and extracellular enzymes in response to atrazine application in black soil - Tiancong Gao; Haixia Tian; Leilei Xiang; Ziqi Wang; Yuhao Fu; Jing Shi; Xin Wen; Xin Jiang; Wenxiang He; Syed A. Hashsham; Fang Wang (Environmental Pollution, 2024)

Exploring the co-operativity of secretory structures for defense and pollination in flowering plants - Jinjin Li; Hao Hu; Hansen Fu; Jie Li; Tuo Zeng; Jiawen Li; Manqun Wang; Maarten A. Jongsma; Caiyun Wang (Planta, 2024)

Genetics and metabolic responses of Artemisia annua L to the lake of phosphorus under the sparingly soluble phosphorus fertilizer: evidence from transcriptomics analysis - Lingyun Wan; Juan Huo; Qiulan Huang; Xiaowen Ji; Lisha Song; Zhanjiang Zhang; Limei Pan; Jine Fu; Mohamed A. Abd Elhamid; Salma A. Soaud; Rania M. Y. Heakel; Jihai Gao; et al. (Functional & Integrative Genomics, 2024)

Polyaniline-metal oxide coatings for biocidal applications: Mechanisms of activation and deactivation - Han Fu; Sofia Shewfelt; Lena D. Sylvan; Jean-François Gaillard; Kimberly A. Gray (Chemosphere, 2024)

FinTech and sustainable financing for low carbon energy transitions: A biodiversity and natural resource perspective in BRICS economies - Li Zeng; Wing-Keung Wong; Hu Fu; Haitham A. Mahmoud; Phan The Cong; Dinh Thi Thanh Thuy; Pham Xuan Bach (Resources Policy, 2024)

Functions and values of sulfated polysaccharides from seaweed - D. P. Nagahawatta; N. M. Liyanage; Thilina U. Jayawardena; Fengqi Yang; H. H. A. C. K. Jayawardena; M. J. M. S. Kurera; Fahe Wang; Xiaoting Fu; You-Jin Jeon (Algae, 2023)
Sulfated polysaccharides (SPs) isolated from seaweed have emerged as remarkable bioactive compounds with a wide spectrum of biological activities and have substantial value in the scientific and industrial domains. The current study explores the diverse biological activities of SPs and their relationship with their structures. This aids in an in-depth examination of the multifaceted biological activities of SPs, including anticoagulant, anti-inflammatory, antiviral, antioxidant, and immunomodulatory properties, which underpin their potential health benefits. Furthermore, the current study explores the complicated properties of SPs, with their extraction methodologies and techniques for precise characterization. Elucidation of the commercial significance of SPs derived from brown, red, and green seaweed by highlighting their potential applications has emphasized their importance in human well-being. Further, this review emphasizes the challenges needed to overcome research and industrial innovations for SPs. Collaboration among researchers, industry stakeholders, and regulatory authorities can overcome these challenges and elevate the potential of SPs to revolutionize industries such as pharmaceuticals, cosmeceuticals, food, and biotechnology.

Correction to: Clinical Significance and Influencing Factors of Microvascular Tissue Reperfusion After Macrovascular Recanalization - Xuesong Bai; Fan Yu; Qiuyue Tian; Wei Li; Arman Sha; Wenbo Cao; Yao Feng; Bin Yang; Yanfei Chen; Peng Gao; Yabing Wang; Jian Chen; et al. (Translational Stroke Research, 2023)

Tree species diversity increases soil microbial carbon use efficiency in a subtropical forest - Pengpeng Duan; Ruitong Fu; Andrew T. Nottingham; Luiz A. Domeignoz‐Horta; Xinyi Yang; Hu Du; Kelin Wang; Dejun Li (Global Change Biology, 2023)
Plant communities strongly influence soil microbial communities and, in turn, soil carbon (C) cycling. Microbial carbon use efficiency (CUE) is an important parameter for predicting soil C accumulation, yet how plant and soil microbial community traits influence microbial CUE remains poorly understood. Here, we determined how soil microbial CUE is influenced by plant and soil microbial community traits, by studying a natural gradient of plant species diversity in a subtropical forest. Our results showed that microbial CUE increased with increasing tree species diversity, suggesting a correlation between plant community traits and soil C storage. The specific soil properties that explained the greatest variation in microbial CUE were associated with microbial communities (biomass, enzyme activities and the ratio of oligotrophic to copiotrophic taxa); there were weaker correlations with plant‐input properties, soil chemistry and soil organic C quality and its mineral protection. Overall, high microbial CUE was associated with soil properties correlated with increased tree species diversity: higher substrate availability (simple SOM chemical structures and weak mineral organic associations) and high microbial growth rates despite increased community dominance by oligotrophic strategists. Our results point to a mechanism by which increased tree species diversity may increase the forest C sink by affecting carbon use with the soil microbial community.

Comparative analysis of the cardiac structure and transcriptome of scallop and snail, perspectives on heart chamber evolution - Meina Lu; Rabia Hayat; Xuejiao Zhang; Yaqi Jiao; Jianyun Huang; Yifan Huangfu; Mingcan Jiang; Jieyi Fu; Qingqiu Jiang; Yaojia Gu; Shi Wang; Alexander A. Akerberg; et al. (Marine Life Science & Technology, 2023)

Diverging fates of cadmium and glyphosate during pasta cooking - Sheryl A. Tittlemier; Lianna Bestvater; Jason Chan; Valentina Timofeiev; Anja Richter; Kun Wang; Yuefeng Ruan; Marta Izydorczyk; Bin Xiao Fu (Food Additives & Contaminants: Part A, 2023)

Water content imaging during capillary rise within a rammed earth structure - A. Ghorbani; T. Chitimbo; A. Revil; N. Prime; K. Zhang; T. Fu; O. Plé (Engineering Geology, 2023)

Magnetic biochar/quaternary phosphonium salt reduced antibiotic resistome and pathobiome on pakchoi leaves - Zhi Mei; Yuhao Fu; Fang Wang; Leilei Xiang; Fang Hu; Jean Damascene Harindintwali; Mingyi Wang; Marko Virta; Syed A. Hashsham; Xin Jiang; James M. Tiedje (Journal of Hazardous Materials, 2023)

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

A top-down deep learning model for predicting spatiotemporal dynamics of groundwater recharge - Xin Huang; Lei Gao; Nan Zhang; Russell S. Crosbie; Long Ye; Jian Liu; Zhaoxia Guo; Qinghua Meng; Guobin Fu; Brett A. Bryan (Environmental Modelling & Software, 2023)

Generation of droplets of shear-thinning non-Newtonian fluids in T-junction parallelized microchannels - Zhongdong Wang; Xingyu Xiang; Hongwei Zhu; Yanpeng Dong; Chunying Zhu; Youguang Ma; Bing Sun; Stanislav A. Patlazhan; Taotao Fu (Chemical Engineering Journal, 2023)

Constitutively Synergistic Multiagent Drug Formulations Targeting MERTK, FLT3, and BCL-2 for Treatment of AML - James M. Kelvin; Juhi Jain; Aashis Thapa; Min Qui; Lacey A. Birnbaum; Samuel G. Moore; Henry Zecca; Ryan J. Summers; Jeffrey M. Switchenko; Emma Costanza; Biaggio Uricoli; Xiaodong Wang; et al. (Pharmaceutical Research, 2023)

Effect of molecular structure on the adsorption behavior of sulfanilamide antibiotics on crumpled graphene balls - Han Fu; Kimberly A. Gray (Water Research, 2023)

Comprehensive magnetic analysis of the tephras in Middle-Late Pleistocene loess records of Serbia, and implications for tephra identification, correlation and loess chronology - Namier Namier; Qingzhen Hao; Xinbo Gao; Yu Fu; Slobodan B. Marković; Ulrich Hambach; Daniel Veres; Joseph A. Mason; Yang Song; Chenglong Deng; Milivoj B. Gavrilov; Rastko Marković; et al. (Quaternary Science Reviews, 2023)

Urinary Amino-PAHs in relation to diesel engine emissions and urinary mutagenicity - Junfeng (Jim) Zhang; Yuxin Zheng; Roel Vermeulen; Xing (Lucy) Liu; Yufei Dai; Wei Hu; Linchen He; Yan Lin; Dianzhi Ren; Huawei Duan; Yong Niu; Jun Xu; et al. (International Journal of Hygiene and Environmental Health, 2023)

Simulated upwelling and marine heatwave events promote similar growth rates but differential domoic acid toxicity in Pseudo-nitzschia australis - Kyla J. Kelly; Amjad Mansour; Chen Liang; Andrew M. Kim; Lily A. Mancini; Matthew J. Bertin; Bethany D. Jenkins; David A. Hutchins; Fei-Xue Fu (Harmful Algae, 2023)

Clinical Significance and Influencing Factors of Microvascular Tissue Reperfusion After Macrovascular Recanalization - Xuesong Bai; Fan Yu; Qiuyue Tian; Wei Li; Araman Sha; Wenbo Cao; Yao Feng; Bin Yang; Yanfei Chen; Peng Gao; Yabing Wang; Jian Chen; et al. (Translational Stroke Research, 2023)

Light-driven micromotor swarm induced in-situ polymerization and synergistic photothermal therapy - Zeqi Li; Shaoming Fu; Huaan Li; Bin Chen; Dazhi Xie; Dongmei Fu; Ye Feng; Chao Gao; Suyi Liu; Daniela A. Wilson; Yingfeng Tu; Fei Peng (Chemical Engineering Journal, 2023)

Simultaneous removal of pharmaceuticals and heavy metals from aqueous phase via adsorptive strategy: A critical review - Mudi Zhai; Bomin Fu; Yuhui Zhai; Weijie Wang; Amy Maroney; Arturo A. Keller; Hongtao Wang; Jean-Marc Chovelon (Water Research, 2023)

Linking rapid eruption of the Linzizong volcanic rocks and Early Eocene Climatic Optimum (EECO): Constraints from the Pana Formation in the Linzhou and Pangduo basins, southern Tibet - Shao-Hua Zhang; Wei-Qiang Ji; Hou-Bin Chen; Linda A. Kirstein; Fu-Yuan Wu (Lithos, 2023)

Gastrointestinal digestion fates of lipids based on pH-stat and Caco-2 cells models: Superior bioavailability of triglyceride monomer derived from silkworm pupae oil - Cheng-Hai Yan; Xiao-Meng Xun; Richard A. Herman; Yu-Fan Zhan; Lu-Chan Gong; Fu-An Wu; Jun Wang (Food Bioscience, 2023)

RNA sequencing in Artemisia annua L explored the genetic and metabolic responses to hardly soluble aluminum phosphate treatment - Lingyun Wan; Qiulan Huang; Xiaowen Ji; Lisha Song; Zhanjiang Zhang; Limei Pan; Jine Fu; Rania G. Elbaiomy; Ahmed S. Eldomiaty; Shabir A. Rather; Mohamed M. A. Elashtokhy; Jihai Gao; et al. (Functional & Integrative Genomics, 2023)

Creating anti-viral high-touch surfaces using photocatalytic transparent films - Han Fu; Vered Yaniv; Yifaat Betzalel; Hadas Mamane; Kimberly A. Gray (Chemosphere, 2023)

Plant and fungal species interactions differ between aboveground and belowground habitats in mountain forests of eastern China - Teng Yang; Leho Tedersoo; Pamela S. Soltis; Douglas E. Soltis; Miao Sun; Yuying Ma; Yingying Ni; Xu Liu; Xiao Fu; Yu Shi; Han-Yang Lin; Yun-Peng Zhao; et al. (Science China Life Sciences, 2023)

The mobility and fate of Cr during aging of ferrihydrite and ferrihydrite organominerals - Yao Zhao; Alba Otero-Fariña; Ke-Qing Xiao; Oliver W. Moore; Steven A. Banwart; Fu-Jun Ma; Qing-Bao Gu; Caroline L. Peacock (Geochimica et Cosmochimica Acta, 2023)

Comparative analysis of single-cell genome sequencing techniques toward the characterization of germline and somatic genomes in ciliated protists - Liping Lyu; Usman Asghar; Jinyu Fu; Yunyi Gao; Xue Zhang; Saleh A. Al-Farraj; Zigui Chen; Feng Gao (European Journal of Protistology, 2023)

Corrigendum to “Validation of the improved GOES-16 aerosol optical depth product over North America” [Atmos. Environ. 298 (2023) 119642] - Disong Fu; Christian A. Gueymard; Xiangao Xia (Atmospheric Environment, 2023)

Validation of the improved GOES-16 aerosol optical depth product over North America - Disong Fu; Christian A. Gueymard; Xiangao Xia (Atmospheric Environment, 2023)

H﻿ow on Earth did that get there? Natural and human vectors of aquatic macrophyte global distribution - Tatiana Lobato‑de Magalhães; Kevin Murphy; Andrey Efremov; Thomas A. Davidson; Eugenio Molina-Navarro; Kevin A. Wood; Julissa Tapia-Grimaldo; Deborah Hofstra; Hui Fu; Ileana Ortegón-Aznar (Hydrobiologia, 2023)

Trends and variability of rainfall characteristics influencing annual streamflow: A case study of southeast Australia - Guobin Fu; Francis H.S. Chiew; David A. Post (International Journal of Climatology, 2023)
The trend and variability in rainfall characteristics that influence annual streamflow of southeast Australia is assessed using two methods, non‐parametric Kendall test and linear slope, and two gridded daily rainfall datasets (SILO and AWAP) and 1,196 station rainfall data for 1971–2021 period. The rainfall anomaly before, during and after the Millennium Drought (1997–2009) is compared to quantify the variability. The results show: (a) a declining rainfall trend is detected as the recent dry decades were preceded by wet decades. The declining trend largely occurs from autumn through to spring with the largest trend in August to October followed by April and May; (b) the trend is more significant for number of rainfall days and for multi‐day rainfall totals (and more so for longer accumulations) than for annual rainfall; (c) the very high extreme rainfall shows a small increasing trend in summer and mixed signal in the other seasons; (d) the streamflow in the post drought period is lower than the long‐term mean, despite the mean annual rainfall being slightly higher. This can be partly explained by the rainfall‐runoff relationship of catchments not having fully recovered from the prolonged drought and partly by changes in rainfall characteristics, like the wet spell length and multi‐day rainfall, influencing annual streamflow; (e) The general conclusions for analyses with different sources of daily rainfall data are the same. However, some differences do exist, with SILO gridded rainfall and station data having larger areas with statistically significant trend than the AWAP gridded rainfall, as well as larger declining trends in the high elevation areas. The general conclusions of this study are drawn from an Australia case study but could have implications for other regions to investigate the attributions of rainfall characteristics other than annual rainfall to the non‐stationary rainfall‐streamflow relationship.

Active species and fundamentals of their creation in Co-containing catalysts for efficient propane dehydrogenation to propylene - Yuming Li; Qiyang Zhang; Shuting Fu; Vita A. Kondratenko; Tatiana Otroshchenko; Stephan Bartling; Yaoyuan Zhang; Anna Zanina; Yajun Wang; Guoqing Cui; Mingxia Zhou; Zhen Zhao; et al. (Chemical Engineering Journal, 2023)

Improving aerosol optical depth retrievals from Himawari-8 with ensemble learning enhancement: Validation over Asia - Disong Fu; Christian A. Gueymard; Dazhi Yang; Yu Zheng; Xiangao Xia; Jianchun Bian (Atmospheric Research, 2023)

Periostin regulation and cartilage degradation early after anterior cruciate ligament reconstruction - Cale A. Jacobs; Laura E. Keller; Sheng Zhang; Qin Fu; Emily R. Hunt; Austin V. Stone; Caitlin E. W. Conley; Christian Lattermann; Lisa A. Fortier (Inflammation Research, 2023)

Measurements of cerebral microvascular blood flow, oxygenation, and morphology in a mouse model of whole-brain irradiation-induced cognitive impairment by two-photon microscopy and optical coherence tomography: evidence for microvascular injury in the cerebral white matter - Baoqiang Li; Andriy Yabluchanskiy; Stefano Tarantini; Srinivasa Rao Allu; Ikbal Şencan-Eğilmez; Ji Leng; Mohammed Ali H. Alfadhel; Jason E. Porter; Buyin Fu; Chongzhao Ran; Sefik Evren Erdener; David A. Boas; et al. (GeroScience, 2023)

Natural bioactive compounds-doxorubicin combinations targeting topoisomerase II-alpha: Anticancer efficacy and safety - Ahmed Elfadadny; Rokaia F. Ragab; Rania Hamada; Soad K. Al Jaouni; Junjiang Fu; Shaker A. Mousa; Ali H. El-Far (Toxicology and Applied Pharmacology, 2023)

Metal oxide encapsulated by 3D graphene oxide creates a nanocomposite with enhanced organic adsorption in aqueous solution - Han Fu; Haotian Cai; Kimberly A. Gray (Journal of Hazardous Materials, 2023)

Measurement of airborne nicotine, as a marker of secondhand smoke exposure, in homes with residents who smoke in 9 European countries - Elisabet Henderson; Luis A. Rodriguez Guerrero; Xavier Continente; Esteve Fernández; Olena Tigova; Nuria Cortés-Francisco; Sean Semple; Ruaraidh Dobson; Anna Tzortzi; Vergina K. Vyzikidou; Giuseppe Gorini; Gergana Geshanova; et al. (Environmental Research, 2023)

The tempo of back-arc basin evolution: Insights from the early Paleozoic Proto-Tethyan North Qilian orogenic belt, northeastern Tibet - Dong Fu; Bo Huang; Simon A. Wilde; Tim E. Johnson; Ali Polat; Brian F. Windley; Zhaochu Hu; Zhipeng Zhou; Timothy M. Kusky (Earth and Planetary Science Letters, 2023)

Factors influencing the transfer and abundance of antibiotic resistance genes in livestock environments in China - Z. F. Wang; H. Yun; S. Li; J. Ji; A. Khan; X. L. Fu; P. Zhang; X. K. Li (International Journal of Environmental Science and Technology, 2023)

Regulation of autophagy of the heart in ischemia and reperfusion - Sergey V. Popov; Alexander V. Mukhomedzyanov; Nikita S. Voronkov; Ivan A. Derkachev; Alla A. Boshchenko; Feng Fu; Galina Z. Sufianova; Maria S. Khlestkina; Leonid N. Maslov (Apoptosis, 2023)

Radiation‐constrained boundaries cause nonuniform responses of the carbon uptake phenology to climatic warming in the Northern Hemisphere - Adrià Descals; Aleixandre Verger; Gaofei Yin; Iolanda Filella; Yongshuo H. Fu; Shilong Piao; Ivan A. Janssens; Josep Peñuelas (Global Change Biology, 2023)
Climatic warming has lengthened the photosynthetically active season in recent decades, thus affecting the functioning and biogeochemistry of ecosystems, the global carbon cycle and climate. Temperature response of carbon uptake phenology varies spatially and temporally, even within species, and daily total intensity of radiation may play a role. We empirically modelled the thresholds of temperature and radiation under which daily carbon uptake is constrained in the temperate and cold regions of the Northern Hemisphere, which include temperate forests, boreal forests, alpine and tundra biomes. The two‐dimensionality of the temperature‐radiation constraint was reduced to one single variable, θ , which represents the angle in a polar coordinate system for the temperature‐radiation observations during the start and end of the growing season. We found that radiation will constrain the trend towards longer growing seasons with future warming but differently during the start and end of season and depending on the biome type and region. We revealed that radiation is a major factor limiting photosynthetic activity that constrains the phenology response to temperature during the end‐of‐season. In contrast, the start of the carbon uptake is overall highly sensitive to temperature but not constrained by radiation at the hemispheric scale. This study thus revealed that while at the end‐of‐season the phenology response to warming is constrained at the hemispheric scale, at the start‐of‐season the advance of spring onset may continue, even if it is at a slower pace.

Exposure to secondhand aerosol from electronic cigarettes at homes: A real-life study in four European countries - Beladenta Amalia; Marcela Fu; Olena Tigova; Montse Ballbè; Blanca Paniello-Castillo; Yolanda Castellano; Vergina K. Vyzikidou; Rachel O'Donnell; Ruaraidh Dobson; Alessandra Lugo; Chiara Veronese; Raúl Pérez-Ortuño; et al. (Science of The Total Environment, 2023)

Determination of soluble angiotensin-converting enzyme 2 in saliva samples and its association with nicotine - Samuel Bru; Adrián González-Marrón; Cristina Lidón-Moyano; Reyes Carballar; Joan Marc Martínez-Láinez; Hipólito Pérez-Martín; Marcela Fu; Raúl Pérez-Ortuño; Montse Ballbè; Jose A. Pascual; Esteve Fernández; Josep Clotet; et al. (Environmental Research, 2023)

Cre-mediated autoexcision of selectable marker genes in soybean, cotton, canola and maize transgenic plants - Xudong Ye; Zarir Vaghchhipawala; Edward J. Williams; Changlin Fu; Jinyuan Liu; Fengming Lu; Erin L. Hall; Shirley X. Guo; LaRee Frank; Larry A. Gilbertson (Plant Cell Reports, 2023)

Increasing clinician participation in tobacco cessation by an implementation science-based tobacco cessation champion program - Cary A. Presant; Kimlin Ashing; Sophia Yeung; Jonjon Macalintal; Brian Tiep; Argelia Sandoval; Susan Brown; Mary Cianfrocca; Loretta Erhunmwunsee; Dan Raz; Arya Amini; Ravi Salgia; et al. (Cancer Causes & Control, 2023)

The Role of Mitochondrial KATP Channels in the Infarct-Reducing Effect of Normobaric Hypoxia - L. N. Maslov; A. S. Sementsov; N. V. Naryzhnaya; I. A. Derkachev; F. Fu; S. V. Gusakova; A. Sarybaev (Bulletin of Experimental Biology and Medicine, 2022)

Doublets of the unicellular organism Euplotes vannus (Alveolata, Ciliophora, Euplotida): the morphogenetic patterns of the ciliary and nuclear apparatuses associated with cell division - Jinyu Fu; Yong Chi; Xiaoteng Lu; Feng Gao; Saleh A. Al-Farraj; Giulio Petroni; Jiamei Jiang (Marine Life Science & Technology, 2022)

Ecophysiological and genomic analyses of a representative isolate of highly abundant Bacillus cereus strains in contaminated subsurface sediments - Jennifer L. Goff; Elizabeth G. Szink; Michael P. Thorgersen; Andrew D. Putt; Yupeng Fan; Lauren M. Lui; Torben N. Nielsen; Kristopher A. Hunt; Jonathan P. Michael; Yajiao Wang; Daliang Ning; Ying Fu; et al. (Environmental Microbiology, 2022)
Bacillus cereus strain CPT56D‐587‐MTF (CPTF) was isolated from the highly contaminated Oak Ridge Reservation (ORR) subsurface. This site is contaminated with high levels of nitric acid and multiple heavy metals. Amplicon sequencing of the 16S rRNA genes (V4 region) in sediment from this area revealed an amplicon sequence variant (ASV) with 100% identity to the CPTF 16S rRNA sequence. Notably, this CPTF‐matching ASV had the highest relative abundance in this community survey, with a median relative abundance of 3.77% and comprised 20%–40% of reads in some samples. Pangenomic analysis revealed that strain CPTF has expanded genomic content compared to other B. cereus species—largely due to plasmid acquisition and expansion of transposable elements. This suggests that these features are important for rapid adaptation to native environmental stressors. We connected genotype to phenotype in the context of the unique geochemistry of the site. These analyses revealed that certain genes (e.g. nitrate reductase, heavy metal efflux pumps) that allow this strain to successfully occupy the geochemically heterogenous microniches of its native site are characteristic of the B. cereus species while others such as acid tolerance are mobile genetic element associated and are generally unique to strain CPTF.

Temperature variability interacts with mean temperature to influence the predictability of microbial phenotypes - Fei‐Xue Fu; Bernhard Tschitschko; David A. Hutchins; Michaela E. Larsson; Kirralee G. Baker; Allison McInnes; Tim Kahlke; Arjun Verma; Shauna A. Murray; Martina A. Doblin (Global Change Biology, 2022)
Despite their relatively high thermal optima ( T opt ), tropical taxa may be particularly vulnerable to a rising baseline and increased temperature variation because they live in relatively stable temperatures closer to their T opt . We examined how microbial eukaryotes with differing thermal histories responded to temperature fluctuations of different amplitudes (0 control, ±2, ±4°C) around mean temperatures below or above their T opt . Cosmopolitan dinoflagellates were selected based on their distinct thermal traits and included two species of the same genus (tropical and temperate Coolia spp.), and two strains of the same species maintained at different temperatures for >500 generations (tropical Amphidinium massartii control temperature and high temperature, CT and HT, respectively). There was a universal decline in population growth rate under temperature fluctuations, but strains with narrower thermal niche breadth (temperate Coolia and HT) showed ~10% greater reduction in growth. At suboptimal mean temperatures, cells in the cool phase of the fluctuation stopped dividing, fixed less carbon (C) and had enlarged cell volumes that scaled positively with elemental C, N, and P and C:Chlorophyll‐ a . However, at a supra‐optimal mean temperature, fixed C was directed away from cell division and novel trait combinations developed, leading to greater phenotypic diversity. At the molecular level, heat‐shock proteins, and chaperones, in addition to transcripts involving genome rearrangements, were upregulated in CT and HT during the warm phase of the supra‐optimal fluctuation (30 ± 4°C), a stress response indicating protection. In contrast, the tropical Coolia species upregulated major energy pathways in the warm phase of its supra‐optimal fluctuation (25 ± 4°C), indicating a broadscale shift in metabolism. Our results demonstrate divergent effects between taxa and that temporal variability in environmental conditions interacts with changes in the thermal mean to mediate microbial responses to global change, with implications for biogeochemical cycling.

Widespread refertilization of cratonic lithospheric mantle related to circum-craton plate subduction: evidence from peridotite xenoliths from the central North China Craton - Yao Xu; Hong-Fu Zhang; A-Bing Lin (Contributions to Mineralogy and Petrology, 2022)

Long-lived dacitic magmatic systems and recharge dynamics in the Jemez Mountains volcanic field, western USA - Jie Wu; Michael C. Rowe; Shane J. Cronin; John A. Wolff; Bin Fu (Contributions to Mineralogy and Petrology, 2022)
We examine the connected history of dacite-dominant volcanic rocks of the Tschicoma Formation, erupted between 5.5 and 2 Ma from the Jemez Mountains volcanic field, western USA. Zircon samples from two separate eruptions have continuous SHRIMP U–Pb age spectra spanning 0.84–1.08 Myr duration (3.12–3.96 Ma and 3.50–4.58 Ma, respectively), following an episode of zircon crystallization 0.28–0.50 Myr earlier (at 4.46 Ma and 4.86 Ma, respectively). Zircon chemical variations, as well as ubiquitous resorption textures that commonly show large core-rim age differences (up to 720–740 kyr), suggest that they grew in separate melt lenses. Zircons were likely stored at near-solidus or even sub-solidus conditions after crystallization, but may have been reactivated in response to at least four major magma recharge events every 300–400 kyr and smaller events in between. A cycle of zircon dissolution (from heating), recrystallization (during cooling), and storage repeated in different locations in the Tschicoma mush system throughout its lifespan; each recharge-induced heating stage may last for several hundred to more than a thousand years based on calculations of zircon dissolution. We envisage the melt lenses to be distributed in a crystal mush zone, coalescing into a single magma batch as magma recharge occurs shortly before eruption. Once active, increasing magma supply rates may trigger large-scale partial melting of the pre-existing mush and caldera-forming eruptions.

The changing extreme values of summer relative humidity in the Tarim Basin in northwestern China - Da Nian; Marianna Linz; Todd A. Mooring; Zuntao Fu (Climate Dynamics, 2022)

Diel variation in anti-predation behavior of a ground squirrel and relationships between vigilance and escape - Ling-Ying Shuai; Mei-Ting Liu; A.-Ping Zhu; Yuan-Yuan Cao; Fu-Shun Zhang (Behavioral Ecology and Sociobiology, 2022)

The Ocean's labile DOC supply chain - Mary Ann Moran; Frank X. Ferrer‐González; He Fu; Brent Nowinski; Malin Olofsson; McKenzie A. Powers; Jeremy E. Schreier; William F. Schroer; Christa B. Smith; Mario Uchimiya (Limnology and Oceanography, 2022)
Microbes of the surface ocean release, consume, and exchange labile metabolites at time scales of minutes to days. The details of this important step in the global carbon cycle remain poorly resolved, largely due to the methodological challenges of studying a diverse pool of metabolites that are produced and consumed nearly simultaneously. In this perspective, a new compilation of published data builds on previous studies to obtain an updated estimate of the fraction of marine net primary production that passes through the labile dissolved organic carbon (DOC) pool. In agreement with previous studies, our data mining and modeling approaches hypothesize that about half of ocean net primary production is processed through the labile DOC pool. The fractional contributions from three major sources are estimated at 0.4 for living phytoplankton, 0.4 for dead and dying phytoplankton, and 0.2 for heterotrophic microbes and mesoplankton.

Higher temperature sensitivity of flowering than leaf‐out alters the time between phenophases across temperate tree species - Xiaojun Geng; Yongshuo H. Fu; Shilong Piao; Fanghua Hao; Hans J. De Boeck; Xuan Zhang; Shouzhi Chen; Yahui Guo; Janet S. Prevéy; Yann Vitasse; Josep Peñuelas; Ivan A. Janssens; et al. (Global Ecology and Biogeography, 2022)
Aim The aims of this study were to evaluate the changes in the length of the time period between leaf‐out and flowering across temperate tree species, and associate these changes with potential physiological and environmental drivers to enhance mechanistic insight into these phenomena. Location Central Europe. Time period 1980–2016. Major taxa studied Six temperate woody species. Methods Statistical analyses were carried out based on long‐term ground observations of both spring leaf‐out and flowering across temperate tree species during 1980–2016, a period characterized by rapid warming. Results The temperature sensitivity of flowering (−5.4 ± 0.04 days/℃, mean ± SE ) was higher than that of leaf‐out (−4.6 ± 0.04 days/℃) across all species, regardless of whether leaf‐out occurred before or after flowering. This study postulates a hypothesis attributing the different temperature sensitivities to different thermal sensitivities, thermal requirements, and photoperiodic controls. Main conclusions The larger temperature sensitivity of flowering than leaf‐out resulted in an extended time period between flowering and leaf‐out in species that bloom before leafing out, but a shorter time period between these phenophases in species with the opposite strategy. We would like to emphasize the importance of changes in time period between different phenophases, and we recommend conducting experimental research to reveal the underlying mechanisms of plant phenology response to climate change, and to explore its potential ecological implications.

Demographic composition, not demographic diversity, predicts biomass and turnover across temperate and tropical forests - Jessica F. Needham; Daniel J. Johnson; Kristina J. Anderson‐Teixeira; Norman Bourg; Sarayudh Bunyavejchewin; Nathalie Butt; Min Cao; Dairon Cárdenas; Chia‐Hao Chang‐Yang; Yu‐Yun Chen; George Chuyong; Handanakere S. Dattaraja; et al. (Global Change Biology, 2022)
The growth and survival of individual trees determine the physical structure of a forest with important consequences for forest function. However, given the diversity of tree species and forest biomes, quantifying the multitude of demographic strategies within and across forests and the way that they translate into forest structure and function remains a significant challenge. Here, we quantify the demographic rates of 1961 tree species from temperate and tropical forests and evaluate how demographic diversity (DD) and demographic composition (DC) differ across forests, and how these differences in demography relate to species richness, aboveground biomass (AGB), and carbon residence time. We find wide variation in DD and DC across forest plots, patterns that are not explained by species richness or climate variables alone. There is no evidence that DD has an effect on either AGB or carbon residence time. Rather, the DC of forests, specifically the relative abundance of large statured species, predicted both biomass and carbon residence time. Our results demonstrate the distinct DCs of globally distributed forests, reflecting biogeography, recent history, and current plot conditions. Linking the DC of forests to resilience or vulnerability to climate change, will improve the precision and accuracy of predictions of future forest composition, structure, and function.

Cycle Length Evaluation in Persistent Atrial Fibrillation Using Kernel Density Estimation to Identify Transient and Stable Rapid Atrial Activity - Szabolcs Z. Nagy; Patrick Kasi; Valtino X. Afonso; Nathaniel Bird; Brian Pederson; Ian E. Mann; Steven Kim; Nicholas W. F. Linton; David C. Lefroy; Zachary I. Whinnett; Fu Siong Ng; Michael Koa-Wing; et al. (Cardiovascular Engineering and Technology, 2022)
Purpose Left atrial (LA) rapid AF activity has been shown to co-localise with areas of successful atrial fibrillation termination by catheter ablation. We describe a technique that identifies rapid and regular activity. Methods Eight-second AF electrograms were recorded from LA regions during ablation for psAF. Local activation was annotated manually on bipolar signals and where these were of poor quality, we inspected unipolar signals. Dominant cycle length (DCL) was calculated from annotation pairs representing a single activation interval, using a probability density function (PDF) with kernel density estimation. Cumulative annotation duration compared to total segment length defined electrogram quality. DCL results were compared to dominant frequency (DF) and averaging. Results In total 507 8 s AF segments were analysed from 7 patients. Spearman’s correlation coefficient was 0.758 between independent annotators ( P < 0.001), 0.837–0.94 between 8 s and ≥ 4 s segments ( P < 0.001), 0.541 between DCL and DF ( P < 0.001), and 0.79 between DCL and averaging ( P < 0.001). Poorer segment organization gave greater errors between DCL and DF. Conclusion DCL identifies rapid atrial activity that may represent psAF drivers. This study uses DCL as a tool to evaluate the dynamic, patient specific properties of psAF by identifying rapid and regular activity. If automated, this technique could rapidly identify areas for ablation in psAF.

Emission inventory processing of biomass burning from a global dataset for air quality modeling - Ernesto Pino-Cortés; Samuel Carrasco; Luis A. Díaz-Robles; Francisco Cubillos; Fidel Vallejo; Francisco Cereceda-Balic; Joshua S. Fu (Air Quality, Atmosphere & Health, 2022)

Low occurrence of multi‐antimicrobial and heavy metal resistance in Salmonella enterica from wild birds in the United States - Yezhi Fu; Nkuchia M. M'ikanatha; Chris A. Whitehouse; Heather Tate; Andrea Ottesen; Jeffrey M. Lorch; David S. Blehert; Brenda Berlowski‐Zier; Edward G. Dudley (Environmental Microbiology, 2022)
Summary Wild birds are common reservoirs of Salmonella enterica . Wild birds carrying resistant S . enterica may pose a risk to public health as they can spread the resistant bacteria across large spatial scales within a short time. Here, we whole‐genome sequenced 375 S . enterica strains from wild birds collected in 41 U.S. states during 1978–2019 to examine bacterial resistance to antibiotics and heavy metals. We found that Typhimurium was the dominant S . enterica serovar, accounting for 68.3% (256/375) of the bird isolates. Furthermore, the proportions of the isolates identified as multi‐antimicrobial resistant (multi‐AMR: resistant to at least three antimicrobial classes) or multi‐heavy metal resistant (multi‐HMR: resistant to at least three heavy metals) were both 1.87% (7/375). Interestingly, all the multi‐resistant S . enterica ( n = 12) were isolated from water birds or raptors; none of them was isolated from songbirds. Plasmid profiling demonstrated that 75% (9/12) of the multi‐resistant strains carried resistance plasmids. Our study indicates that wild birds do not serve as important reservoirs of multi‐resistant S . enterica strains. Nonetheless, continuous surveillance for bacterial resistance in wild birds is necessary because the multi‐resistant isolates identified in this study also showed close genetic relatedness with those from humans and domestic animals.

Modeling neurodegenerative diseases with cerebral organoids and other three-dimensional culture systems: focus on Alzheimer’s disease - Lalitha Venkataraman; Summer R. Fair; Craig A. McElroy; Mark E. Hester; Hongjun Fu (Stem Cell Reviews and Reports, 2022)

Review of Mercury’s dynamic magnetosphere: Post-MESSENGER era and comparative magnetospheres - Weijie Sun; Ryan M. Dewey; Sae Aizawa; Jia Huang; James A. Slavin; Suiyan Fu; Yong Wei; Charles F. Bowers (Science China Earth Sciences, 2022)
This review paper summarizes the research of Mercury’s magnetosphere in the Post-MESSENGER era and compares its dynamics to those in other planetary magnetospheres, especially to those in Earth’s magnetosphere. This review starts by introducing the planet Mercury, including its interplanetary environment, magnetosphere, exosphere, and conducting core. The frequent and intense magnetic reconnection on the dayside magnetopause, which is represented by the flux transfer event “shower”, is reviewed on how they depend on magnetosheath plasma β and magnetic shear angle across the magnetopause, following by how it contributes to the flux circulation and magnetosphere-surface-exosphere coupling. In the next, Mercury’s magnetosphere under extreme solar events, including the core induction and the reconnection erosion on the dayside magnetosphere, the responses of the nightside magnetosphere, are reviewed. Then, the dawn-dusk properties of the plasma sheet, including the features of the ions, the structure of the current sheet, and the dynamics of magnetic reconnection, are summarized. The last topic is devoted to the particle energization in Mercury’s magnetosphere, which includes the energization of the Kelvin-Helmholtz waves on the magnetopause boundaries, reconnection-generated magnetic structures, and the cross-tail electric field. In each chapter, the last section discusses the open questions related to each topic, which can be considered by the simulations and the future spacecraft mission. We end this paper by summarizing the future BepiColombo opportunities, which is a joint mission of ESA and JAXA and is en route to Mercury.

Aspirin use and prostate tumor angiogenesis - Benjamin C. Fu; Kai Wang; Lorelei A. Mucci; Steven K. Clinton; Edward L. Giovannucci (Cancer Causes & Control, 2022)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Investigation on the statistical characteristics of geoelectric field seismic anomalies in the North–South seismic belt of Chinese mainland - Hou Ze-Yu; An Zhang-Hui; Fan Ying-Ying; Tan Da-Cheng; Fu A-Long; Wei Lei (Acta Geophysica, 2021)

Soil pH determines bacterial distribution and assembly processes in natural mountain forests of eastern China - Yingying Ni; Teng Yang; Yuying Ma; Kaoping Zhang; Pamela S. Soltis; Douglas E. Soltis; Jack A. Gilbert; Yunpeng Zhao; Chengxin Fu; Haiyan Chu (Global Ecology and Biogeography, 2021)
Aim There have been numerous studies of forest‐soil microbial biogeography, but an integrated view of edaphic factors, plant, climatic factors, and geographic distance in determining the variation of bacterial community and assembly processes remains unclear at large spatial scales. Here, we analysed the factors affecting the biogeographic pattern and assembly processes of soil bacterial communities under 58 tree species in five natural mountain forests. Location Eastern China. Major taxa studied Bacterial communities. Methods Hierarchical partitioning analysis and distance decay models were performed to evaluate the relative contributions of plant phylogeny, environmental, and spatial variables to the composition of bacterial communities. We applied the nearest taxon index (NTI), β‐nearest taxon index (βNTI), and the modified Raup–Crick metric to reveal the mechanisms of bacterial assembly processes. Results We found that plant phylogeny accounted for a significant, but minor, fraction (0.7%) of the variation in composition of bacterial communities. In contrast, soil pH was the primary determinant of bacterial diversity and community composition, independently explaining 68.6 and 69.9% of the variation, respectively. Based on the NTI analysis, bacterial community assembly was more phylogenetically clustered with increasing soil pH. Variable selection was the predominant process explaining bacterial community assembly when differences in soil pH were ≥ 0.83, whereas homogenizing dispersal dominated when differences in soil pH were Main conclusions Our findings provide strong evidence that soil pH predominantly determines bacterial distribution and mediates the relative impact of stochasticity and determinism in soil bacterial community assembly. This suggests that climate‐change associated forest soil acidification could have a dramatic impact on soil bacterial diversity, composition, and function.

Genetic Depletion of Amylin/Calcitonin Receptors Improves Memory and Learning in Transgenic Alzheimer’s Disease Mouse Models - Aarti Patel; Ryoichi Kimura; Wen Fu; Rania Soudy; David MacTavish; David Westaway; Jing Yang; Rachel A. Davey; Jeffrey D. Zajac; Jack H. Jhamandas (Molecular Neurobiology, 2021)
Based upon its interactions with amyloid β peptide (Aβ), the amylin receptor, a class B G protein-coupled receptor (GPCR), is a potential modulator of Alzheimer’s disease (AD) pathogenesis. However, past pharmacological approaches have failed to resolve whether activation or blockade of this receptor would have greater therapeutic benefit. To address this issue, we generated compound mice expressing a human amyloid precursor protein gene with familial AD mutations in combination with deficiency of amylin receptors produced by hemizygosity for the critical calcitonin receptor subunit of this heterodimeric GPCR. These compound transgenic AD mice demonstrated attenuated responses to human amylin- and Aβ-induced depression of hippocampal long-term potentiation (LTP) in keeping with the genetic depletion of amylin receptors. Both the LTP responses and spatial memory (as measured with Morris water maze) in these mice were improved compared to AD mouse controls and, importantly, a reduction in both the amyloid plaque burden and markers of neuroinflammation was observed. Our data support the notion of further development of antagonists of the amylin receptor as AD-modifying therapies.

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Nuclear Sphingosine-1-phosphate Lyase Generated ∆2-hexadecenal is A Regulator of HDAC Activity and Chromatin Remodeling in Lung Epithelial Cells - David L. Ebenezer; Ramaswamy Ramchandran; Panfeng Fu; Lizar A. Mangio; Vidyani Suryadevara; Alison W. Ha; Evgeny Berdyshev; Paul P. Van Veldhoven; Stephen J. Kron; Fabian Schumacher; Burkhard Kleuser; Viswanathan Natarajan (Cell Biochemistry and Biophysics, 2021)

Evaluation of transfer of lead in soil plant animal system: assessment of consequences of its toxicity - Fu Chen; Jing Ma; Zafar Iqbal Khan; Kafeel Ahmad; Tasneem Ahmad; Ifra Saleem Malik; Asma Ashfaq; Mudasra Munir; Sonaina Nazar; Zunaira Munir; Abid Ejaz; Muhammad Nadeem; et al. (Environmental Science and Pollution Research, 2021)

Robust Estimation Procedure for Autoregressive Models with Heterogeneity - A. Callens; Y.-G. Wang; L. Fu; B. Liquet (Environmental Modeling & Assessment, 2021)

Interactions Between Ultraviolet B Radiation, Warming, and Changing Nitrogen Source May Reduce the Accumulation of Toxic Pseudo-nitzschia multiseries Biomass in Future Coastal Oceans - Kyla J. Kelly; Fei-Xue Fu; Xiaowen Jiang; He Li; Dong Xu; Nina Yang; Michelle A. DeMers; Joshua D. Kling; Kunshan Gao; Naihao Ye; David A. Hutchins (Frontiers in Marine Science, 2021)
Understanding the environmental conditions that trigger Pseudo-nitzschia bloom formation and domoic acid (DA) production is critical as the frequency and severity of these toxic blooms increases in the face of anthropogenic change. However, predicting the formation of these harmful blooms in a future ocean remains a challenge. Previous studies have examined the effects of single environmental drivers on Pseudo-nitzschia spp. growth and toxin production, but few have considered the interactions between them. In this multiple driver study with Pseudo-nitzschia multiseries , we used a full factorial matrix experimental design to examine the simultaneous effects of temperature (20 and 25°C), nitrogen source (nitrate and urea), and irradiance (photosynthetically active radiation with and without ultraviolet B radiation; UVB). This strain of P. multiseries was unable to withstand prolonged exposures (>0.5 h) to 0.06 mw⋅cm –2 UVB light, with implications for near-surface bloom formation if future shallower mixed layers increase UVB exposure. Growth rates were inhibited by UVB, but photosynthesis and carbon fixation continued at a reduced capacity. Additionally, DA synthesis continued despite UVB-induced growth inhibition. Warming by 5°C enhanced cellular DA quotas three-fold. Within these warmer treatments, urea-grown cultures exposed to UVB had the highest amount of DA per cell, suggesting that interactive effects between UVB exposure, warming, and urea can synergistically enhance toxin production. However, overall production of toxic biomass was low, as growth-integrated DA production rates were near zero. This indicates that although Pseudo-nitzschia multiseries cell-specific toxicity could worsen in an anthropogenically-altered future ocean, bloom formation may be inhibited by increased exposure to UVB. This multi-variable experimental approach revealed previously unknown interactions that could not have been predicted based on combined effects of single-variable experiments. Although P. multiseries DA production may be enhanced in a future ocean, inherent sensitivity to prolonged UVB exposure may moderate trophic transfer of toxin to coastal food webs.

The Combined Effects of Increased pCO2 and Warming on a Coastal Phytoplankton Assemblage: From Species Composition to Sinking Rate - Yuanyuan Feng; Fei Chai; Mark L. Wells; Yan Liao; Pengfei Li; Ting Cai; Ting Zhao; Feixue Fu; David A. Hutchins (Frontiers in Marine Science, 2021)
In addition to ocean acidification, a significant recent warming trend in Chinese coastal waters has received much attention. However, studies of the combined effects of warming and acidification on natural coastal phytoplankton assemblages here are scarce. We conducted a continuous incubation experiment with a natural spring phytoplankton assemblage collected from the Bohai Sea near Tianjin. Experimental treatments used a full factorial combination of temperature (7 and 11°C) and pCO 2 (400 and 800 ppm) treatments. Results suggest that changes in pCO 2 and temperature had both individual and interactive effects on phytoplankton species composition and elemental stoichiometry. Warming mainly favored the accumulation of picoplankton and dinoflagellate biomass. Increased pCO 2 significantly increased particulate organic carbon to particulate organic phosphorus (C:P) and particulate organic carbon to biogenic silica (C:BSi) ratios, and decreased total diatom abundance; in the meanwhile, higher pCO 2 significantly increased the ratio of centric to pennate diatom abundance. Warming and increased pCO 2 both greatly decreased the proportion of diatoms to dinoflagellates. The highest chlorophyll a biomass was observed in the high pCO 2 , high temperature phytoplankton assemblage, which also had the slowest sinking rate of all treatments. Overall, there were significant interactive effects of increased pCO 2 and warming on dinoflagellate abundance, pennate diatom abundance, diatom vs. dinoflagellates ratio and the centric vs. pennate ratio. These findings suggest that future ocean acidification and warming trends may individually and cumulatively affect coastal biogeochemistry and carbon fluxes through shifts in phytoplankton species composition and sinking rates.

Warming Iron-Limited Oceans Enhance Nitrogen Fixation and Drive Biogeographic Specialization of the Globally Important Cyanobacterium Crocosphaera - Nina Yang; Carlin A. Merkel; Yu-An Lin; Naomi M. Levine; Nicholas J. Hawco; Hai-Bo Jiang; Ping-Ping Qu; Michelle A. DeMers; Eric A. Webb; Fei-Xue Fu; David A. Hutchins (Frontiers in Marine Science, 2021)
Primary productivity in the nutrient-poor subtropical ocean gyres depends on new nitrogen inputs from nitrogen fixers that convert inert dinitrogen gas into bioavailable forms. Temperature and iron (Fe) availability constrain marine nitrogen fixation, and both are changing due to anthropogenic ocean warming. We examined the physiological responses of the globally important marine nitrogen fixer, Crocosphaera watsonii across its full thermal range as a function of iron availability. At the lower end of its thermal range, from 22 to 27°C, Crocosphaera growth, nitrogen fixation, and Nitrogen-specific Iron Use Efficiencies (N-IUEs, mol N fixed hour –1 mol Fe –1 ) increased with temperature. At an optimal growth temperature of 27°C, N-IUEs were 66% higher under iron-limited conditions than iron-replete conditions, indicating that low-iron availability increases metabolic efficiency. However, Crocosphaera growth and function decrease from 27 to 32°C, temperatures that are predicted for an increasing fraction of tropical oceans in the future. Altogether, this suggests that Crocosphaera are well adapted to iron-limited, warm waters, within prescribed limits. A model incorporating these results under the IPCC RCP 8.5 warming scenario predicts that Crocosphaera N-IUEs could increase by a net 47% by 2100, particularly in higher-latitude waters. These results contrast with published responses of another dominant nitrogen fixer ( Trichodesmium ), with predicted N-IUEs that increase most in low-latitude, tropical waters. These models project that differing responses of Crocosphaera and Trichodesmium N-IUEs to future warming of iron-limited oceans could enhance their current contributions to global marine nitrogen fixation with rates increasing by ∼91 and ∼22%, respectively, thereby shifting their relative importance to marine new production and also intensifying their regional divergence. Thus, interactive temperature and iron effects may profoundly transform existing paradigms of nitrogen biogeochemistry and primary productivity in open ocean regimes.

β-Adrenoceptor blockade prevents carotid body hyperactivity and elevated vascular sympathetic nerve density induced by chronic intermittent hypoxia - Abdulaziz A. Alzahrani; Lily L. Cao; Hayyaf S. Aldossary; Demitris Nathanael; Jiarong Fu; Clare J. Ray; Keith L. Brain; Prem Kumar; Andrew M. Coney; Andrew P. Holmes (Pflügers Archiv - European Journal of Physiology, 2021)
Carotid body (CB) hyperactivity promotes hypertension in response to chronic intermittent hypoxia (CIH). The plasma concentration of adrenaline is reported to be elevated in CIH and our previous work suggests that adrenaline directly activates the CB. However, a role for chronic adrenergic stimulation in mediating CB hyperactivity is currently unknown. This study evaluated whether beta-blocker treatment with propranolol (Prop) prevented the development of CB hyperactivity, vascular sympathetic nerve growth and hypertension caused by CIH. Adult male Wistar rats were assigned into 1 of 4 groups: Control (N), N + Prop, CIH and CIH + Prop. The CIH paradigm consisted of 8 cycles h −1 , 8 h day −1 , for 3 weeks. Propranolol was administered via drinking water to achieve a dose of 40 mg kg −1 day −1 . Immunohistochemistry revealed the presence of both β 1 and β 2 -adrenoceptor subtypes on the CB type I cell. CIH caused a 2–3-fold elevation in basal CB single-fibre chemoafferent activity and this was prevented by chronic propranolol treatment. Chemoafferent responses to hypoxia and mitochondrial inhibitors were attenuated by propranolol, an effect that was greater in CIH animals. Propranolol decreased respiratory frequency in normoxia and hypoxia in N and CIH. Propranolol also abolished the CIH mediated increase in vascular sympathetic nerve density. Arterial blood pressure was reduced in propranolol groups during hypoxia. Propranolol exaggerated the fall in blood pressure in most (6/7) CIH animals during hypoxia, suggestive of reduced sympathetic tone. These findings therefore identify new roles for β-adrenergic stimulation in evoking CB hyperactivity, sympathetic vascular hyperinnervation and altered blood pressure control in response to CIH.

Geographical and interspecific variation in susceptibility of three common thrips species to the insecticide, spinetoram - Yong-Fu Gao; Ya-Jun Gong; Li-Jun Cao; Jin-Cui Chen; Yu-Lin Gao; Majid Mirab-balou; Min Chen; Ary A. Hoffmann; Shu-Jun Wei (Journal of Pest Science, 2021)

Correction to: ChIP-seq and RNA-seq for complex and low-abundance tree buds reveal chromatin and expression co-dynamics during sweet cherry bud dormancy - Noémie Vimont; Fu Xiang Quah; David Guillaume-Schöpfer; François Roudier; Elisabeth Dirlewanger; Philip A. Wigge; Bénédicte Wenden; Sandra Cortijo (Tree Genetics & Genomes, 2020)

Low Static Shear Modulus Along Foliation and Its Influence on the Elastic and Strength Anisotropy of Poorman Schist Rocks, Homestake Mine, South Dakota - Katherine J. Condon; Hiroki Sone; Herbert F. Wang; J. Ajo-Franklin; T. Baumgartner; K. Beckers; D. Blankenship; A. Bonneville; L. Boyd; S. Brown; J. A. Burghardt; C. Chai; et al. (Rock Mechanics and Rock Engineering, 2020)

Development of a pro-arrhythmic ex vivo intact human and porcine model: cardiac electrophysiological changes associated with cellular uncoupling - Joseph Brook; Min-young Kim; Simos Koutsoftidis; David Pitcher; Danya Agha-Jaffar; Annam Sufi; Catherine Jenkins; Konstantinos Tzortzis; Suofeiya Ma; Richard J. Jabbour; Charles Houston; Balvinder S. Handa; et al. (Pflügers Archiv - European Journal of Physiology, 2020)
We describe a human and large animal Langendorff experimental apparatus for live electrophysiological studies and measure the electrophysiological changes due to gap junction uncoupling in human and porcine hearts. The resultant ex vivo intact human and porcine model can bridge the translational gap between smaller simple laboratory models and clinical research. In particular, electrophysiological models would benefit from the greater myocardial mass of a large heart due to its effects on far-field signal, electrode contact issues and motion artefacts, consequently more closely mimicking the clinical setting. Porcine ( n = 9) and human ( n = 4) donor hearts were perfused on a custom-designed Langendorff apparatus. Epicardial electrograms were collected at 16 sites across the left atrium and left ventricle. A total of 1 mM of carbenoxolone was administered at 5 ml/min to induce cellular uncoupling, and then recordings were repeated at the same sites. Changes in electrogram characteristics were analysed. We demonstrate the viability of a controlled ex vivo model of intact porcine and human hearts for electrophysiology with pharmacological modulation. Carbenoxolone reduces cellular coupling and changes contact electrogram features. The time from stimulus artefact to (-dV/dt) max increased between baseline and carbenoxolone (47.9 ± 4.1–67.2 ± 2.7 ms) indicating conduction slowing. The features with the largest percentage change between baseline and carbenoxolone were fractionation + 185.3%, endpoint amplitude − 106.9%, S-endpoint gradient + 54.9%, S point − 39.4%, RS ratio + 38.6% and (-dV/dt) max − 20.9%. The physiological relevance of this methodological tool is that it provides a model to further investigate pharmacologically induced pro-arrhythmic substrates.

Mercury and in situ sulfur isotopes as constraints on the metal and sulfur sources for the world’s largest Sb deposit at Xikuangshan, southern China - Shanling Fu; Ruizhong Hu; Runsheng Yin; Jun Yan; Xifeng Mi; Zhengcheng Song; Neal A. Sullivan (Mineralium Deposita, 2020)

Climate effects on size‐at‐age and growth rate of Chinook Salmon ( Oncorhynchus tshawytscha ) in the Fraser River, Canada - Yi Xu; A. Scott Decker; Charles K. Parken; Lynda M. Ritchie; David A. Patterson; Caihong Fu (Fisheries Oceanography, 2020)
Decline in size‐at‐age of Chinook Salmon ( Oncorhynchus tshawytscha ) has been observed for many populations across the entire Northeast Pacific Ocean, and identifying external drivers of this decline is important for sustainable management of these ecologically, economically, and culturally valuable resources. We assessed size‐at‐age of 96,939 Chinook Salmon sampled in the Fraser River watershed (Canada) from 1969 to 2017. A broad decline in size‐at‐age was confirmed across all population aggregates of Fraser River Chinook Salmon, in particular since year 2000. By developing a novel probability‐based approach to calculate age‐ and year‐specific growth rates for Fraser River Chinook Salmon and relating growth rates to environmental conditions in specific years through a machine learning method (boosted regression trees), we were able to disentangle multi‐year effects on size‐at‐age and thus identify environmental factors that were most related to the observed size‐at‐age of Chinook Salmon. Among 10 selected environmental variables, ocean salinity at Entrance Island in spring, the Aleutian Low Pressure Index and the North Pacific Current Bifurcation Index were consistently identified as important contributors for four of the seven age and population aggregate combinations. These top environmental contributors could be incorporated into future stock assessment and forecast models to improve Chinook Salmon fisheries management under climate change.

Semi-empirical prediction method for monthly precipitation prediction based on environmental factors and comparison with stochastic and machine learning models - Huihui Zhang; Hugo A. Loáiciga; Fu Ren; Qingyun Du; Da Ha (Hydrological Sciences Journal, 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Modeling leaf senescence of deciduous tree species in Europe - Qiang Liu; Shilong Piao; Matteo Campioli; Mengdi Gao; Yongshuo H. Fu; Kai Wang; Yue He; Xiangyi Li; Ivan A. Janssens (Global Change Biology, 2020)
Autumnal leaf senescence signals the end of photosynthetic activities in temperate deciduous trees and consequently exerts a strong control on various ecological processes. Predicting leaf senescence dates (LSD) with high accuracy is thus a prerequisite for better understanding the climate–ecosystem interactions. However, modeling LSD at large spatial and temporal scales is challenging. In this study, first, we used 19972 site‐year records (848 sites and four deciduous tree species) from the PAN European Phenology network to calibrate and evaluate six leaf senescence models during the period 1980–2013. Second, we extended the spatial analysis by repeating the procedure across Europe using satellite‐derived end of growing season and a forest map. Overall, we found that models that considered photoperiod and temperature interactions outperformed models using simple temperature or photoperiod thresholds for Betula pendula , Fagus sylvatica and Quercus robur . On the contrary, no model displayed reasonable predictions for Aesculus hippocastanum . This inter‐model comparison indicates that, contrary to expectation, photoperiod does not significantly modulate the accumulation of cooling degree days (CDD). On the other hand, considering the carryover effect of leaf unfolding date could promote the models’ predictability. The CDD models generally matched the observed LSD at species level and its interannual variation, but were limited in explaining the inter‐site variations, indicating that other environmental cues need to be considered in future model development. The discrepancies remaining between model simulations and observations highlight the need of manipulation studies to elucidate the mechanisms behind the leaf senescence process and to make current models more realistic.

Enhanced pyrogallol toxicity to cyanobacterium Microcystis aeruginosa with increasing alkalinity - Yunni Gao; Qinqin Fu; Jing Lu; Hui Yang; Philip T. Orr; Fang Zhang; Jing Dong; Man Zhang; Qianhong Gu; Chuanjiang Zhou; Michele A. Burford (Journal of Applied Phycology, 2020)

Effect of socioeconomic status on the relationship between short-term exposure to PM2.5 and cardiorespiratory mortality and morbidity in a megacity: the case of Santiago de Chile - Ernesto Pino-Cortés; Luis A. Díaz-Robles; Valeria Campos; Fidel Vallejo; Francisco Cubillos; Jaime Gómez; Francisco Cereceda-Balic; Joshua Fu; Samuel Carrasco; Juan Figueroa (Air Quality, Atmosphere & Health, 2020)

Long-term shifts in abundance of (migratory) crop-feeding and beneficial insect species in northeastern Asia - Jianglong Guo; Xiaowei Fu; Shengyuan Zhao; Xiujing Shen; Kris A. G. Wyckhuys; Kongming Wu (Journal of Pest Science, 2020)
Vast numbers of insects annually engage in trans-latitudinal migration and thereby impact structure and functioning of natural and man-made ecosystems. In eastern Asia, long-distance migration has historically been studied for single insect species rather than diverse species complexes. Here, we assessed migration dynamics of multiple economically important migratory species on an island in the Bohai Strait, China. Drawing upon 15-year trapping records of > 2.5 million specimens, we unveil inter- and intra-annual shifts in the species composition and abundance of migrant individuals. Migrants belonged to 9 orders and 36 families, primarily consisting of Lepidoptera (79% individuals), Odonata (8%), and Coleoptera (4%). Seven crop-feeding noctuids, e.g., Helicoverpa armigera (Hübner), Mythimna separata (Walker), represented 54% of the total trapping records. Trap catches exhibited marked seasonal variation, with the highest capture rate during early fall. Yearly abundance of migratory noctuids was coupled with that of their associated natural enemies. Although overall trap catches did not decrease over the monitoring period, the entire order of Odonata experienced a 14.1% annual rate of decline. Furthermore, 19 out of 108 species exhibited a progressively declining abundance over time, including the cosmopolitan cutworm Agrotis ipsilon (Hufnagel) and the insectivorous dragonfly Pantala flavescens Fabricius. Our work provides unprecedented insights into insect migration dynamics in eastern Asia, helps fine-tune forecasting and early-warning systems of crop pests, and thereby guides integrated pest management within local agro-landscapes. Also, a long-term tracking of migrant insect populations can shine light on the fate of (insect-mediated) ecosystem services and trophic dynamic processes at a macroscale.

ChIP-seq and RNA-seq for complex and low-abundance tree buds reveal chromatin and expression co-dynamics during sweet cherry bud dormancy - Noémie Vimont; Fu Xiang Quah; David Guillaume Schöepfer; François Roudier; Elisabeth Dirlewanger; Philip A. Wigge; Bénédicte Wenden; Sandra Cortijo (Tree Genetics & Genomes, 2020)
Chromatin immunoprecipitation-sequencing (ChIP-seq) is a robust technique to study interactions between proteins, such as histones or transcription factors and DNA. This technique in combination with RNA-sequencing (RNA-seq) is a powerful tool to better understand biological processes in eukaryotes. We developed a combined ChIP-seq and RNA-seq protocol for tree buds ( Prunus avium L., Prunus persica L Batch, Malus x domestica Borkh . ) that has also been successfully tested on Arabidopsis thaliana and Saccharomyces cerevisiae . Tree buds contain phenolic compounds that negatively interfere with ChIP and RNA extraction. In addition to solving this problem, our protocol is optimised to work on small amounts of material. Furthermore, one of the advantages of this protocol is that samples for ChIP-seq are cross-linked after flash freezing, making it possible to work on trees growing in the field and to perform ChIP-seq and RNA-seq on the same starting material. Focusing on dormant buds in sweet cherry, we explored the link between expression level and H3K4me3 enrichment for all genes, including a strong correlation between H3K4me3 enrichment at the DORMANCY-ASSOCIATED MADS-BOX 5 ( PavDAM5 ) loci and its expression pattern. This protocol will allow analysis of chromatin and transcriptomic dynamics in tree buds, notably during its development and response to the environment.

Interactions between ultraviolet radiation exposure and phosphorus limitation in the marine nitrogen‐fixing cyanobacteria Trichodesmium and Crocosphaera - Zhu Zhu; Feixue Fu; Pingping Qu; Esther Wing Kwan Mak; Haibo Jiang; Ruifeng Zhang; Zhuoyi Zhu; Kunshan Gao; David A. Hutchins (Limnology and Oceanography, 2020)
Increased stratification and mixed layer shoaling of the surface ocean resulting from warming can lead to exposure of marine dinitrogen (N 2 )‐fixing cyanobacteria to higher levels of inhibitory ultraviolet (UV) radiation. These same processes also reduce vertically advected supplies of the potentially limiting nutrient phosphorus (P) to N 2 fixers. It is currently unknown how UV inhibition and P limitation interact to affect the biogeochemical cycles of nitrogen and carbon in these biogeochemically critical microbes. We investigated the responses of the important and widespread marine N 2 ‐fixing cyanobacteria Crocosphaera (strain WH0005) and Trichodesmium (strains IMS 101 and GBR) to UV‐A and UV‐B under P‐replete and P‐limited conditions. Growth, N 2 fixation, and carbon dioxide (CO 2 ) fixation rates of Trichodesmium IMS 101 and Crocosphaera were negatively affected by UV exposure. This inhibition was greater for Trichodesmium IMS 101 than for Crocosphaera , which fixes N 2 only during the night and so avoids direct UV damage. Negative effects of UV on both IMS 101 and Crocosphaera were less in P‐limited cultures than in P‐replete cultures. In contrast, no UV inhibition was observed in GBR, regardless of P availability. UV inhibition was related to different amounts of UV‐absorbing compounds produced by these isolates. Responses to UV radiation and P availability interactions were taxon‐specific, but our results indicated that in general, UV radiation effects on Trichodesmium and Crocosphaera range from negative to neutral. UV inhibition and its interactions with P limitation may thus have a substantial influence on the present day and future nitrogen and carbon cycles of the ocean.

Differences in root surface adsorption, root uptake, subcellular distribution, and chemical forms of Cd between low- and high-Cd-accumulating wheat cultivars - Ya-Tao Xiao; Zhen-Jie Du; Carlos-A Busso; Xue-Bin Qi; Hai-Qing Wu; Wei Guo; Da-Fu Wu (Environmental Science and Pollution Research, 2020)

Temporal population variability in local forest communities has mixed effects on tree species richness across a latitudinal gradient - Tak Fung; Ryan A. Chisholm; Kristina Anderson‐Teixeira; Norm Bourg; Warren Y. Brockelman; Sarayudh Bunyavejchewin; Chia‐Hao Chang‐Yang; Rutuja Chitra‐Tarak; George Chuyong; Richard Condit; Handanakere S. Dattaraja; Stuart J. Davies; et al. (Ecology Letters, 2020)
Among the local processes that determine species diversity in ecological communities, fluctuation‐dependent mechanisms that are mediated by temporal variability in the abundances of species populations have received significant attention. Higher temporal variability in the abundances of species populations can increase the strength of temporal niche partitioning but can also increase the risk of species extinctions, such that the net effect on species coexistence is not clear. We quantified this temporal population variability for tree species in 21 large forest plots and found much greater variability for higher latitude plots with fewer tree species. A fitted mechanistic model showed that among the forest plots, the net effect of temporal population variability on tree species coexistence was usually negative, but sometimes positive or negligible. Therefore, our results suggest that temporal variability in the abundances of species populations has no clear negative or positive contribution to the latitudinal gradient in tree species richness.

Shortened temperature‐relevant period of spring leaf‐out in temperate‐zone trees - Yongshuo H. Fu; Xiaojun Geng; Fanghua Hao; Yann Vitasse; Constantin M. Zohner; Xuan Zhang; Xuancheng Zhou; Guodong Yin; Josep Peñuelas; Shilong Piao; Ivan A. Janssens (Global Change Biology, 2019)
Temperature during a particular period prior to spring leaf‐out, the temperature‐relevant period (TRP), is a strong determinant of the leaf‐out date in temperate‐zone trees. Climatic warming has substantially advanced leaf‐out dates in temperate biomes worldwide, but its effect on the beginning and length of the TRP has not yet been explored, despite its direct relevance for phenology modeling. Using 1,551 species–site combinations of long‐term (1951–2016) in situ observations on six tree species (namely, Aesculus hippocastanum , Alnus glutinosa , Betula pendula , Fagus sylvatica , Fraxinus excelsior , and Quercus robur ) in central Europe, we found that the advancing leaf‐out was accompanied by a shortening of the TRP. On average across all species and sites, the length of the TRP significantly decreased by 23% ( p

Different determinants of radiation use efficiency in cold and temperate forests - Manuela Balzarolo; Nadia Valdameri; Yongshuo H. Fu; Lennert Schepers; Ivan A. Janssens; Matteo Campioli (Global Ecology and Biogeography, 2019)
Aim To verify which vegetation and environmental factors are the most important in determining the spatial and temporal variability of average and maximum values of radiation use efficiency (RUE ann and RUE max , respectively) of cold and temperate forests. Location Forty‐eight cold and temperate forests distributed across the Northern Hemisphere. Major taxa studied Evergreen and deciduous trees. Time period 2000–2011. Methods We analysed the impact of 17 factors as potential determinants of mean RUE (at 8 days interval, annual and interannual level) and RUE max (at annual and interannual level) in cold and temperate forests by using linear regression and random forests models. Results Mean annual RUE (RUE ann , c. 1.1 gC/MJ) and RUE max ( c. 0.8 gC/MJ) did not differ between cold and temperate forests. However, for cold forests, RUE ann was affected by temperature‐related variables, while for temperate forests RUE ann was affected by drought‐related variables. Leaf area index (LAI) was important for both forest types, while N deposition only for cold forests and cloud cover only for temperate forest. RUE max of cold forests was mainly driven by N deposition and LAI, whereas for temperate forests only a weak relationship between RUE max and CO 2 concentration was found. Short‐term variability of RUE was strongly related to the meteorological variables and varied during the season and was stronger in summer than spring or autumn. Interannual variability of RUE ann and RUE max was only weakly related to the interannual variability of the environmental drivers. Main conclusions Cold and temperate forests show different relationships with the environment and vegetation properties. Among the RUE drivers observed, the least anticipated was N deposition. RUE is strongly related to short‐term and seasonal changes in meteorological variables among seasons and among sites. Our results should be considered in the formulation of climate zone‐specific tools for remote sensing and global models.

Combined effects of CO2 level, light intensity, and nutrient availability on the coccolithophore Emiliania huxleyi - Yong Zhang; Feixue Fu; David A. Hutchins; Kunshan Gao (Hydrobiologia, 2019)

Correction to: A newly developed APCC SCoPS and its prediction of East Asia seasonal climate variability - Suryun Ham; A-Young Lim; Suchul Kang; Hyein Jeong; Yeomin Jeong; Bin Wang; Baoqiang Xiang; Shu Wu; Joshua Xiouhua Fu (Climate Dynamics, 2019)

SEASTAR: A Mission to Study Ocean Submesoscale Dynamics and Small-Scale Atmosphere-Ocean Processes in Coastal, Shelf and Polar Seas - Christine Gommenginger; Bertrand Chapron; Andy Hogg; Christian Buckingham; Baylor Fox-Kemper; Leif Eriksson; Francois Soulat; Clément Ubelmann; Francisco Ocampo-Torres; Bruno Buongiorno Nardelli; David Griffin; Paco Lopez-Dekker; et al. (Frontiers in Marine Science, 2019)

Extensive changes in gene expression and alternative splicing due to homoeologous exchange in rice segmental allopolyploids - Zhibin Zhang; Tiansi Fu; Zhijian Liu; Xutong Wang; Hongwei Xun; Guo Li; Baoxu Ding; Yuzhu Dong; Xiuyun Lin; Karen A. Sanguinet; Bao Liu; Ying Wu; et al. (Theoretical and Applied Genetics, 2019)

Daylength helps temperate deciduous trees to leaf‐out at the optimal time - Yongshuo H. Fu; Xuan Zhang; Shilong Piao; Fanghua Hao; Xiaojun Geng; Yann Vitasse; Constantin Zohner; Josep Peñuelas; Ivan A. Janssens (Global Change Biology, 2019)
Global warming has led to substantially earlier spring leaf‐out in temperate‐zone deciduous trees. The interactive effects of temperature and daylength underlying this warming response remain unclear. However, they need to be accurately represented by earth system models to improve projections of the carbon and energy balances of temperate forests and the associated feedbacks to the Earth's climate system. We studied the control of leaf‐out by daylength and temperature using data from six tree species across 2,377 European phenological network ( www.pep725.eu ), each with at least 30 years of observations. We found that, in addition to and independent of the known effect of chilling, daylength correlates negatively with the heat requirement for leaf‐out in all studied species. In warm springs when leaf‐out is early, days are short and the heat requirement is higher than in an average spring, which mitigates the warming‐induced advancement of leaf‐out and protects the tree against precocious leaf‐out and the associated risks of late frosts. In contrast, longer‐than‐average daylength (in cold springs when leaf‐out is late) reduces the heat requirement for leaf‐out, ensuring that trees do not leaf‐out too late and miss out on large amounts of solar energy. These results provide the first large‐scale empirical evidence of a widespread daylength effect on the temperature sensitivity of leaf‐out phenology in temperate deciduous trees.

Plant phenology and global climate change: Current progresses and challenges - Shilong Piao; Qiang Liu; Anping Chen; Ivan A. Janssens; Yongshuo Fu; Junhu Dai; Lingli Liu; Xu Lian; Miaogen Shen; Xiaolin Zhu (Global Change Biology, 2019)
Plant phenology, the annually recurring sequence of plant developmental stages, is important for plant functioning and ecosystem services and their biophysical and biogeochemical feedbacks to the climate system. Plant phenology depends on temperature, and the current rapid climate change has revived interest in understanding and modeling the responses of plant phenology to the warming trend and the consequences thereof for ecosystems. Here, we review recent progresses in plant phenology and its interactions with climate change. Focusing on the start (leaf unfolding) and end (leaf coloring) of plant growing seasons, we show that the recent rapid expansion in ground‐ and remote sensing‐ based phenology data acquisition has been highly beneficial and has supported major advances in plant phenology research. Studies using multiple data sources and methods generally agree on the trends of advanced leaf unfolding and delayed leaf coloring due to climate change, yet these trends appear to have decelerated or even reversed in recent years. Our understanding of the mechanisms underlying the plant phenology responses to climate warming is still limited. The interactions between multiple drivers complicate the modeling and prediction of plant phenology changes. Furthermore, changes in plant phenology have important implications for ecosystem carbon cycles and ecosystem feedbacks to climate, yet the quantification of such impacts remains challenging. We suggest that future studies should primarily focus on using new observation tools to improve the understanding of tropical plant phenology, on improving process‐based phenology modeling, and on the scaling of phenology from species to landscape‐level.

Short photoperiod reduces the temperature sensitivity of leaf‐out in saplings of Fagus sylvatica but not in horse chestnut - Yongshuo H. Fu; Shilong Piao; Xuancheng Zhou; Xiaojun Geng; Fanghua Hao; Yann Vitasse; Ivan A. Janssens (Global Change Biology, 2019)
Leaf phenology is one of the most reliable bioindicators of ongoing global warming in temperate and boreal zones because it is highly sensitive to temperature variation. A large number of studies have reported advanced spring leaf‐out due to global warming, yet the temperature sensitivity of leaf‐out has significantly decreased in temperate deciduous tree species over the past three decades. One of the possible mechanisms is that photoperiod is limiting further advance to protect the leaves against potential damaging frosts. However, the “photoperiod limitation” hypothesis remains poorly investigated and experimentally tested. Here, we conducted a photoperiod‐ and temperature‐manipulation experiment in climate chambers on two common deciduous species in Europe: Fagus sylvatica (European beech, a typically late flushing species) and Aesculus hippocastanum (horse chestnut, a typically early flushing species). In agreement with previous studies, we found that the warming significantly advanced the leaf‐out dates by 4.3 and 3.7 days/°C for beech and horse chestnut saplings, respectively. However, shorter photoperiod significantly reduced the temperature sensitivity of beech only (3.0 days/°C) by substantially increasing the heat requirement to avoid leafing‐out too early. Interestingly, the photoperiod limitation only occurs below a certain daylength (photoperiod threshold) when the warming increased above 4°C for beech trees. In contrast, for chestnut, no photoperiod threshold was found even when the ambient air temperature was warmed by 5°C. Given the species‐specific photoperiod effect on leaf phenology, the sequence of the leaf‐out timing among forest tree species may change under future climate warming conditions. Nonphotoperiodic species may benefit from warmer springs by starting the growing season earlier than photoperiodic sensitive species, modifying forest ecosystem structure and functions, but this photoperiod limitation needs to be further investigated experimentally in numerous specie s .

Timing and genesis of Cu–(Au) mineralization in the Khetri Copper Belt, northwestern India: constraints from in situ U–Pb ages and Sm–Nd isotopes of monazite-(Ce) - Xiao-Chun Li; Mei-Fu Zhou; A. E. Williams-Jones; Yue-Heng Yang; Jian-Feng Gao (Mineralium Deposita, 2019)

Physiological responses of the freshwater N 2 ‐fixing cyanobacterium Raphidiopsis raciborskii to Fe and N availabilities - Qing‐Long Fu; Anna C. Y. Yeung; Manabu Fujii; Brett A. Neilan; T. David Waite (Environmental Microbiology, 2019)
Summary The cyanobacterium Raphidiopsis raciborskii is of environmental and social concern in view of its toxicity, bloom‐forming characteristics and increasingly widespread occurrence. However, while availability of macronutrients and micronutrients such as N and Fe are critically important for the growth and metabolism of this organism, the physiological response of toxic and non‐toxic strains of R. raciborskii to varying Fe and N availabilities remains unclear. By determining physiological parameters as a function of Fe and N availability, we demonstrate that R. raciborskii growth and N 2 ‐fixing activity are facilitated at higher Fe availability under N 2 ‐limited conditions with faster growth of the CS‐506 (cylindrospermopsin‐producing) strain compared with that of CS‐509 (the non‐toxic) strain. Radiolabelled Fe uptake assays indicated that R. raciborskii acclimated under Fe‐limited conditions acquires Fe at significantly higher rates than under Fe replete conditions, principally via unchelated Fe(II) generated as a result of photoreduction of complexed Fe(III). While N 2 ‐fixation of both strains occurred during both day and night, the CS‐506 strain overall exhibited higher N 2 ‐fixing and Fe uptake rates than the CS‐509 strain under N‐deficient and Fe‐limited conditions. The findings of this study highlight that Fe availability is of significance for the ecological advantage of CS‐506 over CS‐509 in N‐deficient freshwaters.

Exploration for native parasitoids of Drosophila suzukii in China reveals a diversity of parasitoid species and narrow host range of the dominant parasitoid - Massimo Giorgini; Xin-Geng Wang; Yan Wang; Fu-Shou Chen; Evelyne Hougardy; Hong-Mei Zhang; Zong-Qi Chen; Hong-Yin Chen; Chen-Xi Liu; Pasquale Cascone; Giorgio Formisano; Gislaine A. Carvalho; et al. (Journal of Pest Science, 2019)

Simplified representative models for long-term flow and advective transport in fractured crystalline bedrock - Joel E. Geier; Georg A. Lindgren; Chin-Fu Tsang (Hydrogeology Journal, 2019)

Genotyping-by-sequencing empowered genetic diversity analysis of Jordanian oat wild relative Avena sterilis - Nawal Al-Hajaj; Gregory W. Peterson; Carolee Horbach; Khaled Al-Shamaa; Nicholas A. Tinker; Yong-Bi Fu (Genetic Resources and Crop Evolution, 2018)

Real-World Variability in the Prediction of Intracranial Aneurysm Wall Shear Stress: The 2015 International Aneurysm CFD Challenge - Kristian Valen-Sendstad; Aslak W. Bergersen; Yuji Shimogonya; Leonid Goubergrits; Jan Bruening; Jordi Pallares; Salvatore Cito; Senol Piskin; Kerem Pekkan; Arjan J. Geers; Ignacio Larrabide; Saikiran Rapaka; et al. (Cardiovascular Engineering and Technology, 2018)

Demographic expansion and genetic load of the halophyte model plant Eutrema salsugineum - Xiao‐Juan Wang; Quan‐Jun Hu; Xin‐Yi Guo; Kun Wang; Da‐Fu Ru; Dmitry A. German; Elizabeth A. Weretilnyk; Richard J. Abbott; Martin Lascoux; Jian‐quan Liu (Molecular Ecology, 2018)
The halophyte model plant Eutrema salsugineum (Brassicaceae) disjunctly occurs in temperate to subarctic Asia and North America. This vast, yet extremely discontinuous distribution constitutes an ideal system to examine long‐distance dispersal and the ensuing accumulation of deleterious mutations as expected in expanding populations of selfing plants. In this study, we resequenced individuals from 23 populations across the range of E . salsugineum . Our population genomic data indicate that E . salsugineum migrated “out of the Altai region” at least three times to colonize northern China, northeast Russia and western China. It then expanded its distribution into North America independently from northeast Russia and northern China, respectively. The species colonized northern China around 33.7 thousand years ago (kya) and underwent a considerable expansion in range size approximately 7–8 kya. The western China lineage is likely a hybrid derivative of the northern China and Altai lineages, originating approximately 25–30 kya. Deleterious alleles accumulated in a stepwise manner from (a) Altai to northern China and North America and (b) Altai to northeast Russia and North America. In summary, E . salsugineum dispersed from Asia to North America and deleterious mutations accumulated in a stepwise manner during the expansion of the species’ distribution.

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

DNA Barcoding for Identification of Sugarcane Borers in China - J- D Wang; W- Z Wang; Z- L Lin; A Ali; H- Y Fu; M- T Huang; S- J Gao; R Wang (Neotropical Entomology, 2018)

Responses of the large centric diatom Coscinodiscus sp. to interactions between warming, elevated CO 2 , and nitrate availability - Pingping Qu; Feixue Fu; David A. Hutchins (Limnology and Oceanography, 2018)
Marine ecosystems are facing multiple anthropogenic global changes, including ocean acidification, warming, and reduced nutrient supplies. Together, these will challenge phytoplankton including large centric diatoms such as Coscinodiscus sp., a group that is important to ocean food webs and carbon export. We investigated the interactive effects of warming, elevated CO 2 , and nitrate availability on Coscinodiscus growth, elemental stoichiometry, and Fe and C uptake rates in a four‐treatment factorial experiment combining two CO 2 levels (∼400 ppm and 800 ppm) and two temperatures (16°C and 20°C) across seven nitrate concentrations (1–100 μ mol L −1 ). Higher temperatures led to higher maximum growth rates ( μ max ), but also higher half‐saturation constants for nitrate ( K 1/2 ), while elevated CO 2 increased K 1/2 only at the warmer temperature. Lower μ max / K 1/2 ratios under warming and rising CO 2 indicated a higher nitrate requirement at these conditions. High temperature decreased cellular P and Si contents and consequently increased N : P and C : Si ratios, especially at ambient CO 2 . Fe : C uptake ratios responded positively to lower nitrate levels, lower CO 2 , and warming. Significant interactions between nitrate availability and temperature or CO 2 were observed for specific growth rates, chlorophyll a and Si contents, Fe : C, N : P, and Si : C, while temperature and CO 2 interactions were only significant for μ max / K 1/2 and cellular P content. The mutual interactions among CO 2 concentrations, temperature, and nitrate supply may all affect future growth, physiology, and carbon export by Coscinodiscus sp., however, in general warming and nitrate availability appear to be more influential than CO 2 .

Larger temperature response of autumn leaf senescence than spring leaf‐out phenology - Yongshuo H. Fu; Shilong Piao; Nicolas Delpierre; Fanghua Hao; Heikki Hänninen; Yongjie Liu; Wenchao Sun; Ivan A. Janssens; Matteo Campioli (Global Change Biology, 2018)
Climate warming is substantially shifting the leaf phenological events of plants, and thereby impacting on their individual fitness and also on the structure and functioning of ecosystems. Previous studies have largely focused on the climate impact on spring phenology, and to date the processes underlying leaf senescence and their associated environmental drivers remain poorly understood. In this study, experiments with temperature gradients imposed during the summer and autumn were conducted on saplings of European beech to explore the temperature responses of leaf senescence. An additional warming experiment during winter enabled us to assess the differences in temperature responses of spring leaf‐out and autumn leaf senescence. We found that warming significantly delayed the dates of leaf senescence both during summer and autumn warming, with similar temperature sensitivities (6–8 days delay per °C warming), suggesting that, in the absence of water and nutrient limitation, temperature may be a dominant factor controlling the leaf senescence in European beech. Interestingly, we found a significantly larger temperature response of autumn leaf senescence than of spring leaf‐out. This suggests a possible larger contribution of delays in autumn senescence, than of the advancement in spring leaf‐out, to extending the growing season under future warmer conditions.

Levels of PCDD/Fs, PBDEs, and PBDD/Fs in Breast Milk from Southern Taiwan - Men-Wen Chen; Bryan Angelo A. Castillo; Din-Yan Lin; How-Ran Chao; Lemmuel L. Tayo; Yan-You Gou; Fu-An Chen; Kuo-Lin Huang (Bulletin of Environmental Contamination and Toxicology, 2018)

Simulating the onset of spring vegetation growth across the Northern Hemisphere - Qiang Liu; Yongshuo H. Fu; Yongwen Liu; Ivan A. Janssens; Shilong Piao (Global Change Biology, 2018)
Changes in the spring onset of vegetation growth in response to climate change can profoundly impact climate–biosphere interactions. Thus, robust simulation of spring onset is essential to accurately predict ecosystem responses and feedback to ongoing climate change. To date, the ability of vegetation phenology models to reproduce spatiotemporal patterns of spring onset at larger scales has not been thoroughly investigated. In this study, we took advantage of phenology observations via remote sensing to calibrate and evaluated six models, including both one‐phase (considering only forcing temperatures) and two‐phase (involving forcing, chilling, and photoperiod) models across the Northern Hemisphere between 1982 and 2012. Overall, we found that the model that integrated the photoperiod effect performed best at capturing spatiotemporal patterns of spring phenology in boreal and temperate forests. By contrast, all of the models performed poorly in simulating the onset of growth in grasslands. These results suggest that the photoperiod plays a role in controlling the onset of growth in most Northern Hemisphere forests, whereas other environmental factors (e.g., precipitation) should be considered when simulating the onset of growth in grasslands. We also found that the one‐phase model performed as well as the two‐phase models in boreal forests, which implies that the chilling requirement is probably fulfilled across most of the boreal zone. Conversely, two‐phase models performed better in temperate forests than the one‐phase model, suggesting that photoperiod and chilling play important roles in these temperate forests. Our results highlight the significance of including chilling and photoperiod effects in models of the spring onset of forest growth at large scales, and indicate that the consideration of additional drivers may be required for grasslands.

Field-Based Radiographic Imaging of Marine Megafauna: Marine Iguanas (Amblyrhynchus cristatus) as a Case Study - Gregory A. Lewbart; Eli B. Cohen; Maximilian Hirschfeld; Juan Pablo Muñoz-Pérez; Juan García; Andy Fu; Emile P. Chen; Kenneth J. Lohmann (Frontiers in Marine Science, 2018)

Simulated differences in 21st century aridity due to different scenarios of greenhouse gases and aerosols - L. Lin; A. Gettelman; Q. Fu; Y. Xu (Climatic Change, 2018)

Phenological responses of Icelandic subarctic grasslands to short‐term and long‐term natural soil warming - Niki I. W. Leblans; Bjarni D. Sigurdsson; Sara Vicca; Yongshuo Fu; Josep Penuelas; Ivan A. Janssens (Global Change Biology, 2017)
The phenology of vegetation, particularly the length of the growing season ( LOS ; i.e., the period from greenup to senescence), is highly sensitive to climate change, which could imply potent feedbacks to the climate system, for example, by altering the ecosystem carbon (C) balance. In recent decades, the largest extensions of LOS have been reported at high northern latitudes, but further warming‐induced LOS extensions may be constrained by too short photoperiod or unfulfilled chilling requirements. Here, we studied subarctic grasslands, which cover a vast area and contain large C stocks, but for which LOS changes under further warming are highly uncertain. We measured LOS extensions of Icelandic subarctic grasslands along natural geothermal soil warming gradients of different age (short term, where the measurements started after 5 years of warming and long term, i.e., warmed since ≥50 years) using ground‐level measurements of normalized difference vegetation index. We found that LOS linearly extended with on average 2.1 days per °C soil warming up to the highest soil warming levels (ca. +10°C) and that LOS had the potential to extend at least 1 month. This indicates that the warming impact on LOS in these subarctic grasslands will likely not saturate in the near future. A similar response to short‐ and long‐term warming indicated a strong physiological control of the phenological response of the subarctic grasslands to warming and suggested that genetic adaptations and community changes were likely of minor importance. We conclude that the warming‐driven extension of the LOS s of these subarctic grasslands did not saturate up to +10°C warming, and hence that growing seasons of high‐latitude grasslands are likely to continue lengthening with future warming (unless genetic adaptations or species shifts do occur). This persistence of the warming‐induced extension of LOS has important implications for the C‐sink potential of subarctic grasslands under climate change.

Biogeographic conservation of the cytosine epigenome in the globally important marine, nitrogen‐fixing cyanobacterium Trichodesmium - Nathan G. Walworth; David A. Hutchins; Egor Dolzhenko; Michael D. Lee; Feixue Fu; Andrew D. Smith; Eric A. Webb (Environmental Microbiology, 2017)
Summary Cytosine methylation has been shown to regulate essential cellular processes and impact biological adaptation. Despite its evolutionary importance, only a handful of bacterial, genome‐wide cytosine studies have been conducted, with none for marine bacteria. Here, we examine the genome‐wide, C 5 ‐Methyl‐cytosine (m5C) methylome and its correlation to global transcription in the marine nitrogen‐fixing cyanobacterium Trichodesmium . We characterize genome‐wide methylation and highlight conserved motifs across three Trichodesmium isolates and two Trichodesmium metagenomes, thereby identifying highly conserved, novel genomic signatures of potential gene regulation in Trichodesmium . Certain gene bodies with the highest methylation levels correlate with lower expression levels. Several methylated motifs were highly conserved across spatiotemporally separated Trichodesmium isolates, thereby elucidating biogeographically conserved methylation potential. These motifs were also highly conserved in Trichodesmium metagenomic samples from natural populations suggesting them to be potential in situ markers of m5C methylation. Using these data, we highlight predicted roles of cytosine methylation in global cellular metabolism providing evidence for a ‘core’ m5C methylome spanning different ocean regions. These results provide important insights into the m5C methylation landscape and its biogeochemical implications in an important marine N 2 ‐fixer, as well as advancing evolutionary theory examining methylation influences on adaptation.

A new indole alkaloid with anti-inflammatory activity from Nauclea officinalis - Qing-Long Liu; A-Hong Chen; Jin-Ying Tang; Yan-Lei Ma; Zhi-Hua Jiang; Yan-Ping Liu; Guang-Ying Chen; Yan-Hui Fu; Wei Xu (Natural Product Research, 2017)

Mineral Processing Residue Use as Substrate in a Modular Engineered Wetland for Wastewater Treatment - Zheng Yuan; Shasha Fu; Xinfa Xu; Laura A. Wendling (Environmental Processes, 2017)

A new monoterpenoid indole alkaloid from Ochrosia elliptica - A-Hong Chen; Qing-Long Liu; Yan-Lei Ma; Zhi-Hua Jiang; Jin-Ying Tang; Yan-Ping Liu; Guang-Ying Chen; Yan-Hui Fu; Wei Xu (Natural Product Research, 2017)

Rotor Tracking Using Phase of Electrograms Recorded During Atrial Fibrillation - Caroline H. Roney; Chris D. Cantwell; Norman A. Qureshi; Rasheda A. Chowdhury; Emmanuel Dupont; Phang Boon Lim; Edward J. Vigmond; Jennifer H. Tweedy; Fu Siong Ng; Nicholas S. Peters (Annals of Biomedical Engineering, 2017)

Time Course Field Analysis of COMT-Downregulated Switchgrass: Lignification, Recalcitrance, and Rust Susceptibility - Holly L. Baxter; Mitra Mazarei; Chunxiang Fu; Qunkang Cheng; Geoffrey B. Turner; Robert W. Sykes; Mark T. Windham; Mark F. Davis; Richard A. Dixon; Zeng-Yu Wang; C. Neal Stewart (BioEnergy Research, 2016)

High-density marker profiling confirms ancestral genomes of Avena species and identifies D-genome chromosomes of hexaploid oat - Honghai Yan; Wubishet A. Bekele; Charlene P. Wight; Yuanying Peng; Tim Langdon; Robert G. Latta; Yong-Bi Fu; Axel Diederichsen; Catherine J. Howarth; Eric N. Jellen; Brian Boyle; Yuming Wei; et al. (Theoretical and Applied Genetics, 2016)

Impact of Partially Cemented and Non-persistent Natural Fractures on Hydraulic Fracture Propagation - Wei Fu; Brandon C. Ames; Andrew P. Bunger; Alexei A. Savitski (Rock Mechanics and Rock Engineering, 2016)

Long-term linear trends mask phenological shifts - Yongshuo H Fu; Shilong Piao; Philippe Ciais; Mengtian Huang; Annette Menzel; Marc Peaucelle; Shushi Peng; Yang Song; Yann Vitasse; Zhenzhong Zeng; Hongfang Zhao; Guiyun Zhou; et al. (International Journal of Biometeorology, 2016)

Delayed autumn phenology in the Northern Hemisphere is related to change in both climate and spring phenology - Qiang Liu; Yongshuo H. Fu; Zaichun Zhu; Yongwen Liu; Zhuo Liu; Mengtian Huang; Ivan A. Janssens; Shilong Piao (Global Change Biology, 2016)
The timing of the end of the vegetation growing season ( EOS ) plays a key role in terrestrial ecosystem carbon and nutrient cycles. Autumn phenology is, however, still poorly understood, and previous studies generally focused on few species or were very limited in scale. In this study, we applied four methods to extract EOS dates from NDVI records between 1982 and 2011 for the Northern Hemisphere, and determined the temporal correlations between EOS and environmental factors (i.e., temperature, precipitation and insolation), as well as the correlation between spring and autumn phenology, using partial correlation analyses. Overall, we observed a trend toward later EOS in ~70% of the pixels in Northern Hemisphere, with a mean rate of 0.18 ± 0.38 days yr −1 . Warming preseason temperature was positively associated with the rate of EOS in most of our study area, except for arid/semi‐arid regions, where the precipitation sum played a dominant positive role. Interestingly, increased preseason insolation sum might also lead to a later date of EOS . In addition to the climatic effects on EOS , we found an influence of spring vegetation green‐up dates on EOS , albeit biome dependent. Our study, therefore, suggests that both environmental factors and spring phenology should be included in the modeling of EOS to improve the predictions of autumn phenology as well as our understanding of the global carbon and nutrient balances.

Osteogenic Treatment Initiating a Tissue-Engineered Cartilage Template Hypertrophic Transition - J. Y. Fu; S. Y. Lim; P. F. He; C. J. Fan; D. A. Wang (Annals of Biomedical Engineering, 2016)

Fast neutron-induced structural rearrangements at a soybean NAP1 locus result in gnarled trichomes - Benjamin W. Campbell; Anna N. Hofstad; Suma Sreekanta; Fengli Fu; Thomas J. Y. Kono; Jamie A. O’Rourke; Carroll P. Vance; Gary J. Muehlbauer; Robert M. Stupar (Theoretical and Applied Genetics, 2016)

Strong impacts of daily minimum temperature on the green‐up date and summer greenness of the Tibetan Plateau - Miaogen Shen; Shilong Piao; Xiaoqiu Chen; Shuai An; Yongshuo H. Fu; Shiping Wang; Nan Cong; Ivan A. Janssens (Global Change Biology, 2016)
Understanding vegetation responses to climate change on the Tibetan Plateau ( TP ) helps in elucidating the land–atmosphere energy exchange, which affects air mass movement over and around the TP . Although the TP is one of the world's most sensitive regions in terms of climatic warming, little is known about how the vegetation responds. Here, we focus on how spring phenology and summertime greenness respond to the asymmetric warming, that is, stronger warming during nighttime than during daytime. Using both in situ and satellite observations, we found that vegetation green‐up date showed a stronger negative partial correlation with daily minimum temperature ( T min ) than with maximum temperature ( T max ) before the growing season (‘preseason’ henceforth). Summer vegetation greenness was strongly positively correlated with summer T min , but negatively with T max . A 1‐K increase in preseason T min advanced green‐up date by 4 days ( P P 0.01). In contrast, increases in preseason T max did not advance green‐up date ( P > 0.10) and higher summer T max even reduced greenness by 2.6% K −1 ( P 0.05). The stimulating effects of increasing T min were likely caused by reduced low temperature constraints, and the apparent negative effects of higher T max on greenness were probably due to the accompanying decline in water availability. The dominant enhancing effect of nighttime warming indicates that climatic warming will probably have stronger impact on TP ecosystems than on apparently similar Arctic ecosystems where vegetation is controlled mainly by T max . Our results are crucial for future improvements of dynamic vegetation models embedded in the Earth System Models which are being used to describe the behavior of the Asian monsoon. The results are significant because the state of the vegetation on the TP plays an important role in steering the monsoon.

Parasitism Performance of Tetrastichus brontispae Ferriere over the Coconut Hispine Beetle, Brontispa longissima (Gestro) - K Liu; B L Fu; J R Lin; Y G Fu; Z Q Peng; Q A Jin; L D Tang (Neotropical Entomology, 2016)

Poisonings Associated with Intubation: US National Poison Data System Exposures 2000–2013 - G. A. Beauchamp; S. L. Giffin; B. Z. Horowitz; A. L. Laurie; R. Fu; R. G. Hendrickson (Journal of Medical Toxicology, 2016)

Analyzing Economic and Environmental Performance of Switchgrass Biofuel Supply Chains - T. Edward Yu; Burton C. English; Lixia He; James A. Larson; James Calcagno; Joshua S. Fu; Brad Wilson (BioEnergy Research, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Does geographic location impact the survival differential between screen- and interval-detected breast cancers? - Jeff Ching-Fu Hsieh; Susanna M. Cramb; James M. McGree; Nathan A. M. Dunn; Peter D. Baade; Kerrie L. Mengersen (Stochastic Environmental Research and Risk Assessment, 2016)

A correlated shortening of the North and South American monsoon seasons in the past few decades - Paola A. Arias; Rong Fu; Carolina Vera; Maisa Rojas (Climate Dynamics, 2015)

Increased heat requirement for leaf flushing in temperate woody species over 1980–2012: effects of chilling, precipitation and insolation - Yongshuo H. Fu; Shilong Piao; Yann Vitasse; Hongfang Zhao; Hans J. De Boeck; Qiang Liu; Hui Yang; Ulrich Weber; Heikki Hänninen; Ivan A. Janssens (Global Change Biology, 2015)
Recent studies have revealed large unexplained variation in heat requirement‐based phenology models, resulting in large uncertainty when predicting ecosystem carbon and water balance responses to climate variability. Improving our understanding of the heat requirement for spring phenology is thus urgently needed. In this study, we estimated the species‐specific heat requirement for leaf flushing of 13 temperate woody species using long‐term phenological observations from Europe and North America. The species were defined as early and late flushing species according to the mean date of leaf flushing across all sites. Partial correlation analyses were applied to determine the temporal correlations between heat requirement and chilling accumulation, precipitation and insolation sum during dormancy. We found that the heat requirement for leaf flushing increased by almost 50% over the study period 1980–2012, with an average of 30 heat units per decade. This temporal increase in heat requirement was observed in all species, but was much larger for late than for early flushing species. Consistent with previous studies, we found that the heat requirement negatively correlates with chilling accumulation. Interestingly, after removing the variation induced by chilling accumulation, a predominantly positive partial correlation exists between heat requirement and precipitation sum, and a predominantly negative correlation between heat requirement and insolation sum. This suggests that besides the well‐known effect of chilling, the heat requirement for leaf flushing is also influenced by precipitation and insolation sum during dormancy. However, we hypothesize that the observed precipitation and insolation effects might be artefacts attributable to the inappropriate use of air temperature in the heat requirement quantification. Rather than air temperature, meristem temperature is probably the prominent driver of the leaf flushing process, but these data are not available. Further experimental research is thus needed to verify whether insolation and precipitation sums directly affect the heat requirement for leaf flushing.

Effect of Biochar in Cadmium Availability and Soil Biological Activity in an Anthrosol Following Acid Rain Deposition and Aging - H. Lu; Z. Li; S. Fu; A. Méndez; G. Gascó; J. Paz-Ferreiro (Water, Air, & Soil Pollution, 2015)

Coupling of postural activity with motion of a ship at sea - Manuel Varlet; Benoît G. Bardy; Fu-Chen Chen; Cristina Alcantara; Thomas A. Stoffregen (Experimental Brain Research, 2015)

A Systematic Assessment of the Use of Platelet-Rich Plasma in Spinal Fusion - Benjamin D. Elder; Christina Holmes; C. Rory Goodwin; Sheng-Fu Lo; Varun Puvanesarajah; Thomas A. Kosztowski; John E. Locke; Timothy F. Witham (Annals of Biomedical Engineering, 2015)

Electron transport kinetics in the diazotrophic cyanobacterium Trichodesmium spp. grown across a range of light levels - Xiaoni Cai; Kunshan Gao; Feixue Fu; Douglas A. Campbell; John Beardall; David A. Hutchins (Photosynthesis Research, 2015)

Association of genetic variation in IKZF1, ARID5B, and CEBPE and surrogates for early-life infections with the risk of acute lymphoblastic leukemia in Hispanic children - Ling-I. Hsu; Anand P. Chokkalingam; Farren B. S. Briggs; Kyle Walsh; Vonda Crouse; Cecilia Fu; Catherine Metayer; Joseph L. Wiemels; Lisa F. Barcellos; Patricia A. Buffler (Cancer Causes & Control, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Spatially resolved estimation of ozone-related mortality in the United States under two representative concentration pathways (RCPs) and their uncertainty - Young-Min Kim; Ying Zhou; Yang Gao; Joshua S. Fu; Brent A. Johnson; Cheng Huang; Yang Liu (Climatic Change, 2015)

mTOR ATP-competitive inhibitor INK128 inhibits neuroblastoma growth via blocking mTORC signaling - Huiyuan Zhang; Jun Dou; Yang Yu; Yanling Zhao; Yihui Fan; Jin Cheng; Xin Xu; Wei Liu; Shan Guan; Zhenghu Chen; Yan shi; Roma Patel; et al. (Apoptosis, 2015)

Accuracy and Reproducibility of Patient-Specific Hemodynamic Models of Stented Intracranial Aneurysms: Report on the Virtual Intracranial Stenting Challenge 2011 - S. Cito; A. J. Geers; M. P. Arroyo; V. R. Palero; J. Pallarés; A. Vernet; J. Blasco; L. San Román; W. Fu; A. Qiao; G. Janiga; Y. Miura; et al. (Annals of Biomedical Engineering, 2015)

The risk‐return trade‐off between solitary and eusocial reproduction - Feng Fu; Sarah D. Kocher; Martin A. Nowak (Ecology Letters, 2015)
Social insect colonies can be seen as a distinct form of biological organisation because they function as superorganisms. Understanding how natural selection acts on the emergence and maintenance of these colonies remains a major question in evolutionary biology and ecology. Here, we explore this by using multi‐type branching processes to calculate the basic reproductive ratios and the extinction probabilities for solitary vs. eusocial reproductive strategies. We find that eusociality, albeit being hugely successful once established, is generally less stable than solitary reproduction unless large demographic advantages of eusociality arise for small colony sizes. We also demonstrate how such demographic constraints can be overcome by the presence of ecological niches that strongly favour eusociality. Our results characterise the risk‐return trade‐offs between solitary and eusocial reproduction, and help to explain why eusociality is taxonomically rare: eusociality is a high‐risk, high‐reward strategy, whereas solitary reproduction is more conservative.

Unexpected role of winter precipitation in determining heat requirement for spring vegetation green‐up at northern middle and high latitudes - Yongshuo H Fu; Shilong Piao; Hongfang Zhao; Su‐Jong Jeong; Xuhui Wang; Yann Vitasse; Philippe Ciais; Ivan A Janssens (Global Change Biology, 2014)
Heat requirement, expressed in growing degree days ( GDD ), is a widely used method to assess and predict the effect of temperature on plant development. Until recently, the analysis of spatial patterns of GDD requirement for spring vegetation green‐up onset was limited to local and regional scales, mainly because of the sparse and aggregated spatial availability of ground phenology data. Taking advantage of the large temporal and spatial scales of remote sensing‐based green‐up onset data, we studied the spatial patterns of GDD requirement for vegetation green‐up at northern middle and high latitudes. We further explored the correlations between GDD requirement for vegetation green‐up and previous winter season chilling temperatures and precipitation, using spatial partial correlations. We showed that GDD requirement for vegetation green‐up onset declines towards the north at a mean rate of 18.8 °C‐days per degree latitude between 35°N and 70°N, and vary significantly among different vegetation types. Our results confirmed that the GDD requirement for vegetation green‐up is negatively correlated with previous winter chilling, which was defined as the number of chilling days from the day when the land surface froze in the previous autumn to the day of green‐up onset. This negative correlation is a well‐known phenomenon from local studies. Interestingly, irrespective of the vegetation type, we also found a positive correlation between the GDD requirement and previous winter season precipitation, which was defined as the sum of the precipitation of the month when green‐up onset occur and the precipitation that occurred during the previous 2 months. Our study suggests that GDD requirement, chilling and precipitation may have complex interactions in their effects on spring vegetation green‐up phenology. These findings have important implications for improving phenology models and could therefore advance our understanding of the interplay between spring phenology and carbon fluxes.

The Development of Drug-Free Therapy for Prevention of Dental Caries - Fu Chen; Zhenshan Jia; Kelly C. Rice; Richard A. Reinhardt; Kenneth W. Bayles; Dong Wang (Pharmaceutical Research, 2014)

Viewer perspective in the mirroring of actions - Yan Fu; Elizabeth A. Franz (Experimental Brain Research, 2014)

Comparative responses of two dominant Antarctic phytoplankton taxa to interactions between ocean acidification, warming, irradiance, and iron availability - Kai Xu; Fei‐Xue Fu; David A. Hutchins (Limnology and Oceanography, 2014)
We investigated the responses of the ecologically dominant Antarctic phytoplankton species Phaeocystis antarctica (a prymnesiophyte) and Fragilariopsis cylindrus (a diatom) to a clustered matrix of three global change variables (CO 2 , mixed‐layer depth, and temperature) under both iron (Fe)‐replete and Fe‐limited conditions based roughly on the Intergovernmental Panel on Climate Change (IPCC) A2 scenario: (1) Current conditions, 39 Pa (380 ppmv) CO 2 , 50 µmol photons m −2 s −1 light, and 2°C; (2) Year 2060, 61 Pa (600 ppmv) CO 2 , 100 µmol photons m −2 s −1 light, and 4°C; (3) Year 2100, 81 Pa (800 ppmv) CO 2 , 150 µmol photons m −2 s −1 light, and 6°C. The combined interactive effects of these global change variables and changing Fe availability on growth, primary production, and cell morphology are species specific. A competition experiment suggested that future conditions could lead to a shift away from P. antarctica and toward diatoms such as F. cylindrus. Along with decreases in diatom cell size and shifts from prymnesiophyte colonies to single cells under the future scenario, this could potentially lead to decreased carbon export to the deep ocean. Fe : C uptake ratios of both species increased under future conditions, suggesting phytoplankton of the Southern Ocean will increase their Fe requirements relative to carbon fixation. The interactive effects of Fe, light, CO 2 , and temperature on Antarctic phytoplankton need to be considered when predicting the future responses of biology and biogeochemistry in this region.

Recent spring phenology shifts in western C entral E urope based on multiscale observations - Yongshuo H. Fu; Shilong Piao; Maarten Op de Beeck; Nan Cong; Hongfang Zhao; Yuan Zhang; Annette Menzel; Ivan A. Janssens (Global Ecology and Biogeography, 2014)
Aim Although numerous studies have reported advanced N orthern H emisphere spring phenology since the 1980s, recent studies based on remote sensing have reported a reversal or deceleration of this trend. This study aimed (1) to fully understand recent spring phenology shifts using both in situ observations and satellite‐based normalized difference vegetation index ( NDVI ) datasets, and (2) to test whether the NDVI methods capture the trends observed in situ. Location W estern C entral E urope. Methods Temporal spring phenology trends (leaf unfolding dates) were examined using 1,001,678 in situ observations of 31 plant species at 3984 stations, as well as NDVI ‐based start‐of‐season dates, obtained using five different methods, across the pixels that included the phenology stations. Results In situ and NDVI observations both indicated that spring phenology significantly advanced during the period 1982–2011 at an average rate of −0.45 days yr −1 . This trend was not uniform across the period and significantly weakened over the period 2000–2011. Furthermore, opposite trends were found between in situ and NDVI observations over the period 2000–2011. Averaged over all species, the in situ observations indicated a slower but still advancing trend for leaf unfolding, whereas the NDVI series showed a delayed spring phenology. Main conclusions The recent trend reversal in the advancement of spring phenology in western C entral E urope is likely to be related to the response of early spring species to the cooling trend in late winter. In contrast, late spring species continued to exhibit advanced leaf unfolding, which is consistent with the warming trend during spring months. Because remote sensing does not distinguish between species, the signal of growing‐season onset may only reflect the phenological dynamics of these earliest species in the pixel, even though most species still exhibit advancing trends.

Identification and characterization of trimethylamine N ‐oxide ( TMAO ) demethylase and TMAO permease in M ethylocella silvestris BL 2 - Yijun Zhu; Eleanor Jameson; Rosemary A. Parslow; Ian Lidbury; Tiantian Fu; Timothy R. Dafforn; Hendrik Schäfer; Yin Chen (Environmental Microbiology, 2014)
Summary M ethylocella silvestris , an alphaproteobacterium isolated from a forest soil, can grow on trimethylamine N ‐oxide ( TMAO ) as a sole nitrogen source; however, the molecular and biochemical mechanisms underpinning its growth remain unknown. Marker‐exchange mutagenesis enabled the identification of several genes involved in TMAO metabolism, including M sil_3606 , a permease of the amino acids‐polyamine ( APC ) superfamily, and M sil_3603 , consisting of an N ‐terminal domain of unknown function ( DUF 1989) and a C ‐terminal tetrahydrofolate‐binding domain. Null mutants of M sil_3603 and M sil_3606 can no longer grow on TMAO . Purified M sil_3603 from recombinant E scherichia coli can convert TMAO to dimethylamine and formaldehyde (1 TMAO → 1 dimethylamine + 1 formaldehyde), confirming that it encodes a bona fide TMAO demethylase ( T dm). T dm of M . silvestris and eukaryotic T dms have no sequence homology and contrasting characteristics. Recombinant T dm of M . silvestris appears to be hexameric, has a high affinity for TMAO ( K m = 3.3 mM ; V max = 21.7 nmol min −1 mg −1 ) and only catalyses demethylation of TMAO and a structural homologue, dimethyldodecylamine N ‐oxide. Our study has contributed to the understanding of the genetic and biochemical mechanisms for TMAO degradation in M . silvestris .

A promoter that drives gene expression preferentially in male transgenic rats - Qiling Li; Yamin Ma; Wenzhi Li; Wei Xu; Li Ma; Guoxing Fu; Xiaohua Tian; Yueling Wang; Xu Li; Tameka Bythwood; Jendai Richards; Mukaila A. Akinbami; et al. (Transgenic Research, 2014)

Next generation sequencing-based molecular diagnosis of retinitis pigmentosa: identification of a novel genotype-phenotype correlation and clinical refinements - Feng Wang; Hui Wang; Han-Fang Tuan; Duy H. Nguyen; Vincent Sun; Vafa Keser; Sara J. Bowne; Lori S. Sullivan; Hongrong Luo; Ling Zhao; Xia Wang; Jacques E. Zaneveld; et al. (Human Genetics, 2014)

The Detection of Inherent Homologous Recombination Between Repeat Sequences in H. pylori 26695 by the PCR-Based Method - Yajuan Fu; Reyna Cristina Zepeda-Gurrola; Germán Rubén Aguilar-Gutiérrez; Edgar E. Lara-Ramírez; Erick J. De Luna-Santillana; Isabel Cristina Rodríguez-Luna; Alejandro Sánchez-Varela; Ricardo Carreño-López; Víctor Ricardo Moreno-Medina; Mario A. Rodríguez-Pérez; Yolanda López-Vidal; Xianwu Guo (Current Microbiology, 2014)

Understanding Human–Landscape Interactions in the “Anthropocene” - Carol P. Harden; Anne Chin; Mary R. English; Rong Fu; Kathleen A. Galvin; Andrea K. Gerlak; Patricia F. McDowell; Dylan E. McNamara; Jeffrey M. Peterson; N. LeRoy Poff; Eugene A. Rosa; William D. Solecki; et al. (Environmental Management, 2014)

The Development of Dentotropic Micelles with Biodegradable Tooth-Binding Moieties - Fu Chen; Zhenshan Jia; Kelly C. Rice; Richard A. Reinhardt; Kenneth W. Bayles; Dong Wang (Pharmaceutical Research, 2013)

Genetic structure and association mapping of cold tolerance in improved japonica rice germplasm at the booting stage - Di Cui; Chang-ying Xu; Cui-feng Tang; Chun-gang Yang; Teng-qiong Yu; Xin-xiang A; Gui-lan Cao; Fu-rong Xu; Jun-guo Zhang; Long-zhi Han (Euphytica, 2013)

Isolation of Functional Human Endothelial Cells from Small Volumes of Umbilical Cord Blood - Sa Do Kang; Tim A. Carlon; Alexandra E. Jantzen; Fu-Hsiung Lin; Melissa M. Ley; Jason D. Allen; Thomas V. Stabler; N. Rebecca Haley; George A. Truskey; Hardean E. Achneck (Annals of Biomedical Engineering, 2013)

Console video games, postural activity, and motion sickness during passive restraint - Chih-Hui Chang; Wu-Wen Pan; Fu-Chen Chen; Thomas A. Stoffregen (Experimental Brain Research, 2013)

Erratum to: Dehydroascorbate reductase and glutathione reductase play an important role in scavenging hydrogen peroxide during natural and artificial dehydration of Jatropha curcas seeds - Samar A. Omar; Nabil I. Elsheery; Hazem M. Kalaji; Zeng-Fu Xu; Song-Quan Song; Robert Carperntier; Choon-Hwan Lee; Suleyman I. Allakverdiev (Journal of Plant Biology, 2013)

Colimitation of the unicellular photosynthetic diazotroph Crocosphaera watsonii by phosphorus, light, and carbon dioxide - Nathan S. Garcia; Fei-Xue Fu; David A. Hutchins (Limnology and Oceanography, 2013)
We describe interactive effects of total phosphorus (total P = 0.1–4.0 µmol L −1 ; added as H 2 NaPO 4 ), irradiance (40 and 150 µmol quanta m −2 s −1 ), and the partial pressure of carbon dioxide (; 19 and 81 Pa, i.e., 190 and 800 ppm) on growth and CO 2 ‐ and dinitrogen (N 2 )‐fixation rates of the unicellular N 2 ‐fixing cyanobacterium Crocosphaera watsonii (WH0003) isolated from the Pacific Ocean near Hawaii. In semicontinuous cultures of C. watsonii , elevated positively affected growth and CO 2 ‐ and N 2 ‐fixation rates under high light. Under low light, elevated positively affected growth rates at all concentrations of P, but CO 2 ‐ and N 2 ‐fixation rates were affected by elevated only when P was low. In both high‐light and low‐light cultures, the total P requirements for growth and CO 2 ‐ and N 2 ‐fixation declined as increased. The minimum concentration (C min ) of total P and half‐saturation constant (K ʽ ) for growth and CO 2 ‐ and N 2 ‐fixation rates with respect to total P were reduced by 0.05 µmol L −1 as a function of elevated . We speculate that low P requirements under high resulted from a lower energy demand associated with carbon‐concentrating mechanisms in comparison with low‐ cultures. There was also a 0.10 µmol L −1 increase in C min and K ʽ for growth and N 2 fixation with respect to total P as a function of increasing light regardless of concentration. We speculate that cellular P concentrations are responsible for this shift through biodilution of cellular P and possibly cellular P uptake systems as a function of increasing light. Changing concentrations of P, CO 2 , and light have both positive and negative interactive effects on growth and CO 2 ‐, and N 2 ‐fixation rates of unicellular oxygenic diazotrophs like C. watsonii .

The Effect of Stress-Induced Senescence on Aging Human Cord Blood-Derived Endothelial Cells - Tracy M. Cheung; Mansi P. Ganatra; Justin J. Fu; George A. Truskey (Cardiovascular Engineering and Technology, 2013)

Standardization of Switchgrass Sample Collection for Cell Wall and Biomass Trait Analysis - C. Frank Hardin; Chunxiang Fu; Hiroshi Hisano; Xirong Xiao; Hui Shen; C. Neal Stewart; Wayne Parrott; Richard A. Dixon; Zeng-Yu Wang (BioEnergy Research, 2013)

Three genetic systems controlling growth, development and productivity of rice (Oryza sativa L.): a reevaluation of the ‘Green Revolution’ - Fan Zhang; Yun-Zhu Jiang; Si-Bin Yu; J. Ali; A. H. Paterson; G. S. Khush; Jian-Long Xu; Yong-Ming Gao; Bin-Ying Fu; R. Lafitte; Zhi-Kang Li (Theoretical and Applied Genetics, 2013)

Scl gene construction, expression and effect on hemangioma - H. X. Yin; Z. H. Zhang; J. C. Shen; A. L. Zhang; T. Y. Zhang; J. X. Luo; C. Y. Fu; X. P. Yi; Z. W. Liu; S. S. Yang; B. Zhou; X. Fu (Molecular Biology Reports, 2013)

Tetracyclic spirooxindole blockers of hNaV1.7: activity in vitro and in CFA-induced inflammatory pain model - Sultan Chowdhury; Shifeng Liu; Jay A. Cadieux; Tom Hsieh; Mikhail Chafeev; Shaoyi Sun; Qi Jia; Jianyu Sun; Mark Wood; Jonathan Langille; Serguei Sviridov; Jianmin Fu; et al. (Medicinal Chemistry Research, 2013)

Origin of the Tongbai-Dabie-Sulu Neoproterozoic low-δ 18O igneous province, east-central China - Bin Fu; Noriko T. Kita; Simon A. Wilde; Xiaochun Liu; John Cliff; Alan Greig (Contributions to Mineralogy and Petrology, 2013)

Seedling growth and soil nutrient availability in exotic and native tree species: implications for afforestation in southern China - Faming Wang; Weixing Zhu; Bi Zou; Deborah A. Neher; Shenglei Fu; Hanping Xia; Zhian Li (Plant and Soil, 2013)

Risk factors for primary lung cancer among never smokers by gender in a matched case–control study - Yen-Li Lo; Chin-Fu Hsiao; Gee-Chen Chang; Ying-Huang Tsai; Ming-Shyan Huang; Wu-Chou Su; Yuh-Min Chen; Che-Wei Hsin; Chin-Hao Chang; Pan-Chyr Yang; Chien-Jen Chen; Chao A. Hsiung (Cancer Causes & Control, 2013)

Dehydroascorbate reductase and glutathione reductase play an important role in scavenging hydrogen peroxide during natural and artificial dehydration of Jatropha curcas seeds - Samar A. Omar; Nabil I. Elsheery; Hazem M. Kalaji; Zeng-Fu Xu; Song Song-Quan; Robert Carpentier; Choon-Hwan Lee; Suleyman I. Allakhverdiev (Journal of Plant Biology, 2012)

Prevention of Orthopedic Device-Associated Osteomyelitis Using Oxacillin-Containing Biomineral-Binding Liposomes - Xin-Ming Liu; Yijia Zhang; Fu Chen; Irine Khutsishvili; Edward V. Fehringer; Luis A. Marky; Kenneth W. Bayles; Dong Wang (Pharmaceutical Research, 2012)

Responses of soil microbial and nematode communities to aluminum toxicity in vegetated oil-shale-waste lands - Yuanhu Shao; Weixin Zhang; Zhanfeng Liu; Yuxin Sun; Dima Chen; Jianping Wu; Lixia Zhou; Hanping Xia; Deborah A. Neher; Shenglei Fu (Ecotoxicology, 2012)

Low BDNF is associated with cognitive impairment in chronic patients with schizophrenia - Xiang Yang Zhang; Jun Liang; Da Chun Chen; Mei Hong Xiu; Fu De Yang; Therese A. Kosten; Thomas R. Kosten (Psychopharmacology, 2012)

Timing of gold mineralisation in the western Lachlan Orogen, SE Australia: A critical overview - D. Phillips; B. Fu; C. J.L. Wilson; M. A. Kendrick; A. M. Fairmaid; J. MCL. Miller (Australian Journal of Earth Sciences, 2012)

Constitutive expression of barley α-amylase in Pichia pastoris by high-density cell culture - Z. W. Liu; H. X. Yin; X. P. Yi; A. L. Zhang; J. X. Luo; T. Y. Zhang; C. Y. Fu; Z. H. Zhang; J. C. Shen; L. P. Chen (Molecular Biology Reports, 2012)

Partial least squares regression, support vector machine regression, and transcriptome-based distances for prediction of maize hybrid performance with gene expression data - Junjie Fu; K. Christin Falke; Alexander Thiemann; Tobias A. Schrag; Albrecht E. Melchinger; Stefan Scholten; Matthias Frisch (Theoretical and Applied Genetics, 2012)

Fine mapping of 14q24.1 breast cancer susceptibility locus - Phoebe Lee; Yi-Ping Fu; Jonine D. Figueroa; Ludmila Prokunina-Olsson; Jesus Gonzalez-Bosquet; Peter Kraft; Zhaoming Wang; Kevin B. Jacobs; Meredith Yeager; Marie-Josèphe Horner; Susan E. Hankinson; Amy Hutchinson; et al. (Human Genetics, 2012)

New constraints on fluid sources in orogenic gold deposits, Victoria, Australia - Bin Fu; Mark A. Kendrick; Alison M. Fairmaid; David Phillips; Christopher J. L. Wilson; Terrence P. Mernagh (Contributions to Mineralogy and Petrology, 2012)

Bayesian calibration of the Unified budburst model in six temperate tree species - Yongshuo H. Fu; Matteo Campioli; Gaston Demarée; Alex Deckmyn; Rafiq Hamdi; Ivan A. Janssens; Gaby Deckmyn (International Journal of Biometeorology, 2012)

Erratum to: Effects of proNGF on Neuronal Viability, Neurite Growth and Amyloid-beta Metabolism - Yan-Jiang Wang; Deborah Valadares; Ying Sun; Xin Wang; Jin-Hua Zhong; Xiao-Hong Liu; Shohreh Majd; Li Chen; Chang-Yue Gao; Si Chen; Yoon Lim; Anthony Pollard; et al. (Neurotoxicity Research, 2011)

Portal protein diversity and phage ecology - Matthew B. Sullivan; Maureen L. Coleman; Vanessa Quinlivan; Jessica E. Rosenkrantz; Alicia S. DeFrancesco; G. Tan; Ross Fu; Jessica A. Lee; John B. Waterbury; Joseph P. Bielawski; Sallie W. Chisholm (Environmental Microbiology, 2011)

Changes in cloudiness over the Amazon rainforests during the last two decades: diagnostic and potential causes - Paola A. Arias; Rong Fu; Carlos D. Hoyos; Wenhong Li; Liming Zhou (Climate Dynamics, 2011)

Downregulation of Cinnamyl Alcohol Dehydrogenase (CAD) Leads to Improved Saccharification Efficiency in Switchgrass - Chunxiang Fu; Xirong Xiao; Yajun Xi; Yaxin Ge; Fang Chen; Joseph Bouton; Richard A. Dixon; Zeng-Yu Wang (BioEnergy Research, 2011)

Experimental Studies and Modeling of Drug Release from a Tunable Affinity-Based Drug Delivery Platform - Andrew S. Fu; Thimma R. Thatiparti; Gerald M. Saidel; Horst A. von Recum (Annals of Biomedical Engineering, 2011)

Inactivation of a centromere during the formation of a translocation in maize - Zhi Gao; Shulan Fu; Qianhua Dong; Fangpu Han; James A. Birchler (Chromosome Research, 2011)

Activation of group IVC phospholipase A2 by polycyclic aromatic hydrocarbons induces apoptosis of human coronary artery endothelial cells - Patricia K. Tithof; Sean M. Richards; Mona A. Elgayyar; Fu-Minn Menn; Vijay M. Vulava; Larry McKay; John Sanseverino; Gary Sayler; Dawn E. Tucker; Christina C. Leslie; Kim P. Lu; Kenneth S. Ramos (Archives of Toxicology, 2011)

Effects of changing p CO 2 and phosphate availability on domoic acid production and physiology of the marine harmful bloom diatom Pseudo‐nitzschia multiseries - Jun Sun; David A. Hutchins; Yuanyuan Feng; Erica L. Seubert; David A. Caron; Fei-Xue Fu (Limnology and Oceanography, 2011)
Some members of the diatom genus Pseudo‐nitzschia produce the toxin domoic acid (DA), which through trophic transfer causes mass mortalities of wildlife, shellfish harvesting closures, and risks to human health. Nutrient and micronutrient limitation have been shown to regulate DA production. This study tested the hypothesis that changing partial pressure of CO 2 ( p CO 2 ) can interact with nutrient limitation to help determine cellular DA levels, an environmentally relevant issue in light of current increases in atmospheric p CO 2 . Cultures of the toxic species Pseudo‐nitzschia multiseries were incubated using semicontinuous methods under a matrix of three p CO 2 conditions: ∼ 22 Pa (220 ppm), ∼ 41 Pa (400 ppm), and ~ 74 Pa (730 ppm), and two phosphate concentrations: 20 μmol L −1 , P‐replete; and 0.5 μmol L −1 , P‐limited. DA production was regulated by both p CO 2 and phosphate availability. DA concentrations were 30–50 times higher in P‐limited cultures compared to P‐replete ones, at the same p CO 2 levels. Increasing CO 2 levels stimulated DA production under both nutrient conditions, but especially in P‐limited cultures, where DA levels increased approximately four times over the p CO 2 range examined. Growth rates, primary productivity, photosynthesis vs. irradiance parameters, and cellular elemental ratios also responded interactively to the availability of both CO 2 and phosphate. Our results raise the possibility that growth rates and toxicity of the diatom Pseudo‐nitzschia multiseries could increase substantially in the future high‐CO 2 ocean, suggesting a potentially escalating negative effect of this harmful algal bloom species on the future marine environment.

Saturnispora serradocipensis sp. nov. and Saturnispora gosingensis sp. nov., two ascomycetous yeasts from ephemeral habitats - Monica R. Canelhas; Anne C. Barbosa; Adriana O. Medeiros; Ching-Fu Lee; Li-Yin Huang; Marc-André Lachance; Carlos A. Rosa (Antonie van Leeuwenhoek, 2011)

Mechanisms for phenotypic variation in Lesch–Nyhan disease and its variants - Radhika Sampat; Rong Fu; Laura E. Larovere; Rosa J. Torres; Irene Ceballos-Picot; Michel Fischbach; Raquel de Kremer; David J. Schretlen; Juan Garcia Puig; H. A. Jinnah (Human Genetics, 2011)

Triclosan-Loaded Tooth-Binding Micelles for Prevention and Treatment of Dental Biofilm - Fu Chen; Kelly C. Rice; Xin-Ming Liu; Richard A. Reinhardt; Kenneth W. Bayles; Dong Wang (Pharmaceutical Research, 2010)

Nicotine dependence and serum BDNF levels in male patients with schizophrenia - Xiang Yang Zhang; Mei Hong Xiu; Da Chun Chen; Fu De Yang; Gui Ying Wu; Lin Lu; Therese A. Kosten; Thomas R. Kosten (Psychopharmacology, 2010)

How are seasonal prediction skills related to models’ performance on mean state and annual cycle? - June-Yi Lee; Bin Wang; I.-S. Kang; J. Shukla; A. Kumar; J.-S. Kug; J. K. E. Schemm; J.-J. Luo; T. Yamagata; X. Fu; O. Alves; B. Stern; et al. (Climate Dynamics, 2010)

Relative competitive abilities and productivity in Ginkgo and broad bean and wheat mixtures in southern China - Fu-liang Cao; J. P. Kimmins; P. A. Jolliffe; J. R. Wang (Agroforestry Systems, 2010)

Dietary flexibility aids Asian earthworm invasion in North American forests - Weixin Zhang; Paul F. Hendrix; Bruce A. Snyder; Marirosa Molina; Jianxiong Li; Xingquan Rao; Evan Siemann; Shenglei Fu (Ecology, 2010)
On a local scale, invasiveness of introduced species and invasibility of habitats together determine invasion success. A key issue in invasion ecology has been how to quantify the contribution of species invasiveness and habitat invasibility separately. Conventional approaches, such as comparing the differences in traits and/or impacts of species between native and/or invaded ranges, do not determine the extent to which the performance of invaders is due to either the effects of species traits or habitat characteristics. Here we explore the interaction between two of the most widespread earthworm invaders in the world (Asian Amynthas agrestis and European Lumbricus rubellus ) and study the effects of species invasiveness and habitat invasibility separately through an alternative approach of “third habitat” in Tennessee, USA. We propose that feeding behaviors of earthworms will be critical to invasion success because trophic ecology of invasive animals plays a key role in the invasion process. We found that (1) the biomass and isotopic abundances (δ 13 C and δ 15 N) of A. agrestis were not impacted by either direct effects of L. rubellus competition or indirect effects of L. rubellus ‐preconditioned habitat; (2) A. agrestis disrupted the relationship between L. rubellus and soil microorganisms and consequently hindered litter consumption by L. rubellus ; and (3) compared to L. rubellus , A. agrestis shifted its diet more readily to consume more litter, more soil gram‐positive (G+) bacteria (which may be important for litter digestion), and more non‐microbial soil fauna when soil microorganisms were depleted. In conclusion, A. agrestis showed strong invasiveness through its dietary flexibility through diet shifting and superior feeding behavior and its indirectly negative effect of habitat invasibility on L. rubellus via changes in the soil microorganism community. In such context, our results expand on the resource fluctuation hypothesis and support the superior competitor hypothesis. This work presents additional approaches in invasion ecology, provides some new dimensions for further research, and contributes to a greater understanding of the importance of interactions between multiple invading species.

Effect of Dietary Polyphenon E and EGCG on Lung Tumorigenesis in A/J Mice - Qi Zhang; Huijing Fu; Jing Pan; Jun He; Seto Ryota; Yukihiko Hara; Yian Wang; Ronald A Lubet; Ming You (Pharmaceutical Research, 2010)

Characterization of microsatellite DNA markers in the Emei moustache toads (Leptobrachium boringii) - Ke Bi; Duncan Deng; M. Kathrine A. Crosby; Jinzhong Fu (Conservation Genetics, 2010)

Chromosomal evolution of Arvicolinae (Cricetidae, Rodentia). III. Karyotype relationships of ten Microtus species - Natalia A. Lemskaya; Svetlana A. Romanenko; Feodor N. Golenishchev; Nadezhda V. Rubtsova; Olga V. Sablina; Natalya A. Serdukova; Patricia C. M. O’Brien; Beiyuan Fu; Nuri Yiğit; Malcolm A. Ferguson-Smith; Fengtang Yang; Alexander S. Graphodatsky (Chromosome Research, 2010)

Development of delivery methods for carbohydrate-based drugs: controlled release of biologically-active short chain fatty acid-hexosamine analogs - Udayanath Aich; M. Adam Meledeo; Srinivasa-Gopalan Sampathkumar; Jie Fu; Mark B. Jones; Christopher A. Weier; Sung Yun Chung; Benjamin C. Tang; Ming Yang; Justin Hanes; Kevin J. Yarema (Glycoconjugate Journal, 2010)

Environmental control of open‐ocean phytoplankton groups: Now and in the future - Philip W. Boyd; Robert Strzepek; Feixue Fu; David A. Hutchins (Limnology and Oceanography, 2010)
Climate change will alter concurrently many environmental factors that exert control over oceanic phytoplankton. Recent laboratory culture work, shipboard experiments, and field surveys reveal many remaining unknowns about the bottom‐up controls for five globally important algal groups. Increasing uncertainties exist, respectively, for picocyanobacteria, diatoms, Phaeocystis spp., N 2 ‐fixing cyanobacteria, and coccolithophores. This missing information about current environmental controls will hinder progress in modeling how these phytoplankton will be influenced by climate change. A review of conceptual approaches used to elucidate the relationship between environmental controls and phytoplankton dominance, from Margalef's mandala to functional traits, uncovered limitations regarding their application to climate‐change scenarios. For example, these previous approaches have insufficient scope or dimensions to take into account the confounding effects of synergistic and antagonistic interactions of multiple environmental change variables. A new approach is needed that considers all of the different environmental properties altered by climate change and their interactions while at the same time permitting a subset of the most significant controls for a specific phytoplankton group to be isolated and evaluated in factorial matrix perturbation experiments. We advocate three new interlinked approaches, including environmental clusters that incorporate all factors (temperature, CO 2 , light, nutrients, and trace metals), which both exert control over present‐day floristics and will be altered by climate change. By carefully linking a holistic conceptual approach to a reductionist experimental design, the future responses of open‐ocean phytoplankton groups to a complex, rapidly changing environment can be better predicted.

Transcriptome-based distance measures for grouping of germplasm and prediction of hybrid performance in maize - Matthias Frisch; Alexander Thiemann; Junjie Fu; Tobias A. Schrag; Stefan Scholten; Albrecht E. Melchinger (Theoretical and Applied Genetics, 2010)

Correlation between parental transcriptome and field data for the characterization of heterosis in Zea mays L. - Alexander Thiemann; Junjie Fu; Tobias A. Schrag; Albrecht E. Melchinger; Matthias Frisch; Stefan Scholten (Theoretical and Applied Genetics, 2010)

The effect of habitat fragmentation on finescale population structure of wood frogs (Rana sylvatica) - M. Kathrine A. Crosby; Lawrence E. Licht; Jinzhong Fu (Conservation Genetics, 2009)

Effect of polymorphism in the leukemia inhibitory factor gene on litter size in Large White pigs - H. C. Lin; G. F. Liu; A. G. Wang; L. J. Kong; X. F. Wang; J. L. Fu (Molecular Biology Reports, 2009)

Advance and prospectus of seasonal prediction: assessment of the APCC/CliPAS 14-model ensemble retrospective seasonal prediction (1980–2004) - Bin Wang; June-Yi Lee; In-Sik Kang; J. Shukla; C.-K. Park; A. Kumar; J. Schemm; S. Cocke; J.-S. Kug; J.-J. Luo; T. Zhou; B. Wang; et al. (Climate Dynamics, 2009)

Avian comparative genomics: reciprocal chromosome painting between domestic chicken (Gallus gallus) and the stone curlew (Burhinus oedicnemus, Charadriiformes)—An atypical species with low diploid number - Wenhui Nie; Patricia C. M. O’Brien; Bee L. Ng; Beiyuan Fu; Vitaly Volobouev; Nigel P. Carter; Malcolm A. Ferguson-Smith; Fengtang Yang (Chromosome Research, 2009)

PPARγ ligands, rosiglitazone and pioglitazone, inhibit bFGF- and VEGF-mediated angiogenesis - Ahmad Aljada; Laura O’Connor; Yu-Yen Fu; Shaker A. Mousa (Angiogenesis, 2008)

Structural basis for executioner caspase recognition of P5 position in substrates - Guoxing Fu; Alexander A. Chumanevich; Johnson Agniswamy; Bin Fang; Robert W. Harrison; Irene T. Weber (Apoptosis, 2008)

Interactions between changing pCO2, N2 fixation, and Fe limitation in the marine unicellular cyanobacterium Crocosphaera - Fei-Xue Fu; Margaret R. Mulholland; Nathan S. Garcia; Aaron Beck; Peter W. Bernhardt; Mark E. Warner; Sergio A. Sañudo-Wilhelmy; David A. Hutchins (Limnology and Oceanography, 2008)
We examined the physiological responses of steady‐state iron (Fe)‐replete and Fe‐limited cultures of the biogeochemically critical marine unicellular diazotrophic cyanobacterium Crocosphaera at glacial (19 Pa; 190 ppm), current (39 Pa; 380 ppm), and projected year 2100 (76 Pa; 750 ppm) CO 2 levels. Rates of N 2 and CO 2 fixation and growth increased in step with increasing partial pressure of CO 2 (pCO 2 ), but only under Fe‐replete conditions. N 2 and carbon fixation rates at 75 Pa CO 2 were 1.4‐1.8‐fold and 1.2‐2.0‐fold higher, respectively, relative to those at present day and glacial pCO 2 levels. In Fe‐replete cultures, cellular Fe and molybdenum quotas varied threefold and were linearly related to N 2 fixation rates and to external pCO 2 . However, N 2 fixation and trace metal quotas were decoupled from pCO 2 in Fe‐limited Crocosphaera . Higher CO 2 and Fe concentrations both resulted in increased cellular pigment contents and affected photosynthesis vs. irradiance parameters. If these results also apply to natural Crocosphaera populations, anthropogenic CO 2 enrichment could substantially increase global oceanic N 2 and CO 2 fixation, but this effect may be tempered by Fe availability. Possible biogeochemical consequences may include elevated inputs of new nitrogen to the ocean and increased potential for Fe and/or phosphorus limitation in the future high‐CO 2 ocean, and feedbacks to atmospheric pCO 2 in both the near future and over glacial to interglacial timescales.

Portal protein diversity and phage ecology - Matthew B. Sullivan; Maureen L. Coleman; Vanessa Quinlivan; Jessica E. Rosenkrantz; Alicia S. DeFrancesco; G. Tan; Ross Fu; Jessica A. Lee; John B. Waterbury; Joseph P. Bielawski; Sallie W. Chisholm (Environmental Microbiology, 2008)
Summary Oceanic phages are critical components of the global ecosystem, where they play a role in microbial mortality and evolution. Our understanding of phage diversity is greatly limited by the lack of useful genetic diversity measures. Previous studies, focusing on myophages that infect the marine cyanobacterium Synechococcus , have used the coliphage T4 portal‐protein‐encoding homologue, gene 20 ( g20 ), as a diversity marker. These studies revealed 10 sequence clusters, 9 oceanic and 1 freshwater, where only 3 contained cultured representatives. We sequenced g20 from 38 marine myophages isolated using a diversity of Synechococcus and Prochlorococcus hosts to see if any would fall into the clusters that lacked cultured representatives. On the contrary, all fell into the three clusters that already contained sequences from cultured phages. Further, there was no obvious relationship between host of isolation, or host range, and g20 sequence similarity. We next expanded our analyses to all available g20 sequences (769 sequences), which include PCR amplicons from wild uncultured phages, non‐PCR amplified sequences identified in the Global Ocean Survey (GOS) metagenomic database, as well as sequences from cultured phages, to evaluate the relationship between g20 sequence clusters and habitat features from which the phage sequences were isolated. Even in this meta‐data set, very few sequences fell into the sequence clusters without cultured representatives, suggesting that the latter are very rare, or sequencing artefacts. In contrast, sequences most similar to the culture‐containing clusters, the freshwater cluster and two novel clusters, were more highly represented, with one particular culture‐containing cluster representing the dominant g20 genotype in the unamplified GOS sequence data. Finally, while some g20 sequences were non‐randomly distributed with respect to habitat, there were always numerous exceptions to general patterns, indicating that phage portal proteins are not good predictors of a phage's host or the habitat in which a particular phage may thrive.

Ti-in-zircon thermometry: applications and limitations - Bin Fu; F. Zeb Page; Aaron J. Cavosie; John Fournelle; Noriko T. Kita; Jade Star Lackey; Simon A. Wilde; John W. Valley (Contributions to Mineralogy and Petrology, 2008)

One new cinnamic imide dervative from the fruits of Tribulus terrestris - A-Li Lv; Nan Zhang; Min-Ge Sun; Yong-Fu Huang; Yi Sun; Hong-Yu Ma; Hui-Ming Hua; Yue-Hu Pei (Natural Product Research, 2008)

Radiation-Guided P-Selectin Antibody Targeted to Lung Cancer - G. Hariri; Y. Zhang; A. Fu; Z. Han; M. Brechbiel; M. N. Tantawy; T. E. Peterson; R. Mernaugh; D. Hallahan (Annals of Biomedical Engineering, 2008)

Hypoxia-induced compensatory effect as related to Shh and HIF-1α in ischemia embryo rat heart - Jin-Ming Hwang; Yi-Jiun Weng; James A. Lin; Da-Tian Bau; Fu-Yang Ko; Fuu-Jen Tsai; Chang-Hai Tsai; Chieh-Hsi Wu; Pei-Cheng Lin; Chih-Yang Huang; Wei-Wen Kuo (Molecular and Cellular Biochemistry, 2008)

Multidirectional cross-species painting illuminates the history of karyotypic evolution in Perissodactyla - Vladimir A. Trifonov; Roscoe Stanyon; Anastasia I. Nesterenko; Beiyuan Fu; Polina L. Perelman; Patricia C M O’Brien; Gary Stone; Nadezhda V. Rubtsova; Marlys L. Houck; Terence J. Robinson; Malcolm A. Ferguson-Smith; Gauthier Dobigny; et al. (Chromosome Research, 2008)

Response of Brassica napus and B. juncea germplasm from Australia, China and India to Australian populations of Leptosphaeria maculans - C. X. Li; N. Wratten; P. A. Salisbury; W. A. Burton; T. D. Potter; G. Walton; Hua Li; K. Sivasithamparam; Surinder S. Banga; Shashi Banga; D. Singh; S. Y. Liu; et al. (Australasian Plant Pathology, 2008)

Disarming and sequencing of Agrobacterium rhizogenes strain K599 (NCPPB2659) plasmid pRi2659 - S. Luke Mankin; D. Steven Hill; Paula M. Olhoft; Effie Toren; Allan R. Wenck; Lawrence Nea; Liqun Xing; Jeffrey A. Brown; Huihua Fu; Lesley Ireland; Hongmei Jia; Helke Hillebrand; et al. (In Vitro Cellular & Developmental Biology - Plant, 2007)

Physcomitrella patens arabinogalactan proteins contain abundant terminal 3-O-methyl-l-rhamnosyl residues not found in angiosperms - Hu Fu; Madhav P. Yadav; Eugene A. Nothnagel (Planta, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

CO 2 control of Trichodesmium N 2 fixation, photosynthesis, growth rates, and elemental ratios: Implications for past, present, and future ocean biogeochemistry - D. A. Hutchins; F.-X. Fu; Y. Zhang; M. E. Warner; Y. Feng; K. Portune; P. W. Bernhardt; M. R. Mulholland (Limnology and Oceanography, 2007)
Diazotrophic marine cyanobacteria in the genus Trichodesmium contribute a large fraction of the new nitrogen entering the oligotrophic oceans, but little is known about how they respond to shifts in global change variables such as carbon dioxide (CO 2 ) and temperature. We compared Trichodesmium dinitrogen (N 2 ) and CO 2 fixation rates during steady‐state growth under past, current, and future CO 2 scenarios, and at two relevant temperatures. At projected CO 2 levels of year 2100 (76 Pa, 750 ppm), N 2 fixation rates of Pacific and Atlantic isolates increased 35–100%, and CO 2 fixation rates increased 15‐128% relative to present day CO 2 conditions (39 Pa, 380 ppm). CO 2 ‐mediated rate increases were of similar relative magnitude in both phosphorus (P)‐replete and P‐limited cultures, suggesting that this effect may be independent of resource limitation. Neither isolate could grow at 15 Pa (150 ppm) CO 2 , but N 2 and CO 2 fixation rates, growth rates, and nitrogen : phosophorus (N : P) ratios all increased significantly between 39 Pa and 152 Pa (1500 ppm). In contrast, these parameters were affected only minimally or not at all by a 4°C temperature change. Photosynthesis versus irradiance parameters, however, responded to both CO 2 and temperature but in different ways for each isolate. These results suggest that by the end of this century, elevated CO 2 could substantially increase global Trichodesmium N 2 and CO 2 fixation, fundamentally altering the current marine N and C cycles and potentially driving some oceanic regimes towards P limitation. CO 2 limitation of Trichodesmium diazotrophy during past glacial periods could also have contributed to setting minimum atmospheric CO 2 levels through downregulation of the biological pump. The relationship between marine N 2 fixation and atmospheric CO 2 concentration appears to be more complex than previously realized and needs to be considered in the context of the rapidly changing oligotrophic oceans.

Cross-species chromosome painting among camel, cattle, pig and human: further insights into the putative Cetartiodactyla ancestral karyotype - Gabriel Balmus; Vladimir A. Trifonov; Larisa S. Biltueva; Patricia C.M. O’Brien; Elena S. Alkalaeva; Beiyuan Fu; Julian A. Skidmore; Twink Allen; Alexander S. Graphodatsky; Fengtang Yang; Malcolm A. Ferguson-Smith (Chromosome Research, 2007)

Chromosomal evolution of Arvicolinae (Cricetidae, Rodentia). I. The genome homology of tundra vole, field vole, mouse and golden hamster revealed by comparative chromosome painting - Natalia A. Sitnikova; Svetlana A. Romanenko; Patricia C. M. O’Brien; Polina L. Perelman; Beiyuan Fu; Nadezhda V. Rubtsova; Natalya A. Serdukova; Feodor N. Golenishchev; Vladimir A. Trifonov; Malcolm A. Ferguson-Smith; Fengtang Yang; Alexander S. Graphodatsky (Chromosome Research, 2007)

The Heilongjiang Group: A Jurassic accretionary complex in the Jiamusi Massif at the western Pacific margin of northeastern China - Fu‐Yuan Wu; Jin‐Hui Yang; Ching‐Hua Lo; Simon A. Wilde; De‐You Sun; Bor‐Ming Jahn (Island Arc, 2007)
The tectonic setting of the Eastern Asian continental margin in the Jurassic is highly controversial. In the current study, we have selected the Heilongjiang complex located at the western margin of the Jiamusi Massif in northeastern China for geochronological investigation to address this issue. Field and petrographic investigations indicate that the Heilongjiang complex is composed predominately of granitic gneiss, marble, mafic‐ultramafic rocks, blueschist, greenschist, quartzite, muscovite‐albite schist and two‐mica schist that were tectonically interleaved, indicating they represent a mélange. The marble, two‐mica schist and granitic gneiss were most probably derived from the Mashan complex, a high‐grade gneiss complex in the Jiamusi Massif with which the Heilongjiang Group is intimately associated. The ultramafic rocks, blueschist, greenschist and quartzite (chert) are similar to components in ophiolite. The sensitive high mass‐resolution ion microprobe U‐Pb zircon age of 265 ± 4 Ma for the granitic gneiss indicates that the protolith granite was emplaced coevally with Permian batholiths in the Jiamusi Massif. 40 Ar/ 39 Ar dating of biotite and phengite from the granitic gneiss and mica schist yields a late Early Jurassic metamorphic age between 184 and 174 Ma. Early components of the Jiamusi Massif, including the Mashan complex, probably formed part of an exotic block from Gondwana, affected by late Pan‐African orogenesis, and collided with the Asian continental margin during the Early Jurassic. Subduction of oceanic crust between the Jiamusi block and the eastern part of the Central Asian Orogenic Belt resulted in the formation of a huge volume of Jurassic granites in the Zhangguangcai Range. Consequently, the collision of the Jiamusi Massif with the Central Asian Orogenic Belt to the west can be considered as the result of circum‐Pacific accretion, unrelated to the Central Asian Orogenic Belt. The widespread development of Jurassic accretionary complexes along the Asian continental margin supports such an interpretation.

Patterns of EphA2 protein expression in primary and metastatic pancreatic carcinoma and correlation with genetic status - Shiyama V. Mudali; Baojin Fu; Sindhu S. Lakkur; Mingde Luo; Erlinda E. Embuscado; Christine A. Iacobuzio-Donahue (Clinical & Experimental Metastasis, 2007)

Tracing magma mixing in granite genesis: in situ U–Pb dating and Hf-isotope analysis of zircons - Jin-Hui Yang; Fu-Yuan Wu; Simon A. Wilde; Lie-Wen Xie; Yue-Heng Yang; Xiao-Ming Liu (Contributions to Mineralogy and Petrology, 2006)

Successful implantation of intravenously administered stem cells correlates with severity of inflammation in murine myocarditis - Sohail Malek; Emel Kaplan; Ju-Feng Wang; Qingen Ke; Jamal S. Rana; Yu Chen; Bilal G. Rahim; Ma Li; Qin Huang; Yong-Fu Xiao; Freek W. A. Verheugt; James P. Morgan; et al. (Pflügers Archiv - European Journal of Physiology, 2006)

Comparative genome maps of the pangolin, hedgehog, sloth, anteater and human revealed by cross-species chromosome painting: further insight into the ancestral karyotype and genome evolution of eutherian mammals - Fengtang Yang; Alexander S. Graphodatsky; Tangliang Li; Beiyuan Fu; Gauthier Dobigny; Jinghuan Wang; Polina L. Perelman; Natalya A. Serdukova; Weiting Su; Patricia CM O'Brien; Yingxiang Wang; Malcolm A. Ferguson-Smith; et al. (Chromosome Research, 2006)

Targeting xa13, a recessive gene for bacterial blight resistance in rice - Zhaohui Chu; Binying Fu; Hong Yang; Caiguo Xu; Zhikang Li; A. Sanchez; Y. J. Park; J. L. Bennetzen; Qifa Zhang; Shiping Wang (Theoretical and Applied Genetics, 2006)

A Modified Cyclic Cracking Model for RC Structural Walls Behaviour Under Dynamic Excitation - Tsai-Fu Chuang; Andrew H. C. Chan; Les A. Clark (Bulletin of Earthquake Engineering, 2005)

Evaluation of five ab initio gene prediction programs for the discovery of maize genes - Hong Yao; Ling Guo; Yan Fu; Lisa A. Borsuk; Tsui-Jung Wen; David S. Skibbe; Xiangqin Cui; Brian E. Scheffler; Jun Cao; Scott J. Emrich; Daniel A. Ashlock; Patrick S. Schnable (Plant Molecular Biology, 2005)

Simulation Studies of High-Latitude Magnetospheric Boundary Dynamics - Q. Q. Shi; Z. Y. Pu; H. Zhang; S. Y. Fu; C. J. Xiao; Q. -G. Zong; T. A. Fritz; Z. X. Liu (Surveys in Geophysics, 2005)

Energetic Particles Observed in the CUSP Region During a Storm Recovery Phase - S. Y. Fu; Q. G. Zong; Z. Y. Pu; C. J. Xiao; A. Korth; P. Daly; H. Reme (Surveys in Geophysics, 2005)

Multiple Flux Rope Events at the High-Latitude Magnetopause: Cluster/Rapid Observation on 26 January, 2001 - Z. Y. Pu; Q. -G. Zong; T. A. Fritz; C. J. Xiao; Z. Y. Huang; S. Y. Fu; Q. Q. Shi; M. W. Dunlop; K. -H. Glassmeier; A. Balogh; P. Daly; H. Reme; et al. (Surveys in Geophysics, 2005)

Laboratory culture studies of Trichodesmium isolated from the Great Barrier Reef Lagoon, Australia - Peter R. F. Bell; Philippa J. R. Uwins; Ibrahim Elmetri; Julie A. Phillips; Fei-Xue Fu; Anya J.E. Yago (Hydrobiologia, 2005)

Kokchetavite: a new potassium-feldspar polymorph from the Kokchetav ultrahigh-pressure terrane - Shyh-Lung Hwang; Pouyan Shen; Hao-Tsu Chu; Tzen-Fu Yui; Juhn G. Liou; Nikolay V. Sobolev; Ru-Yuan Zhang; Vladislav S. Shatsky; Anton A. Zayachkovsky (Contributions to Mineralogy and Petrology, 2004)

Amazonian climate: results and future research - J. H. C. Gash; C. Huntingford; J. A. Marengo; R. A. Betts; P. M. Cox; G. Fisch; R. Fu; A. W. Gandu; P. P. Harris; L. A. T. Machado; C. von Randow; M. A. Silva Dias (Theoretical and Applied Climatology, 2004)

Evolution of Genome Organizations of Squirrels (Sciuridae) Revealed by Cross-Species Chromosome Painting - Tangliang Li; Patricia C. M. O'Brien; Larisa Biltueva; Beiyuan Fu; Jinhuan Wang; Wenhui Nie; Malcolm A. Ferguson-Smith; Alexander S. Graphodatsky; Fengtang Yang (Chromosome Research, 2004)

Segmental nerve conduction velocity in vibration-exposed shipyard workers - M. Cherniack; A. J. Brammer; R. Lundstrom; J. Meyer; T. F. Morse; G. Nealy; T. Nilsson; D. Peterson; E. Toppilla; N. Warren; R. W. Fu; H. Bruneau (International Archives of Occupational and Environmental Health, 2004)

Refined genome-wide comparative map of the domestic horse, donkey and human based on cross-species chromosome painting: insight into the occasional fertility of mules - Fengtang Yang; Beiyuan Fu; Patricia C. M. O'Brien; Wenhui Nie; Oliver A. Ryder; Malcolm A. Ferguson-Smith (Chromosome Research, 2004)

Spontaneous clearance of high-titer serum HBV DNA and risk of hepatocellular carcinoma in a Chinese population - Rebecca A. Harris; Gang Chen; Wen Yao Lin; Fu Min Shen; W. Thomas London; Alison A. Evans (Cancer Causes & Control, 2003)

Insulin 3: From chemical synthesis to biological function - Ping Fu; Ross A. D. Bathgate; Geoffrey W. Tregear; John D. Wade (International Journal of Peptide Research and Therapeutics, 2003)

Second primary tumors in patients with upper aerodigestive tract cancers: joint effects of smoking and alcohol (United States) - Kim-Anh Do; Marcella M. Johnson; Dorota A. Doherty; J. Jack Lee; Xi Feng Wu; Qiong Dong; Waun K. Hong; Fadlo R. Khuri; Karen K. Fu; Margaret R. Spitz (Cancer Causes & Control, 2003)

Suppression of multipath and jamming signals by digital beamforming for GPS/Galileo applications - Z. Fu; A. Hornbostel; J. Hammesfahr; A. Konovaltsev (GPS Solutions, 2003)

Phylogenetics of rat inbred strains - Michael A. Thomas; Chin-Fu Chen; Michael I. Jensen-Seaman; Peter J. Tonellato; Simon N. Twigger (Mammalian Genome, 2003)

Parameterization of effective ice particle size for high‐latitude clouds - Faisal S. Boudala; George A. Isaac; Qiang Fu; Stewart G. Cober (International Journal of Climatology, 2002)
A parameterization has been developed for mean effective size D ge in terms of ice water content (IWC) and temperature using in situ measurements of ice crystal spectra, cloud particle shapes and particle cross‐sectional area A from four research projects conducted in latitudes north of 45° N. The cloud microphysical measurements were made using PMS 2D optical probes, a PMS forward scattering spectrometer probe (FSSP), and Nevzorov total water and liquid water content probes. The IWCs derived from particle spectra using three different methods were compared with IWC measured with the Nevzorov probe (IWC Nev ). The contribution of small particles to the total mass was estimated by integrating a gamma distribution function that was fitted to match the measured FSSP concentrations. The D ge was calculated from the derived IWC and total cross‐sectional area per unit volume A c . This analysis indicates that there are significant differences among the schemes used to derive the IWC. It was found that the IWC derived based on the Cunningham scheme and IWC Nev have the highest correlation: r 2 = 0.78. After considering small particles, the derived IWC almost matched the IWC Nev . The average estimated contribution of small particles to the A c was 43%. The average estimated contribution of small particles to the total IWC, however, was 20%. Since D ge is directly proportional to the ratio IWC/ A c , the addition of small particles reduced the derived D ge considerably. The largest changes in D ge associated with small particles, however, occur at the coldest temperature and at low IWC, reaching up to 45% for temperatures less than −25° C. Generally, D ge and IWC increase with increasing temperature. Good agreement between the parameterized D ge and derived D ge from measurements were found when small particles were included. Copyright © 2002 Royal Meteorological Society.

The genome phylogeny of domestic cat, red panda and five mustelid species revealed by comparative chromosome painting and G-banding - Wenhui Nie; Jinhuan Wang; Patricia C.M. O'Brien; Beiyuan Fu; Tian Ying; Malcolm A. Ferguson-Smith; Fengtang Yang (Chromosome Research, 2002)

Transgenic rice as a system to study the stability of transgene expression: multiple heterologous transgenes show similar behaviour in diverse genetic backgrounds - D. Gahakwa; S. B. Maqbool; X. Fu; D. Sudhakar; P. Christou; A. Kohli (Theoretical and Applied Genetics, 2000)

Inhibition of B16BL6 melanoma invasion by tyrosine and phenylalanine deprivation is associated with decreased secretion of plasminogen activators and increased plasminogen activator inhibitors - Bertha A. Pelayo; Ya-Min Fu; Gary G. Meadows (Clinical & Experimental Metastasis, 1999)

Relative Lymphocytosis-Disorder Caused by Occupational Exposure to Vinyl Chloride Monomer - A. Fu ) i '; Z. x pacir; D. Barkovi '; A. Jazbec; A. Miji '; B. Labar (Bulletin of Environmental Contamination and Toxicology, 1998)

Use of alternate splice sites in granule-bound starch synthase mRNA from low-amylose rice varieties - H. Frances J. Bligh; Patrick D. Larkin; Paul S. Roach; Christopher A. Jones; Hongyong Fu; William D. Park (Plant Molecular Biology, 1998)

Anchor probes for comparative mapping of grass genera - A. E. Van Deynze; M. E. Sorrells; W. D. Park; N. M. Ayres; H. Fu; S. W. Cartinhour; E. Paul; S. R. McCouch (Theoretical and Applied Genetics, 1998)

Expression and Immunolocalisation of the Snowdrop Lectin, GNA in Transgenic Rice Plants - Duraialagaraja Sudhakar; Xiangdong Fu; Eva Stoger; Sarah Williams; Jacqui Spence; David P. Brown; Muthusamy Bharathi; John A. Gatehouse; Paul Christou (Transgenic Research, 1998)

Old age, multiple formations or genetic plasticity? Clonal diversity in the uniparental Caucasian rock lizard, Lacerta dahli - Robert W. Murphy; Ilya S. Darevsky; Ross D. MacCulloch; Jinzhong Fu; Larissa A. Kupriyanova; Darlene E. Upton; Felix Danielyan (Genetica, 1997)

The dual role of mRNA half-lives in the expression of the yeast ALG7 gene - Kelley Lennon; Alberto Bird; Young-Fu Chen; Robert Pretel; Maria A. Kukuruzinska (Molecular and Cellular Biochemistry, 1997)

Comparative Analyses of Soil Contaminant Levels and Plant Species Diversity at Developing and Disused Oil Well Sites in Qianjiang Oilfield, China - Z.-T. Xiong; H.-X. Hu; Y.-X. Wang; G.-H. Fu; Z.-Q. Tan; G.-A. Yan (Bulletin of Environmental Contamination and Toxicology, 1997)

Case 23 nomination of precursory seismic quiescence as a significant precursor - Max Wyss; R. E. Habermann; P. Bodin; Carl Kisslinger; R. O. Burford; F. W. Klein; A. C. Johnson; Zhengxiang Fu (Pure and Applied Geophysics, 1997)

Determination of thein situ forces and force distribution within the human anterior cruciate ligament - Glen A. Livesay; Hiromichi Fujie; Shinji Kashiwaguchi; Duane A. Morrow; Freddie H. Fu; Savio L. -Y. Woo (Annals of Biomedical Engineering, 1995)

Effect of waterborne and dietary cadmium on plasma ions of the teleostOreochromis mossambicus in relation to water calcium levels - H. B. Pratap; H. Fu; R. A. C. Lock; S. E. Wendelaar Bonga (Archives of Environmental Contamination and Toxicology, 1989)